Universal precursors for nanoscale morphologies

JP2022554198A5Active Publication Date: 2025-02-18NEWSOUTH INNOVATIONS PTY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022524195
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-10-25
Filing Date
2020-10-26
Publication Date
2025-02-18
Estimated Expiration
2040-10-26

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present disclosure relates to metal coordination polymers. In particular, the present disclosure relates to layered metal coordination polymers that can be used as precursors to form nanostructures of various morphologies and compositions. The present disclosure also relates to metal-based nanostructures that can be prepared from the metal coordination polymers. The nanostructures can have various catalytic properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to Australian Provisional Patent Application No. 2019904036, filed on October 25, 2019, the entire contents of which are incorporated herein by reference.

[0002] The present disclosure relates to metal coordination polymers. In particular, the present disclosure relates to layered metal coordination polymers that can be used as precursors to form nanostructures of various morphologies and compositions. The present disclosure also relates to metal-based nanostructures that can be prepared from the metal coordination polymers. [Background technology]

[0003] Two-dimensional structures (e.g., sheets, including nanosheets) have established a new level of functionality for materials, especially in energy and environmental applications. Minimization of transverse charge carrier diffusion distances is achieved by reducing the sheet thickness. However, sheet thickness can only be reduced to the extent that the structure and chemistry of the sheet can dictate the sheet thickness.

[0004] Another way to minimize charge carrier diffusion is to reduce the lateral distance of the sheets, for example by the introduction of pores. The formation of pores in nanosheets enhances the density of accessible active sites and reduces the distance of lateral charge carrier diffusion. However, to minimize the transverse dispersion distance in porous 2D materials, sheets with thicknesses in the atomic range should be achieved. Furthermore, to preserve highly active sheets, polycrystalline 2D planar materials are desirable to prevent irreversible re-stacking of nanosheets. However, the synthesis of polycrystalline porous 2D sheets by either top-down or bottom-up strategies remains elusive for most compounds.

[0005] The production of porous 2D graphene and porous 2D transition metal chalcogenides (TMC) and selenides (TMS) has been reported. However, the processing is relatively complicated and requires surfactants, sacrificial templates, and / or additional steps to remove the template at high temperatures, which ultimately results in nanosheets with thicknesses of tens of nanometers. However, to date, there is little information on the effective synthesis of porous 2D metal oxides (MOs).

[0006] It is understood that where any prior art publication is referred to herein, no admission is made by such reference that the publication forms part of the general knowledge in the art in Australia or any other country.

[0007] The present inventors have conducted research and developed metal coordination polymers that can be used to fabricate a variety of metal-based nanostructures, including porous metal oxide nanosheets. In particular, as described herein, metal coordination polymers are inherently unstable and contain reactive metal centers that can be stabilized by the presence of one or more organic linkers. When used as precursors, removal of the organic linkers produces highly reactive metal-based substructures that can then be used to form a variety of stable nanostructures, allowing tailored and unique processes for preparing nanostructures with altered morphologies.

[0008] The metal coordination polymer may be a layered metal coordination polymer. The layered metal coordination polymer may include two or more layers. The layers of the metal coordination polymer each include a metal atom coordinated to one or more organic linkers to form a metal coordination polymer layer. Two or more of these metal coordination polymer layers may interact electrostatically to form a layered metal coordination polymer. The electrostatic interaction may form between the metal coordination polymer layers. The organic linker includes a metal binding moiety, which may form a coordinate bond to the metal atom to form a metal coordination polymer layer. The organic linker also includes one or more moieties to form an electrostatic interaction with an adjacent metal coordination polymer layer to form a layered metal coordination polymer. The one or more moieties may be substituted on an optionally interrupted alkyl, alkenyl, or alkynyl group and / or directly substituted on the metal binding moiety. The metal coordination polymer may also be a reaction product of an organic linker and a source of metal atoms.

[0009] In one embodiment, a layered metal coordination polymer comprising two or more layers, Each layer comprises a metal atom coordinated to an organic linker to form a metal coordination polymer layer; wherein the organic linker is represented by Formula 1: XR 1 (1) and wherein the compound is selected from one or more compounds having the structure During the ceremony: X is a metal binding moiety for coordinating to a metal atom; and R 1 is H, or an optionally interrupted alkyl, alkenyl, or alkynyl group substituted with one or more moieties to form electrostatic interactions with adjacent metal coordination polymer layers to form said layered metal coordination polymer.

[0010] In another aspect, there is provided a layered metal coordination polymer that is the reaction product of an organic linker and a source of metal atoms, The layered metal coordination polymer comprises two or more layers, each layer comprising a metal atom coordinated to an organic linker to form a metal coordination polymer layer; wherein the organic linker is represented by Formula 1: XR1 (1) and wherein the compound is selected from one or more compounds having the structure During the ceremony: X is a metal binding moiety for coordinating to a metal atom; and R 1 is an optionally interrupted alkyl, alkenyl or alkynyl group substituted with one or more moieties to form electrostatic interactions with adjacent metal coordination polymer layers to form a layered metal coordination polymer.

[0011] In another aspect, there is provided a process for preparing a layered metal coordination polymer comprising two or more metal coordination polymer layers, as defined above, comprising the steps of: Combining a metal atom source and an organic linker to form a layered metal coordination polymer comprising two or more metal coordination polymer layers held together by electrostatic interactions. The present invention provides a process including:

[0012] In another aspect, there is provided a process for preparing a layered metal coordination polymer comprising two or more metal coordination polymer layers, as defined above, comprising the steps of: mixing an aqueous solution containing a metal atom source and an organic linker to form a layered metal coordination polymer containing two or more metal coordination polymer layers held together by electrostatic interactions; The present invention provides a process including:

[0013] In another aspect, there is provided a method of forming a nanostructure, comprising the steps of: providing a layered metal coordination polymer comprising two or more layers, each layer comprising a metal atom each coordinated to one or more organic linkers to form the metal coordination polymer; removing at least a portion of the coordinating organic linkers to form a nanostructure; The present invention provides a method comprising:

[0014] In another aspect, there is provided a nanostructure prepared using a method as defined above.

[0015] In another embodiment, a porous metal oxide nanosheet is provided. The porous metal oxide nanosheet may have a thickness of about 1 nm to about 100 nm.

[0016] In another aspect, there is provided a catalyst composition comprising the nanostructures defined above.

[0017] In another aspect, there is provided the use of a nanostructure as defined above as a catalyst.

[0018] It is understood that any one or more of the embodiments and examples described herein for metal coordination polymers may also be applied to the processes for preparing metal coordination polymers, the methods for preparing nanostructures described herein, the nanostructures described herein, and / or the catalyst compositions described herein. Any embodiment herein should be construed to apply mutatis mutandis to any other embodiment unless specifically stated otherwise. It is also understood that other aspects, embodiments, and examples of metal coordination polymers and nanostructures are described herein.

[0019] It is also understood that certain features of the metal coordination polymers, processes for preparing metal coordination polymers, nanostructures, and methods for preparing nanostructures, as described herein, identified in some aspects, embodiments, or examples, are not required in all aspects, embodiments, or examples, as described herein, and the application should be read in this context. It is also understood that in the various aspects, embodiments, or examples, the order of method or process steps is not essential and may be varied.

[0020] Embodiments of the present disclosure will now be further described, by way of example only, with reference to the accompanying drawings, where applicable, in which: [Brief description of the drawings]

[0021] [Figure 1]We show the exfoliation and transformation of Ce coordination polymer (CP) nanotubes into porous 2D CeO2-x nanostructures: a–c) ex situ SEM, TEM, schematics of Ce-CP hexagonal; d–f) ex situ SEM, TEM, schematics of Ce-CP nanosheets obtained by exfoliation of Ce-CP hexagonal nanotubes at room temperature for 4 min; g–i) ex situ SEM, TEM, schematics of Ce-CP nanosheets obtained by exfoliation of Ce-CP hexagonal nanotubes at room temperature for 8 min; j–l) ex situ SEM, TEM, schematics of porous CeO2-x nanosheets obtained by exfoliation of Ce-CP hexagonal nanotubes in basic aqueous solution (pH = 8) at room temperature for 15 min; m) schematics of the layered structure of Ce-CP; n) Ce-CP exfoliated nanosheets as a result of penetration of water molecules between stacked Ce-CP nanosheets; and o) CeO2-x nanosheets with many defects. The blue, green, red, brown, and black spheres represent cerium, chlorine, oxygen, carbon, and hydrogen ions, respectively. The gaps in the defective CeO2-x nanosheets represent oxygen vacancies. [Figure 1A] A schematic of the layered (layered) structure of Ce-CP. Large yellow sphere = Ce4+, small green sphere = C4+, small black sphere = H+, small blue sphere = O2-, small red sphere = Cl-. [Diagram 2] Defect and structural analysis of CeO2-x porous nanosheets: a, b) low magnification HAADF images of CeO2-x nanosheets; c) high magnification HAADF image of CeO2-x nanosheets showing nanopores with lateral sizes of about 2-5 nm; d) EELS spectrum from intercrystalline regions in CeO2-x nanosheets; e) EELS spectrum from within CeO2-x crystallites; and f) high magnification HAADF image showing Ce vacancies within CeO2-x crystallites. [Diagram 3]Characterization of porous metal oxide (MO) nanosheets: a) TEM images of CeO2-x nanosheets, b) TiO2-x nanosheets, c) ZrO2-x nanosheets; d) corresponding SAED patterns of CeO2-x nanosheets, e) TiO2-x nanosheets, f) ZrO2-x nanosheets; g) AFM images of CeO2-x nanosheets, h) TiO2-x nanosheets, i) ZrO2-x nanosheets; and j) corresponding height profiles of CeO2-x nanosheets, k) TiO2-x nanosheets, l) ZrO2-x nanosheets. [Figure 4] Characterization of transition metal oxides (TMOs) in 0D / 2D heterostructures: a–c) EDS mapping of Fe2O3-functionalized CeO2-x nanosheets (FCO), NiO-functionalized CeO2-x nanosheets (NCO), and ZnO-functionalized CeO2-x nanosheets (ZCO), respectively; d–f) Laser Raman microspectra of FCO, NCO, and ZCO, respectively; and g–i) XRD patterns of FCO, NCO, and ZCO, respectively. [Diagram 5] Characterization of the band structures of CeO2-x and 0D / 2D heterostructures is shown: a) topography of CeO2-x porous nanosheets; b) contact potential difference measured by KPFM of CeO2-x porous nanosheets; c) XPS valence band plot of CeO2-x porous nanosheets; d) Tauc plot from UV-Vis spectrophotometric data of CeO2-x porous nanosheets (Tauc plot model (αhν)=A(hν-Eg) 2 applied, where A and α are the absorption and absorption coefficients, respectively; hν is the photon energy, and Eg is the photon indirect band gap); e) electronic energy level diagrams of CeO2-x porous nanosheets and 0D / 2D heterostructures; f) first-principles DFT calculations of electronic density of states and band gap of CeO2 nanosheets and bulk CeO2; and g~i) first-principles DFT calculations of electronic density of states and band gap of 0D / 2D heterostructures. [Figure 6]Figure 1 shows the formation mechanism of Ce-CP tubes by galvanostatic electrochemical deposition method. a) Current-deposition time plot; b–f) SEM images depicting the nucleation / growth process of Ce-CP tubes as a function of electrodeposition time. [Figure 7] Figure 2 shows a Pourbay diagram illustrating the thermodynamic study of the aqueous quaternary system Ce(III)-Ce(IV)-trichloroacetic acid (TCA)-HO as a function of pH. [Figure 8] 1 shows the experimental X-ray diffraction pattern of Ce-CP. [Figure 9] 4 shows the neutron diffraction patterns of Ce-CP obtained at wavelengths of 1.63 Å and 2.41 Å. [Figure 10] Shown is an SEM image of Ce-CP tubes grown on an FTO substrate. [Figure 10A] a) Low magnification TEM image of a single Ce-CP tube, b) SAED pattern of the area shown in the yellow box, and c) HRTEM image of the area shown in the red box. [Figure 11] Raman spectra of the Ce-CP tube (top) and trichloroacetic acid (bottom) are shown. [Figure 11A] Raman spectra of CeO2 (top), Ce-CP tube (middle) and trichloroacetic acid (bottom). [Figure 12] FTIR spectrum of Ce-CP tube. [Figure 13] XPS data of Ce-CP tubes is shown. [Figure 14] TGA analysis of Ce-CP in nitrogen (top) and air (bottom) atmosphere is shown. [Figure 15] The Rietveld refined X-ray diffraction pattern of Ce-CP is shown. [Figure 16] The Rietveld refined ND patterns of Ce-CP at wavelengths of 1.63 Å (bottom) and 2.41 Å (top) are shown. [Figure 17] A schematic of the refined structure from XRD and ND data is shown. [Figure 18A]The relaxed structure of the smallest possible Ce-CP unit cell is shown, which was used as a building block to construct a more representative structural model. [Figure 18B] (a) Structure shows relaxed Ce-CP corresponding to experimental lattice parameters. All TCA molecules were found to remain intact. A, B, and C indicate Ce ions bound to TCA molecules, water molecules, and OH groups, respectively. (b-e) Site-projected partial density of states of labeled Ce ions and labeled O ions from well-defined coordinating ligands. [Figure 19] Comparison of X-ray diffraction patterns of experimental, Rietveld refined, and initial MD simulated structures. [Figure 20] The structural and morphological evolution from Ce-CP hexagonal nanotubes to CeO2-x nanosheets is shown: a) SEM image of Ce-CP hexagonal nanotubes; b) TEM image of Ce-CP hexagonal nanotubes (inset: SAED pattern); c) XRD pattern of Ce-CP hexagonal nanotubes; d) SEM image of Ce-CP nanosheets; e) TEM image of Ce-CP nanosheets (inset: SAED pattern); f) XRD pattern of Ce-CP nanosheets; g) SEM image of porous CeO2-x nanosheets; h) TEM image of porous CeO2-x nanosheets (inset: SAED pattern); i) XRD pattern of CeO2-x nanosheets. [Figure 21] a) TEM image of Ce-CP nanosheets, b) EDS elemental mapping images of cerium (red), c) oxygen (green), d) chlorine (dark blue), and e) carbon (light blue), and f) EDS spectrum of Ce-CP nanosheets. [Figure 22] a, b) Bright-field TEM images of CeO2-x porous nanosheets, c) EDS elemental mapping images of oxygen (green) and d) cerium (red), and e) EDS spectrum of CeO2-x porous nanosheets. [Figure 23] The Raman spectra of CeO2-x nanosheets compared to that of pristine Ce-CP are shown, showing no significant difference. [Figure 24] The SEM image of Ti-CP is shown. [Diagram 25] Shown are SEM images of Ti-CP, b) EDS elemental mapping images of titanium, c) oxygen, and d) carbon, e) overlay of EDS images of Ti-CP, and f) corresponding EDS spectrum. [Figure 26] The Raman spectrum of Ti-CP is shown. [Figure 27] An SEM image of Zr-CP is shown. [Figure 28] a) SEM image of Zr-CP, b) EDS elemental mapping images of zirconium, c) oxygen, and d) carbon, e) overlay of the EDS images of Zr-CP, and f) corresponding EDS spectra. [Figure 29] The Raman spectrum of Zr-CP is shown. [Diagram 30] a-c) TEM images of ultrathin Ti-CP nanosheets exfoliated in DI water at room temperature. [Diagram 31] a-c) TEM images of ultrathin porous TiO2 nanosheets along with d) the corresponding SAED pattern of the TiO2 nanosheets. [Diagram 32] Raman spectrum of TiO2 nanosheets (black) and the corresponding fitting of vibrational modes of the anatase (blue) and rutile (red) phases. [Diagram 33] XPS results of carbon 1s orbitals in both Ti-CP and TiO2 nanostructures are shown. [Diagram 34] XPS results of oxygen 1s orbitals in both Ti-CP and TiO2 nanostructures are shown. [Diagram 35] TEM images showing the exfoliation of bulk Zr-CP in DI water at room temperature and the formation of free-standing Zr-CP nanosheets. [Diagram 36] a-c) TEM images of ultrathin porous ZrO2 nanosheets obtained by exfoliation of Zr-CP in DI water at room temperature, d) SAED pattern of ZrO2 nanosheets revealing the polycrystalline nature of the nanosheets. [Figure 37] Raman spectrum of zirconia oxide nanosheets (black) and the corresponding fitting of the vibrational modes of the monoclinic (blue) and cubic (red) phases. [Figure 38] XPS results of carbon 1s orbitals in both Zr-CP and ZrO2 nanostructures are shown. [Figure 39] XPS results of carbon 1s orbitals in both Zr-CP and ZrO2 nanostructures are shown. [Diagram 40] The XPS results of the cerium 3d orbital and the oxygen 1s orbital in the CeO2-x porous nanostructure are shown. [Diagram 41] Figure 1 shows the zeta potential of CeO2-x in DI water. [Diagram 42] Speciation diagrams of a) Fe(II), b) Ni(II), and c) Zn(II) species showing the species stability and the change in species concentration as a function of pH in aqueous solution. [Diagram 43] TEM and HRTEM images of FCO; d) SAED pattern of FCO; e-g) TEM and HRTEM images of NCO; h) SAED pattern of NCO; i-k) TEM and HRTEM images of ZCO; l) SAED pattern of ZCO. [Diagram 44] XPS valence measurements of a) porous CeO2-x nanosheets, b) FCO, c) NCO, and d) ZCO. [Diagram 45] Tauc plots of a) porous CeO2-x nanosheets, b) FCO, c) NCO, and d) ZCO. [Figure 46] Photoluminescence spectra of CeO2-x, FCO, NCO, and ZCO are shown. [Figure 47] a) Methylene blue (MB) decomposition in the presence of porous nanosheets (blue bars) and NiO (purple) and Fe2O3 (green) anchored porous nanosheets; b) MB decomposition kinetics; c) Comparison table between as-synthesized samples and recently reported results of MB decomposition; d) Summary of the MB decomposition performance of CeO2-x structures. [Figure 48] TEM and SEM micrographs of Ce-CP-derived CeO2-x nanostructures (scale bars yellow = 3 μm, red = 100 nm). For f and h, low magnification TEM images are shown instead of SEM images due to the small size of the cubic and dumbbell morphologies, respectively. [Figure 49] a) Three-electrode electrochemical cell used for the synthesis of Ce-CP tubes under intense oxygen evolution and deposition of free-standing hexagonal tubes of Ce-CP on fluorine-doped tin oxide (FTO) substrates; b) Schematic diagram of the formation of CeO2-x through a three-step process, including the exfoliation of the Ce-CP tubes to Ce-CP nanosheets and the subsequent oxidation of the Ce-CP nanosheets to porous CeO2-x nanosheets. [Figure 50] a) Chronopotentiometric electrodeposition of solid Ce-CP hexagonal rods under electrolytic conditions; b) decomposition of Ce-CP hexagonal rods and recrystallization of Ce-CP into hollow pseudooctahedra; c) simplified molecular structure of hexagonal Ce-CP rods; d) schematic of solutes in ethanol solution; e) corresponding molecular structure; f) schematic of recrystallized Ce-CP; g) schematic of corresponding molecular structure. Large yellow sphere = Ce4+, small green sphere = C4+, small blue sphere = O2, small red sphere = Cl-. [Figure 51] (a, b) SEM and (c, d) TEM images of the Ce-CP structures are shown (insets show SAED patterns, respectively). [Figure 52] Experimental X-ray diffraction patterns obtained from (a) freshly prepared Ce-CP and (b) a 3-month aged sample (under ambient conditions) are shown. [Diagram 53] (a) Formation of Ce-CP monolayer at the ethanol / air interface: Ce4+ (green), -OH groups of ethanol (purple), -COO- groups of TCA (blue), and -CCl3 groups of TCA (red); b) monolayer and stacked arrangements (residues -OH and HO are omitted from Ce-CP and solution volumes for simplicity); c) optical microscope image of Ce-CP nanosheets; d) AFM image of Ce-CP nanosheets and corresponding indicators for height profile; e) low magnification TEM image of Ce-CP nanosheets; inset: SAED pattern of Ce-CP nanosheets; f-k) schematic of EDS mapping of Ce-CP nanosheets showing maps of (g) Ce; h) O; i) Cl; j) C; k) Sn. [Figure 54]AFM images and corresponding height profiles of Ce-CP nanosheets printed from an ethanol surface with evaporation times of a) 12 h, b) 24 h, c) 36 h, d) 48 h, and (e) 72 h. [Figure 55] AFM images and corresponding height profiles of Ce-CP nanosheets printed from the surface of ethanol at different Ce-CP concentrations: a, b) 4 M, c, d) 8 M. [Figure 56] a, b) HAADF images and (b, inset) SAED image of porous CeO2-x nanosheets; c) HRTEM image of porous CeO2-x nanosheets; d) XPS spectrum of Ce 3d orbitals in porous CeO2-x nanosheets; e) AFM image of porous CeO2-x nanosheets; f) AFM height profile of CeO2-x nanosheets. [Figure 57] a) SEM image, b) schematic of as-recrystallized Ce-CP, c) corresponding XRD pattern, d) SEM image, e) schematic of NaOH aged CeO2-x pseudo-octahedron, f) corresponding XRD pattern, g) SEM image, h) schematic of CeO2-x pseudo-octahedron, i) corresponding XRD pattern, j) dark-field TEM and SAED (inset), k) dark-field HRTEM image of CeO2-x pseudo-octahedron. [Figure 58] (a) XRD patterns of Ce-CP rods (black) synthesized by electrochemical deposition and Ce-CP octahedra (red) obtained by decomposition / recrystallization method in ethanol; b) HRTEM images of Ce-CP rods (left) and Ce-CP octahedra (areas surrounded by yellow solid lines indicate single crystals); c) Raman spectra of Ce-CP rods (black) and Ce-CP octahedra (red); d) FTIR spectra of Ce-CP rods (black) and Ce-CP octahedra (red). [Figure 59]SEM images of Ce-CP morphology synthesized at 0 °C: a) [Ce-CP] = 4 M, b) [Ce-CP] = 16 M, c) hollow spheres being released from nanosheets, d) schematic showing the formation of Ce-CP hollow spheres via bubbling of stacked nanosheets as a result of ethanol evaporation, e) 3D AFM image of Ce-CP nanosheets synthesized by two-step evaporation at -10 °C (12 h) and 15 °C (0.5 h), f) AFM height profile (black dotted line). [Figure 60] Characterization of hollow CeO2-x spheres: a) low magnification SEM image of hollow CeO2-x spheres, b) high magnification SEM image of hollow CeO2-x spheres, c) SEM image of damaged hollow spheres, d) low magnification TEM image of hollow CeO2-x spheres, e, f) high magnification TEM images of hollow CeO2-x spheres, g) SAED pattern of hollow CeO2-x spheres, h, i) EDS elemental mapping of Ce and O in hollow CeO2-x spheres, j) Raman spectra of Ce-CP rods before and after NaOH aging and heating at 200 °C. [Figure 61] SEM images of Ce-CP nanostructures synthesized at 25 °C using varying concentrations of Ce-CP: a) 4 M, b) 8 M, c) 40 M, d) 120 M; e-h) SEM images of the corresponding CeO2-x nanostructures derived from Ce-CP by aging in NaOH (6 M) at 25 °C followed by heating at 200 °C. [Figure 62] SEM, TEM, HRTEM images, and SAED patterns of CeO2-x derived from Ce-CP morphology synthesized at 25 °C: a–c) 5 mM, d–f) 10 mM, g–i) 50 mM, and j–l) 100 mM are shown. [Figure 63] The formation mechanism of Ce-CP nanostructures is shown. [Figure 64] a) CO conversion rate and TOF values ​​for CO oxidation obtained using different nanostructure morphologies of CeO2-x, b) Arrhenius plot for CO oxidation across samples. [Figure 65] XPS Ce 3d spectra of porous nanosheets, hollow octahedra, hollow spheres, and exfoliated CeO2-x are shown. [Figure 66]XPS Ce 3d spectra of porous nanosheets, hollow octahedra, hollow spheres, and exfoliated CeO2-x are shown. [Figure 67] Photocatalytic performance of CeO2-x morphologies: a) UV-Vis absorption spectra of MB dye solution after 160 min of irradiation for different morphologies, (b) 664 nm peak intensity based on UV-Vis absorption spectra of MB dye solution at different irradiation times for different morphologies, c) Plot of absorbance (At / A0, time t vs. initial time) and dye degradation as a function of irradiation time of porous nanosheets, d) Comparison of the photocatalytic performance obtained in this work with that of the prior art under similar test conditions. [Figure 68] The effects of morphology, structure and physical properties on their catalytic and photocatalytic performance are demonstrated. [Figure 69] 4 shows the zeta potential of layered Ce-CPs in DI water. [Figure 70] Structural analysis: a) XRD spectra and b) laser Raman microspectra (all intensities are on the same scale) of Ce-CP nanotubes, reconstructed Ce-CP macrolayers (DMSO-derived, R-Ce-CP), air-burned Ce / S / C, and N2-burned Ce / S / C. [Figure 71] XPS spectra of a) Cl 2p, b) C 1s, and c) S 2p orbitals of Ce-CP nanotubes (NTs), Ce-CP derived from DMSO (T room temperature), Ce / S / C burned in air (air), and Ce / S / C burned in N2 (N2). [Figure 72] XPS spectra of (a) Ce 3d orbitals and (b) O 1s orbitals of Ce-CP, Ce-CP derived from DMSO, Ce / S / C burned in air, and Ce / S / C burned in N2 are shown. [Figure 73] The EPR analysis of Ce / S / C and pristine CeO2 is shown. [Figure 74] Figure 1 shows the XRD patterns of the polycrystalline octahedral nanostructures compared with those of pristine Ce-CP. [Figure 75]a) HAADF-STEM image and EELS-STEM map of the Ce-OS sample. The map was obtained by extracting the SK edge signal at 165 eV (green), the CK edge signal at 284 eV (yellow), the OK edge at 532 eV (blue), and the CeM edge at 883 eV (red). b) CeM5 / M4 ratio to evaluate the cerium oxidation state distribution, color legend is also reported. c) Normalized EELS spectrum of the CK edge peak and d) CeM edge peak. Scale bar is 100 nm. [Figure 76] HRTEM images from the sample are shown together with the corresponding indexed power spectrum and frequency filtered maps highlighting the different crystallites. [Figure 77] a) Schematic of the two-step process of exfoliating Ce-CP nanotubes in a stirred TEA solution and oxidizing them in air at 450 °C to layered CeO2-x macrolayers, b–e) showing the CeO2-x morphology derived from Ce-CP. [Figure 78] SEM images of CeO2-x obtained at 450 °C with different heating rates: a) slow combustion at 0.2 °C min-1, b) medium combustion at 1.0 °C min-1, c) fast combustion at 2.0 °C min-1, and d) fast combustion at 3.0 °C min-1. [Figure 79] a-c) SEM images of hybrid 2D-3D CeO2-x, d) HRTEM image and SAED (outlining pores) of porous 2D CeO2-x nanosheets, e) EDS elemental mapping of porous 2D CeO2-x nanosheets, f) AFM image (step height at white dotted line) and corresponding height profile of porous 2D CeO2-x nanosheets. [Figure 80] a) TEM and b) HRTEM images of porous Mn-Ce nanosheets, c) SAED pattern of porous Mn-Ce nanosheets, d) STEM elemental mapping of O, Mn, and Ce in the porous Mn-Ce nanosheets, e) STEM line scan across the porous Mn-Ce nanosheets. [Figure 81]XRD spectra of 2D-3D CeO2-x, Mn-Ce, and Cu-Ce are shown (α-MnO2 is shown by Miller indices in Mn-Ce). [Figure 82] a) CO oxidation plots for Ce-NT, CeO2-x, Mn-Ce, and Cu-Ce; b) Comparative CO oxidation data for CeO2-x and CeO2-x-based hybrids; c) Mechanism 1: CO oxidation reaction pathway upon initial O2 adsorption estimated from first-principles DFT calculations; d) Calculated energy profile for mechanism 1; e) Mechanism 2: CO oxidation reaction pathway upon initial CO adsorption estimated from first-principles DFT calculations; f) Calculated energy profile for mechanism 2. MODE FOR CARRYING OUT THE PRESENTINVENTION

[0022] General terminology In the following description, reference is made to the accompanying drawings that form a part hereof, and in which several embodiments are shown by way of illustration, It is understood that other embodiments may be utilized and structural changes may be made without departing from the scope of the present disclosure.

[0023] With respect to the definitions provided herein, the defined terms and phrases include the meanings provided unless otherwise stated or implicit from the context. Unless expressly stated otherwise or clear from the context, the following terms and phrases do not exclude the meaning that the term or phrase would have in the art to which it pertains. For example, all technical and scientific terms used herein should be interpreted to have the same meaning as commonly understood by those of ordinary skill in the art (e.g., materials science, inorganic chemistry, polymer chemistry, nanotechnology, etc.). The definitions are provided to help explain certain embodiments and are not intended to limit the invention as set forth in the claims, since the scope of the invention is limited only by the claims. Further, unless otherwise required by context, the singular includes the plural and the plural includes the singular.

[0024] All publications discussed and / or referenced herein are incorporated herein in their entirety.

[0025] Any discussion of documents, acts, materials, devices, articles or the like which has been included in the present specification is solely for the purpose of providing a context for the present invention and is not to be construed as an admission that any or all of such matter forms part of the prior art or was common general knowledge in the art relevant to this disclosure as it existed prior to the priority date of each claim of this application.

[0026] Throughout this disclosure, unless specifically stated otherwise or the context requires otherwise, a single step, composition of matter, group of steps, or group of compositions of matter should be construed to include one and a plurality (i.e., one or more) of those steps, compositions of matter, group of steps, or group of compositions of matter. Thus, as used herein, the singular forms "a," "an," and "the" include plural aspects unless the context clearly dictates otherwise. For example, reference to "a" includes the singular as well as two or more; reference to "an" includes the singular as well as two or more; reference to "the" includes the singular as well as two or more, etc.

[0027] Those skilled in the art will recognize that the present disclosure herein is susceptible to variations and modifications other than those specifically described. The present disclosure is to be understood to include all such variations and modifications. The present disclosure also includes, individually or collectively, all embodiments, steps, features, methods, compositions, coatings, processes, and coated substrates referred to or shown in this specification, as well as any and all combinations or any two or more of said steps or features.

[0028] The term "and / or", e.g., "X and / or Y", shall be understood to mean either "X and Y" or "X or Y" and shall be interpreted as providing explicit support for both or either meanings. As used in this application, the term "or" is intended to mean an inclusive "or" rather than an exclusive "or". That is, unless otherwise indicated or clear from the context, "X employs A or B" is intended to mean any of the inherent inclusive permutations. That is, if X employs A, X employs B, or X employs both A and B, then "X employs A or B" is satisfied in any of the above cases. Furthermore, at least one of A and B and / or the like generally means A or B, or both A and B. In addition, the articles "a" and "an" as used in this application and the appended claims may be generally interpreted to mean "one or more" unless otherwise indicated or clear from the context directed to the singular form.

[0029] Unless otherwise specified, terms such as "first," "second," "further," and the like are used herein merely as labels and are not intended to impose any order, position, or hierarchy on the items to which they refer. Furthermore, a reference to a "second" item does not require or preclude the presence of lower-numbered items (e.g., a "first" item) and / or higher-numbered items (e.g., a "third" item).

[0030] As used herein, the phrase "at least one of" when used with respect to a list of items means that different combinations of one or more of the listed items may be used, and only one of the items in the list may be required. The items may be specific objects, things, or categories. In other words, "at least one of" means any combination of items, or a number of items from the list may be used, but not all items in the list are required. For example, "at least one of item A, item B, and item C" may mean item A; item A and item B; item B; item A, item B, and item C; or item B and item C. In some cases, "at least one of item A, item B, and item C" may mean, for example, but not limited to, two items A, one item B, and ten items C; four items B and seven items C; or some other suitable combination.

[0031] As used herein, the term "about" typically refers to + / - 10%, for example + / - 5%, of a particular value, unless otherwise specified.

[0032] It should be understood that certain features that are described in this specification in the context of separate embodiments may also be provided in combination in a single embodiment. Conversely, various features that are, for brevity, described in the context of a single embodiment may also be provided separately or in any subcombination.

[0033] Throughout this specification, various aspects and components of the invention may be presented in a range format. The range format is included for convenience and should not be construed as an inflexible limitation on the scope of the invention. Thus, the description of a range should be considered to have specifically disclosed all possible subranges as well as individual numerical values ​​within that range, unless specifically indicated otherwise. For example, description of a range such as 1-5 should be considered to have specifically disclosed subranges such as 1-3, 1-4, 1-5, 2-4, 2-5, 3-5, as well as individual and partial numbers within the recited range, e.g., 1, 2, 3, 4, 5.5, and 6, unless an integer is required or implied by context. This applies regardless of the breadth of the disclosed range. If specific values ​​are required, they will be set forth herein.

[0034] Throughout this specification, the words "comprise" or variations such as "comprises" or "comprising" will be understood to imply the inclusion of a referred element, integer or step, or group of elements, integers or steps, but not the exclusion of any other element, integer or step, or group of elements, integers or steps.

[0035] Variations such as the term "consists of" or "consisting of" refer to the inclusion of any mentioned element, integer or step, or group of elements, integers or steps, that are recited in the context of the term, to the exclusion of any other element, integer or step, or group of elements, integers or steps, that are not recited in the context of the term.

[0036] Specific Terms The following definitions apply to terms used throughout this specification, unless specifically limited in specific instances.

[0037] The term "organic linker" refers to a compound capable of forming one or more coordinate bonds to one or more metal atoms.

[0038] The term "metal binding moiety" refers to a chemical moiety capable of coordinating to (e.g., binding to) a metal. Non-limiting examples of metal binding ligand moieties include -COOH, -OH, -NH2, -SH, and -CN.

[0039] The term "optionally substituted" means that the functional group is either substituted or unsubstituted at any available position. It is to be understood that "unsubstituted" refers to a hydrogen group. The substitution may have one or more heteroatoms, including one or more O, N, S, Se, Te, Si, and / or one or more functional groups selected from one or more alkenyl, alkynyl, aryl, heteroaryl, heteroaryl, and / or cycloalkyl groups, where each alkenyl, alkynyl, aryl, heteroaryl, heteroaryl, and / or cycloalkyl group, each alkenyl, alkynyl, aryl, heteroaryl, heteroaryl, and / or cycloalkyl group, each alkenyl, alkynyl, aryl, heteroaryl, heteroaryl, and / or cycloalkyl group, is as defined herein.

[0040] "Alkyl," whether used alone or in compound words such as alkoxy, alkylthio, alkylamino, dialkylamino, or haloalkyl, refers to a straight or branched chain hydrocarbon ranging in size from 1 to about 20 or more carbon atoms. Thus, unless expressly limited, alkyl moieties include smaller groups, moieties, such as methyl, ethyl, n-propyl, iso-propyl, and / or butyl, pentyl, hexyl, ranging in size from, for example, 1 to about 6 or more carbon atoms, as well as higher isomers including straight or branched chain hydrocarbons ranging in size from, for example, about 6 to about 20 or more carbon atoms. 1-20 Alkyl, C 1-10 Alkyl" and "C 1-6 "Alkyl" refers to a specific alkyl chain length, as described herein.

[0041] "Alkenyl," whether used alone or in compound words such as alkenyloxy or haloalkenyl, refers to a straight or branched chain hydrocarbon containing at least one carbon-carbon double bond, and unless expressly limited, includes smaller groups, moieties, such as ethylene, 1-propenyl, 2-propenyl, and / or butenyl, pentenyl, hexenyl, ranging in size, for example, from 2 to about 6 or more carbon atoms, as well as higher isomers including straight or branched chain hydrocarbons ranging in size, for example, from about 6 to about 10 or more carbon atoms.

[0042] "Alkynyl," whether used alone or in compound words such as alkynyloxy, refers to a straight or branched chain hydrocarbon containing at least one carbon-carbon triple bond, and unless expressly limited, includes smaller groups, moieties, such as ethynyl, 1-propynyl, 2-propynyl, and / or butynyl, pentynyl, hexynyl, and higher isomers including straight or branched chain hydrocarbons ranging in size, for example, from about 6 to about 10 or more carbon atoms.

[0043] "Cycloalkyl" refers to monocyclic or polycyclic carbocyclic ring systems of various sizes, for example, from about 3 to about 10 carbon atoms, such as, for example, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, or cycloheptyl. The term "cycloalkyloxy" refers to the same groups linked through a single oxygen atom, such as cyclopentyloxy and cyclohexyloxy. The term "cycloalkylthio" refers to the same groups linked through a single sulfur atom, such as cyclopentylthio and cyclohexylthio.

[0044] "Aryl," whether used alone or in compound words such as arylalkyl, aryloxy, or arylthio, refers to (i) an optionally substituted monocyclic or polycyclic aromatic carbocyclic moiety of about 6 to about 60 carbon atoms, e.g., phenyl, naphthyl, or fluorenyl; or (ii) an optionally substituted partially saturated polycyclic aromatic carbocyclic ring system in which aryl and cycloalkyl or cycloalkenyl groups are fused together to form a ring structure, e.g., tetrahydronaphthyl, indenyl, indanyl, or fluorene ring.

[0045] "Heterocyclyl" or "heterocyclic", whether used alone or in compound words such as heterocyclyloxy, refers to (i) an optionally substituted cycloalkyl or cycloalkenyl group, e.g., about 3 to about 60 ring members, which may contain one or more heteroatoms such as nitrogen, oxygen, or sulfur (examples include pyrrolidinyl, morpholino, thiomorpholino, or fully or partially hydrogenated thienyl, furyl, pyrrolyl, thiazolyl, oxazolyl, oxazinyl, thiazinyl, pyridyl, and azepinyl); (ii) an optionally substituted partially saturated polycyclic ring system in which an aryl (or heteroaryl) ring and a heterocyclic group are fused together to form a ring structure (examples include chromanyl, dihydrobenzofuryl, and indolinyl); or (iii) an optionally substituted fully or partially saturated polycyclic fused ring system having one or more bridges (examples include quinuclidinyl and dihydro-1,4-epoxynaphthyl).

[0046] "Heteroaryl", whether used alone or in compound words such as heteroaryloxy, refers to (i) an optionally substituted monocyclic or polycyclic aromatic organic moiety, e.g., from about 1 to about 10 ring members, in which one or more of the ring members is an element(s) other than carbon, e.g., nitrogen, oxygen, sulfur, or silicon; a heteroatom(s) interrupting a carbocyclic ring structure and having a sufficient number of delocalized pi-electrons to provide aromaticity, with the proviso that the ring does not contain adjacent oxygen and / or sulfur atoms. Exemplary 6-membered heteroaryl groups are pyrazinyl, pyridazinyl, pyrazolyl, pyridyl, and pyrimidinyl. All positional isomers are contemplated, e.g., 2-pyridyl, 3-pyridyl, and 4-pyridyl. Exemplary 5-membered heteroaryl rings are furyl, imidazolyl, oxazolyl, isoxazolyl, isothiazolyl, oxadiazolyl, pyrrolyl, 1,3,4-thiadiazolyl, thiazolyl, thienyl, triazolyl, and silole. All positional isomers are contemplated, for example, 2-thienyl and 3-thienyl. Bicyclic groups are typically benzo-fused ring systems derived from the heteroaryl groups named above, such as benzofuryl, benzimidazolyl, benzothiazolyl, indolyl, indolizinyl, isoquinolyl, quinazolinyl, quinolyl, and benzothienyl; or (ii) an optionally substituted partially saturated polycyclic heteroaryl ring system in which heteroaryl and cycloalkyl or cycloalkenyl groups are fused together to form a ring structure, such as a tetrahydroquinolyl or pyridinyl ring.

[0047] "Carboxyl" refers to a -CO2H moiety. "Carboxylate" refers to a -CO2 - The two terms may be used interchangeably, as would be understood by one of ordinary skill in the art.

[0048] "Cyano" refers to a -CN moiety.

[0049] "Hydroxyl" refers to an --OH moiety.

[0050] "Alkoxy" refers to an -O-alkyl group, where the alkyl group is as defined above. Examples include methoxy, ethoxy, n-propoxy, iso-propoxy, and the different butoxy, pentoxy, hexyloxy and higher isomers.

[0051] "Amino" or "amine" refers to a -NH2 moiety.

[0052] "Alkylamino" refers to an -NHR or -NR group, where R is an alkyl group as defined above. Examples include, but are not limited to, methylamino, ethylamino, n-propylamino, isopropylamino, and the different butylamino, pentylamino, hexylamino, and higher isomers.

[0053] "Nitro" refers to a -NO2 moiety.

[0054] "Amide" refers to the moiety -C(O)NR1R2.

[0055] "Sulfonyl" refers to a -SO2R group linked to the remainder of the molecule via a sulfur atom.

[0056] "Sulfonamide" refers to the moiety -SO2NR1R2.

[0057] "Alkylsulfonyl" refers to a -SO2-alkyl group, in which the alkyl group is as defined above.

[0058] The terms "thiol," "thio," "mercapto," or "mercaptan" refer to any organosulfo group containing a sulfhydryl moiety, -SH, which includes an R-SH group, where R is a moiety containing a carbon atom covalently bonded to the -SH moiety, e.g., an alkylsulfo group, as defined above. In one embodiment, the thiol or mercapto group is a sulfhydryl moiety, -SH.

[0059] "Alkylthio" refers to an -S-alkyl group, where the alkyl group is as defined above. Examples include, but are not limited to, methylthio, ethylthio, n-propylthio, isopropylthio, and the different butylthio, pentylthio, hexylthio and higher isomers.

[0060] "Cyano" or "nitrile" refers to a -CN moiety.

[0061] The term "halo" or "halogen", whether used alone or in compound words such as haloalkyl, haloalkenyl, haloalkynyl, haloalkoxy, or haloalkylsulfonyl, represents fluorine, chlorine, bromine, or iodine. Furthermore, when used in compound words such as haloalkyl, haloalkenyl, haloalkynyl, haloalkoxy, or haloalkylsulfonyl, the alkyl may be partially halogenated or fully substituted with halogen atoms, which may be independently the same or different. Examples of haloalkyl include, but are not limited to, -CH2CH2F, -CF2CF3, and -CH2CHFCl. Examples of haloalkoxy include, but are not limited to, -OCHF2, -OCF3, -OCH2CCl3, -OCH2CF3, and -OCH2CH2CF3. Examples of haloalkylsulfonyl include, but are not limited to, -SO2CF3, -SO2CCl3, -SO2CH2CF3, and -SO2CF2CF3.

[0062] metal coordination polymer The present disclosure provides metal coordination polymers. Metal coordination polymers are organometallic polymeric structures that contain metal atom centers linked by linkers / ligands. Metal coordination polymers contain repeating coordination entities that can extend in one, two, or three directions.

[0063] The metal coordination polymer may be at least partially amorphous or at least partially crystalline, e.g., a layered metal coordination polymer having ordered regions that provide crystallinity and disordered regions that provide amorphous character. The metal coordination polymer may be crystalline or amorphous. In one embodiment, the metal coordination polymer is crystalline, e.g., polycrystalline, and may, e.g., contain a suitable amount of homogeneity. In another embodiment, the metal coordination polymer is amorphous. It is understood that a crystalline (e.g., polycrystalline) metal coordination polymer is a void-containing framework that includes an array of metal atoms linked by organic linkers. Amorphous metal coordination polymers retain the basic building blocks and connectivity of their crystalline counterparts, but lack any long-range periodic order.

[0064] The metal coordination polymer may have a one-dimensional, two-dimensional, or three-dimensional architecture. The metal coordination polymer may include two or more two-dimensional metal coordination polymer layers (e.g., a layered metal coordination polymer) or may be a metal-organic framework (MOF). In some embodiments, the metal coordination polymer is in the form of a two-dimensional sheet. Two or more two-dimensional sheets may interact electrostatically to form a layered metal coordination polymer. The architecture of the metal coordination polymer is generally determined by the metal(s) and ligand(s) used to form the metal coordination polymer.

[0065] It is to be understood that one-dimensional architectures include, for example, linear structures of metal atoms linked by organic linkers. It is to be understood that two-dimensional architectures include, for example, sheet or layer structures having length and width (e.g., area) dimensions of metal atoms linked by organic linkers. Two-dimensional architectures can electrostatically interact to form layered metal coordination polymers. It is also to be understood that three-dimensional architectures can form structures including, for example, spheres or cubes having length, width, and height (e.g., volume) dimensions of metal atoms linked by organic ligands.

[0066] In some embodiments, a metal coordination polymer can include two or more layers, each layer extending in two dimensions (i.e., a two-dimensional metal coordination polymer layer). Each metal coordination polymer layer can interact (e.g., via electrostatic interactions) to form a layered metal coordination polymer.

[0067] In one embodiment, the layered metal coordination polymer may include at least two layers (e.g., at least two metal coordination polymer layers). The layered metal coordination polymer may be referred to as a bulk layered or layered metal coordination polymer. The term layered means formed or arranged in hierarchical or layered structures. The layered metal coordination polymer may include at least 2, 3, 4, 5, 10, 12, 15, 20, 25, 50, 75, 100, 125, 150, 200, 300, 400, or 500 layers. The layered metal coordination polymer may have a range of layers provided by any two of these upper and / or lower layer count limits, e.g., about 2 to 500, or about 10 to 200, or 20 to 100 layers. The number of layers may be measured using scanning electron microscopy.

[0068] When the metal coordination polymer forms a sheet, multiple sheets can be assembled to form a layered metal coordination polymer. When forming a layered structure, a portion of the organic linker can be sandwiched between adjacent sheets, and in some embodiments (e.g., one or more interspersed between the layers). labile Electrostatic interactions (via ions) can be formed.

[0069] It is understood that the layered metal coordination polymers can form structures with any morphology, including metal coordination polymer layers that can be exfoliated into individual metal coordination polymer layers. The layered metal coordination polymers can also be decomposed and reconstituted in organic solvents, allowing the morphology of the metal coordination polymer to be modified depending on the conditions.

[0070] The layered metal coordination polymer need not be planar. In some embodiments, the layered metal coordination polymer may form in the shape of a tube or rod. For example, the layers may wrap around the central axis of the layered metal coordination polymer. Suitable morphologies may include, but are not limited to, sheet-like, hollow, cubic, rod-like, polyhedral, spherical or hemispherical, round or semicircular, angular, and irregular morphologies. For example, the layered metal coordination polymer may form layers (e.g., hexagonal Ce-CP nanotubes) or hexagonal nanotubes including irregular layered structures. The layered metal coordination polymer forms structures with aspect ratios (i.e., the ratio of length to width, where length and width are measured perpendicular to one another and length refers to the longest linearly measured dimension) of 1.0-100.0, 1.0-50.0, or 1.0-20.0. The morphology may be determined using scanning or transmission electron microscopy.

[0071] The layered metal coordination polymer may have an average pore size. In some embodiments, the average pore size of the layered metal coordination polymer may be at least 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 50, 80, or 100 nm. The average pore size of the layered metal coordination polymer may be less than 100, 80, 50, 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, 2, or 1 nm. The pore size may be in the range provided by any two of these upper and / or lower average pore sizes, for example, from about 1 nm to about 50 nm or from about 5 nm to about 20 nm. The pore size may be about 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 nm.

[0072] The layered metal coordination polymer can have an average pore volume of at least about 0.01, 0.1, 0.2, 0.5, 0.8, 1.0, 1.2, 1.5, 2, 5, or 10 cm. 3 The average pore volume can be about 10, 5, 2, 1.5, 1.2, 1.0, 0.8, 0.5, 0.2, 0.1, or 0.01 cm 3The average pore volume may be less than about 0.1 cm3 / g. The average pore volume may be within the range provided by any two of these upper and / or lower average pore volumes, for example, from about 0.1 cm3 to about 2 cm3 / g. 3 / g.

[0073] The layered metal coordination polymer can have a specific surface area, such as a Brunauer-Emmett-Teller (BET) surface area, of at least about 25, 50, 75, 85, 95, 100, 200, 500, or 1000 m 2 The specific surface area can be about 1000, 500, 200, 100, 95, 85, 75, 50, or 25 m 2 The specific surface area may be at least about 70, 75, 80, 85, 90, 95, or 100 m 2 The specific surface area may be within a range provided by any two of these upper and / or lower specific surface areas, for example, from about 75 to about 1000 m. 2 / g.

[0074] It should be understood that the average pore size, pore volume, and specific surface area can be modified depending on the metal atom or organic linker, reagents, solvents, and reaction conditions used in the preparation of the metal coordination polymer layer. The average pore size, pore volume, and specific surface area can be measured by any suitable technique, such as gas sorption or scattering techniques.

[0075] The layered metal coordination polymer comprises a metal atom coordinated to an organic linker to form a metal coordination polymer layer, the organic linker of the metal coordination polymer comprising a metal binding moiety and one or more moieties capable of forming electrostatic interactions with adjacent metal coordination polymer layers to form a layered metal coordination polymer.

[0076] The organic linker is typically selected from compounds that contain a metal binding moiety. In one embodiment, the organic linker is one or more carboxylic acids (-COOH) / carboxylates (-COO -In addition to the metal binding moiety, the organic linker may include one or more moieties capable of forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers.

[0077] In one embodiment, the organic linker can be an optionally interrupted alkyl, alkenyl, or alkynyl substituted with a metal binding moiety and one or more moieties capable of forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers. In another embodiment, the organic linker is an optionally interrupted alkyl substituted with a metal binding moiety and one or more moieties capable of forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers.

[0078] In one embodiment, the metal coordination polymer comprises a metal atom coordinated to an organic linker to form a metal coordination polymer layer, the metal atom comprises one or more metals selected from transition metals, post-transition metals, metalloids, or rare earth metals (including actinides and lanthanides); the organic linker is selected from metal binding moieties and optionally interrupted alkyl, alkenyl, or alkynyl substituted with one or more moieties capable of forming electrostatic interactions with adjacent metal coordination polymer layers to form a layered metal coordination polymer. The metal atom may be provided by any of the embodiments or examples thereof described herein.

[0079] In one embodiment, the organic linker may be selected from compounds containing one or more carboxylic acid (-COOH), hydroxyl (-OH), amine (-NH2), nitro (-NO2), thiol (-SH), or nitrile (-CN) groups, and one or more moieties capable of forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers. The organic linker may be provided by any of the embodiments or examples thereof described herein.

[0080] Metals used in metal coordination polymers The layered metal coordination polymer comprises a metal atom coordinated to an organic linker to form a metal coordination polymer layer. The metal atom can be any metal atom suitable for forming a coordination network, e.g., capable of forming a coordinate bond to a metal binding moiety.

[0081] In some embodiments, the metal atoms may include one or more metals typically selected from Groups 1 to 16 of the periodic table and the rare earth metals (ie, the actinides and lanthanides).

[0082] In some embodiments, the metal atoms may typically include one or more metals selected from alkali metals, alkaline earth metals, transition metals, post-transition metals, metalloids, or rare earth metals (including actinides and lanthanides). Non-limiting metal atoms are from the following groups: alkali metals (e.g., Li, Na, K, Rb, Cs, Fr), alkaline earth metals (e.g., Be, Mg, Ca, Sr, Ba, Ra), transition metals (e.g., Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg), transition metals (e.g. ... Post-transition metals (e.g., Al, Ga, In, Tl, Sn, Pb, Bi), metalloids (e.g., B, Si, Ge, As, Sb, Te, Po, P), and rare earth metals (e.g., La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ac, Th, Pa, U, Np, Pu, Am, Cm, Bk, Cf, Es, Fm, Md, No, Lr), and any combination thereof.

[0083] In some embodiments, the metal atom may include one or more of rare earth metals or transition metals. In embodiments, the metal atom is selected from one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Ta, W, Re, Os, Ir, Pt, Au, Hg, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Sc, Zn, Y, Zr, Cd, Lu, Hf, La, B, Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, or Sb. In some embodiments, the metal atom is selected from one or more of Ce, Cu, Mn, Fe, Ni, Zn, Ti, Zr. In some embodiments, the metal atom is selected from one or more of Ce, Ti, Zr, or Zn. In one embodiment, the metal atom is Ce. The metal atom can be a single metal atom or a cluster of metal atoms, for example a cluster of two or more different metal atoms as described herein.

[0084] In some embodiments, the metal atom is a metal ion. The metal ion can be monovalent or monovalent (i.e., a metal ion with only one possible charge). The metal ion can be multivalent (i.e., a metal ion can have two or more possible charges, e.g., two or more oxidation states). The metal ion can have two or more oxidation states.

[0085] The metal may be a multivalent ion, and the metal ion may be unstable / metastable when the multivalent ion is in a first oxidation state, and stable when the multivalent ion is in a second oxidation state. For example, a metal ion may have a first oxidation state when bound to an organic linker, and a second oxidation state when the organic linker is removed.

[0086] The metal ion can be an ion of any one of the metal atoms described herein. In some embodiments, the metal ion is selected from one or more of alkali metals, alkaline earth metals, transition metals, post-transition metals, metalloids, and rare earth metals (including actinides and lanthanides). Non-limiting metal ions are those selected from the following groups: alkali metals (e.g., Li, Na, K, Rb, Cs, Fr), alkaline earth metals (e.g., Be, Mg, Ca, Sr, Ba, Ra), transition metals (e.g., Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg ... ) post-transition metals (e.g., Al, Ga, In, Tl, Sn, Pb, Bi), metalloids (e.g., B, Si, Ge, As, Sb, Te, Po, P), and rare earth metals (e.g., La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ac, Th, Pa, U, Np, Pu, Am, Cm, Bk, Cf, Es, Fm, Md, No, Lr), and any combination thereof.

[0087] In some embodiments, the metal ion may include one or more of rare earth metals or transition metals. In some embodiments, the metal ion is selected from one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Ta, W, Re, Os, Ir, Pt, Au, Hg, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Sc, Zn, Y, Zr, Cd, Lu, Hf, La, B, Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, or Sb. In some embodiments, the metal ion is selected from one or more of Ce, Cu, Mn, Fe, Ni, Zn, Ti, Zr.

[0088] For example, the metal ion is Ce. 3+ , Ce 4+ , Ti 4+ , Zr 4+ , or Zn + In one embodiment, the metal ion is Ce.3+ and / or Ce 4+ The metal atom (including any ion thereof) may be provided as a salt, for example, a hydroxide, nitrate, chloride, acetate, oxalate, formate, peroxide, or sulfate.

[0089] In addition to being coordinated to one or more organic linkers according to any embodiment or example thereof as described herein, the metal atom may be coordinated to one or more additional organic ligands. These organic ligands may be oxygen-based ligands. For example, the organic ligands may be hydroxyl or water.

[0090] Organic linkers used in metal coordination polymers The layered metal coordination polymer comprises a metal atom coordinated to an organic linker to form a metal coordination polymer layer. The organic linker comprises a metal binding moiety. The organic linker may also comprise one or more moieties capable of forming electrostatic interactions with adjacent metal coordination polymer layers to form a layered metal coordination polymer. The organic linker stabilizes the metal atom by forming a coordinate bond.

[0091] One or more moieties capable of forming electrostatic interactions with adjacent metal coordination polymers can form pendant groups (i.e., termini) on the opposite side of the organic linker to the metal binding moiety. The metal binding moieties can form coordinate bonds (e.g., stronger covalent coordinate bonds) to one or more metals, which can result in stronger interlayer bonds within the metal coordination polymer layer. One or more moieties capable of forming electrostatic interactions with adjacent metal coordination polymer layers can result in weaker interlayer electrostatic interactions (e.g., weaker van der Waals interactions). Such weaker electrostatic interactions between layers can allow the layered metal coordination polymer to be exfoliated into individual metal coordination polymer layers, which can act as a platform for preparing thin nanostructures. Such weaker interactions can also allow the metal coordination polymer to be decomposed and reassembled into various morphologies.

[0092] By way of example only, the organic linker can be trichloroacetic acid, where the carboxylic acid group is the metal binding moiety and the trichloromethyl group is the moiety capable of forming an electrostatic interaction with an adjacent metal coordination polymer chain. Alternatively, in another example, the organic linker can be formic acid, where the carboxylic acid group is the metal binding moiety and the terminal hydrogen can form an electrostatic interaction with an adjacent metal coordination polymer layer, e.g., the terminal hydrogen of the organic linker on an adjacent metal coordination polymer chain can be interspersed between the layers. Rayville The layers may be held together by forming electrostatic interactions with ions, for example, terminal hydrogens may form electrostatic interactions with intralayer hydroxide ions or oxygen in water, or any other suitable ions capable of forming hydrogen bonds with the terminal hydrogens.

[0093] In one embodiment, the metal binding moiety is distinct from the one or more moieties capable of forming electrostatic interactions with an adjacent metal coordination polymer layer.

[0094] In some embodiments, the organic linker may be selected from one or more compounds having the structure of Formula 1: XR 1 (1) During the ceremony: X is a metal binding moiety for coordinating to a metal atom; and R 1 is H or an optionally interrupted alkyl, alkenyl, or alkynyl group substituted with one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers.

[0095] In some embodiments, R 1 is H or an optionally interrupted alkyl group substituted with one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers.

[0096] Metal joining part (X) The metal binding moiety (X) can be any suitable moiety for forming a coordinate bond to one or more metal atoms. In some embodiments, the coordinate bond of the metal binding moiety to the metal atom can be a direct bond, e.g., a covalent coordinate bond or a metal-ligand bond, or an indirect bond, e.g., a weaker electrostatic interaction (e.g., hydrogen bond, halogen bond), van der Waals interaction (e.g., dipole-dipole, dipole-induced dipole, London dispersion forces). In one embodiment, the metal binding moiety forms a covalent coordinate bond with one or more metal atoms. The metal binding moiety can be a head group on an organic linker, and the organic linker includes a tail. The tail can be H or an optionally interrupted and substituted alkyl, alkenyl, or alkynyl according to any embodiment or example thereof as described herein.

[0097] The metal binding moiety can be a monodentate, bidentate, or polydentate ligand. In some embodiments, the metal binding moiety is a monodentate or bidentate ligand. The monodentate or bidentate ligand forms a bridging coordination bond to two or more metal atoms to form a metal coordination polymer layer.

[0098] The metal binding moiety may have one site that can coordinate with one or more metal atoms. When using these organic linkers and the metal coordination polymer is in the form of multiple sheets, each sheet may be at least partially covered by the organic linker. In some embodiments, the organic linker has two or more sites (e.g., carboxylic acid / carboxylate moieties) that can coordinate with one or more metal atoms.

[0099] In some embodiments, the metal binding moiety comprises a metal donor atom. In some embodiments, the metal donor atom is a heteroatom. In some embodiments, the metal donor atom is selected from the group consisting of oxygen, nitrogen, sulfur, selenium, silicon, or tellurium. In some embodiments, the metal donor atom is sulfur, nitrogen, or oxygen. In one embodiment, the metal donor atom is oxygen. In some embodiments, the metal donor atom is a heteroatom in a heteroalkyl, heterocyclyl, or heteroaryl.

[0100] In some embodiments, the metal binding moiety comprises a carboxylic acid (-COOH), a hydroxyl (-OH), an amine (-NH2), a nitro (-NO2), a thiol (-SH), a nitrile (-CN), a substituted or unsubstituted heterocyclyl, or a substituted or unsubstituted heteroaryl. In some embodiments, the metal binding moiety is a carboxylic acid (-COOH). Various metal binding moieties, including hydrogen (e.g., carboxylic acid-COOH), can be used with hydrogen (e.g., carboxylate-COO). - It should be understood that the term may also be written without the suffix "-", "- or "-". For example, a carboxylic acid may form a monodentate coordinate bond to one or more metal atoms, where the hydrogen is retained. Alternatively, a carboxylic acid may form a monodentate or bidentate coordinate bond to one or more metal atoms via a carboxylate anion. References herein to carboxylate also refer to carboxylic acid, and the two may be used interchangeably, as would be understood by one of skill in the art.

[0101] In one embodiment, the metal binding moiety can be bidentate. Any suitable bidentate metal binding moiety can be used, for example, a bidentate metal binding moiety can be a carboxylic acid (-COOH) / carboxylate (-COO - ), amine (-NH2) (including, for example, a primary amine (-NH2), a secondary amine (-NH), a tertiary amine (-N(R)-)), thiol (-SH), hydroxyl (-OH), or nitrile (-CN).

[0102] In one embodiment, the metal binding moiety comprises a carboxylic acid group (which may be deprotonated under certain binding conditions to form a carboxylate group). The carboxylic acid / carboxylate metal binding moiety of each organic linker may independently form monodentate or bidentate coordinate bonds to one or more metal atoms. In some embodiments, the carboxylic acid / carboxylate metal binding moiety forms a bridging coordinate bond to at least two metal atoms to form the metal coordination polymer layer.

[0103] In some embodiments, the metal binding moiety may include a carboxylic acid, a carboxylate, an acetate, an oxalate, an acetylacetonate, or a chatecholate. In one embodiment, the metal binding moiety is a carboxylic acid and / or a carboxylate.

[0104] R 1 base The organic linker may include one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers to form a layered metal coordination polymer. The one or more moieties may be directly attached to the metal binding moiety. Alternatively, the one or more moieties may be selected from the group consisting of R, R ... 1 If present and not H, R 1 A group can be substituted with one or more moieties.

[0105] In some embodiments, the organic linker is an R 1 R 1 can be any type of unsaturated or saturated organic molecule. In some embodiments, R 1 is H. In some embodiments, R 1 R is an optionally interrupted alkyl, alkenyl, or alkynyl group substituted with one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers. 1 It should be understood that when R is hydrogen, the hydrogen may still form electrostatic interactions with adjacent metal coordination polymers to form layered metal coordination polymers. 1is an optionally interrupted alkyl group substituted with one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers to form a layered metal coordination polymer.

[0106] An optionally interrupted alkyl, alkenyl or alkynyl group is an optionally interrupted C 1-20 Alkyl, C 2-20 Alkenyl or C 2-20 alkynyl groups, each of which is substituted with one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers. The optionally interrupted alkyl, alkenyl or alkynyl groups can be selected from optionally interrupted C 1-10 Alkyl, C 2-10 Alkenyl or C 2-10 alkynyl groups, each of which is substituted with one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers. The optionally interrupted alkyl, alkenyl or alkynyl groups can be selected from optionally interrupted C 1-6 Alkyl, C 2-6 Alkenyl or C 2-6 alkynyl groups, each substituted with one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers. The one or more moieties for forming electrostatic interactions with adjacent substituted metal coordination polymer layers to form layered metal coordination polymers can be provided according to any embodiment or example thereof, as described herein.

[0107] In embodiments, R 1 is an optionally interrupted C substituted with one or more moieties that form electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers; 1-20 It is an alkyl.

[0108] In embodiments, R 1 is an optionally interrupted C substituted with one or more moieties that form electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers;1-10 It is an alkyl.

[0109] In embodiments, R 1 is an optionally interrupted C substituted with one or more moieties that form electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers; 1-6 It is an alkyl.

[0110] In embodiments, R 1 is H or an optionally interrupted methyl, ethyl, propyl, butyl, pentyl, or hexyl substituted with one or more moieties to form electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers.

[0111] In embodiments, R 1 is H or methyl substituted with one or more moieties to form electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers.

[0112] In some embodiments, each R of the organic linker as described above 1 The alkyl group may be optionally interrupted by one or more heteroatoms, such as one or more O, N, S, Se, Te, Si, and / or one or more alkenyl, alkynyl, aryl, heteroaryl, heteroaryl, and / or cycloalkyl, wherein each of the alkenyl, alkynyl, aryl, heteroaryl, or cycloalkyl groups may be optionally substituted.

[0113] In some embodiments, R 1 The one or more moieties substituted above may be, for example, by oppositely charged ions in any of the adjacent metal coordination polymer chains and / or by one or more interspersed ions between the metal coordination polymer layers. Rayville It may be any suitable ion capable of forming an electrostatic interaction with an adjacent metal coordination polymer chain via a proton.

[0114] In some embodiments, R 1One or more of the moieties substituted on the metal coordination polymer layer may form hydrogen bonds, halogen bonds, van der Waals interactions (e.g., dipole-dipole, dipole induced dipole, London dispersion forces) with adjacent metal coordination polymer layers. 1 One or more of the moieties substituted on the metal coordination polymer layer form van der Waals interactions with adjacent metal coordination polymer layers. Such interactions may include one or more metal coordination polymer moieties interspersed between the metal coordination polymer layers. Rayville It can be formed via a proton.

[0115] In some embodiments, R 1 is terminated with one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers. For example, R 1 The terminal hydrogen ions of the alkyl of R can be replaced with one or more moieties to form electrostatic interactions with adjacent metal coordination polymer layers. 1 The terminal hydrogen ion of R may be replaced with a more electronegative moiety, e.g., a halogen-based moiety, e.g., a halogen, a haloalkyl, a haloalkenyl, a haloalkynyl, a haloalkoxy, a haloalkylsulfonyl, or one or more other suitable moieties described herein. 1 may be replaced with a less electronegative moiety, such as one or more halides selected from the group consisting of Li, Na, K, Rb, or Cs.

[0116] In some embodiments, R 1 One or more of the moieties substituted above are interspersed between the metal coordination polymer layers. Rayville It forms electrostatic interactions with ions to form layered metal coordination polymers.

[0117] In some embodiments, R is an anion for forming an electrostatic interaction with an adjacent metal coordination polymer. 1The one or more moieties substituted on the metal coordination polymer may be selected from the group consisting of halogen, haloalkyl, haloalkenyl, haloalkynyl, haloalkoxy, haloalkylsulfonyl, nitrile, hydroxyl, amine, carboxyl, carboxylate, amide, nitro, thiol, sulfonamide, or sulfonyl. In some embodiments, R is an alkyl group that is capable of forming an electrostatic interaction with an adjacent metal coordination polymer. 1 The one or more moieties substituted on the above may be selected from the group consisting of halogen, haloalkyl, haloalkenyl, haloalkynyl, haloalkoxy, or haloalkylsulfonyl.

[0118] In some embodiments, R is an anion for forming an electrostatic interaction with an adjacent metal coordination polymer. 1 One or more of the moieties substituted above may be halogen, C 1-20 Haloalkyl, C 2-20 Haloalkenyl, C 2-20 Haloalkynyl, C 1-20 Haloalkoxy, or C 1-20 In some embodiments, R for forming electrostatic interactions with adjacent metal coordination polymers may be selected from the group consisting of haloalkylsulfonyl. 1 One or more of the moieties substituted above may be halogen, C 1-10 Haloalkyl, C 2-10 Haloalkenyl, C 2-10 Haloalkynyl, C 1-10 Haloalkoxy, or C 1-10 In some embodiments, R for forming electrostatic interactions with adjacent metal coordination polymers may be selected from the group consisting of haloalkylsulfonyl. 1 One or more of the moieties substituted above may be halogen, C 1-6 Haloalkyl, C 2-6 Haloalkenyl, C 2-6 Haloalkynyl, C 1-6 Haloalkoxy, or C 1-6 It may be selected from the group consisting of haloalkylsulfonyl.

[0119] In some embodiments, R is an anion for forming an electrostatic interaction with an adjacent metal coordination polymer.1 The one or more moieties substituted on the above may be selected from the group consisting of halogens. In some embodiments, R is an alkyl group for forming electrostatic interactions with adjacent metal coordination polymers. 1 One or more of the moieties substituted above may be selected from -F, -Cl, -Br, or -I.

[0120] In some embodiments, R is an anion for forming an electrostatic interaction with an adjacent metal coordination polymer. 1 One or more of the moieties substituted above may be -F, -Cl, -Br, -I, -CF3, -CI3, -CCl3, -CBr3, -CHF2, -CHCl2, -CHI2, -CHBr2, -OCH2F, -OCH2Cl, -OCH2I, -OCH2Br, -OCHF2, -OCHCl2, -OCHI2, -OCHBr2, -OCF3, -OCl3, -OCI3, -OCBr3, -CN, -OH, -NH2, -COOH, -CONH2, -NO2, -SH, -SO3H, -SO4H, -SO2NH2, -NHNH2, -ONH2, -NHC= (O)NHNH2, -NHC=(O)NH2, -NHSO2H, -NHC=(O)H, -NHC(O)-OH, -NHOH, substituted or unsubstituted alkyl (e.g., C1-C8, C1-C6, or C1-C4), substituted or unsubstituted heteroalkyl (e.g., 2-8 membered, 2-6 membered, or 2-4 membered), substituted or unsubstituted cycloalkyl (e.g., C3-C8, C3-C6, or C5-C6), substituted or unsubstituted heterocyclyl (e.g., 3-8 membered, 3-6 membered, or 5-6 membered), substituted or unsubstituted aryl (e.g., C6-C 10 , C 10 , or phenyl), or substituted or unsubstituted heteroaryl (eg, 5-10 membered, 5-9 membered, or 5-6 membered).

[0121] In some embodiments, R is an anion for forming an electrostatic interaction with an adjacent metal coordination polymer. 1The one or more moieties substituted above may be selected from the group consisting of -F, -Cl, -Br, -I, -CF3, -CI3, -CCl3, -CBr3, -CHF2, -CHCl2, -CHI2, -CHBr2, -OCH2F, -OCH2Cl, -OCH2I, -OCH2Br, -OCHF2, -OCHCl2, -OCHI2, -OCHBr2, -OCF3, -OCl3, -OCI3, and -OCBr3.

[0122] In some embodiments, R 1 is selected from the group consisting of H, alkyl, alkenyl, alkynyl, alkoxy, haloalkyl, haloalkenyl, haloalkynyl, haloalkoxy, haloalkylsulfonyl, alkylamine, alkylcarboxylic acid, alkylamide, alkylthiol, alkylsulfonamide, or alkylsulfonyl.

[0123] In some embodiments, R 1 is selected from the group consisting of H, alkyl, haloalkyl, haloalkoxy, alkylamine, alkylcarboxylic acid, alkylthiol, alkylsulfonamide, or alkylsulfonyl. 1 is selected from the group consisting of H, alkyl, halogen, haloalkyl, and alkylcarboxylic acid.

[0124] In some embodiments, R 1 , H, C 1-20 Alkyl, C 1-20 Haloalkyl and C 1-20 In some embodiments, R 1 H, halogen, C 1-10 Alkyl, C 1-10 Haloalkyl and C 1-10 The carboxylic acid is selected from the group consisting of:

[0125] In some embodiments, R 1-CF3, -CI3, -CCl3, -CBr3, -CHF2, -CHCl2, -CHI2, -CHBr2, -OCH2F, -OCH2Cl, -OCH2I, -OCH2Br, -OCHF2, -OCHCl2, -OCHI2, -OCHBr2, - OCF3, -OCl3, -OCI3, -OCBr3, -CN, -OH, -NH2, -COOH, -CONH2, -NO2, -SH, -SO3H, -SO4H, -SO2NH2, -NHNH2, -ONH2, -NHC=(O)NHNH2, -NHC=( O)NH2, -NHSO2H, -NHC=(O)H, -NHC(O)-OH, -NHOH, substituted or unsubstituted alkyl (e.g., C1-C8, C1-C6, or C1-C4), substituted or unsubstituted heteroalkyl (e.g., 2-8 membered, 2-6 membered, or 2-4 membered), substituted or unsubstituted cycloalkyl (e.g., C3-C8, C3-C6, or C5-C6), substituted or unsubstituted heterocycloalkyl (e.g., 3-8 membered, 3-6 membered, or 5-6 membered), substituted or unsubstituted aryl (e.g., C6-C 10 , C 10 , or phenyl), or substituted or unsubstituted heteroaryl (eg, 5-10 membered, 5-9 membered, or 5-6 membered).

[0126] In some embodiments, the metal atom is Ce. 3+ , Ce 4+ , Ti 4+ , Zr + or Zn + X is -COOH, -SH, -NH2, -OH, and R 1 is selected from -CF3, -CI3, -CCl3, -CBr3, -CHF2, -CHCl2, -CHI2, -CHBr2, -OCH2F, -OCH2Cl, -OCH2I, -OCH2Br, -OCHF2, -OCHCl2, -OCHI2, -OCHBr2, -OCF3, -OCl3, -OCI3, or -OCBr3.

[0127] In some embodiments, the organic linker is organic based. In some embodiments, the organic linker comprises an alkyl-, alkene-, alkyne-, and / or aryl-based carboxylic acid. For example, the organic linker can be a halide-substituted alkyl acid, such as trichloroacetic acid. In some embodiments, the organic linker comprises formic acid. In some embodiments, the organic linker can act as a Lewis acid and the metal atom acts as a Lewis base, or vice versa.

[0128] In some embodiments, the organic linker is a carboxylic acid. In some embodiments, the organic linker is formic acid, trifluoroacetic acid, trichloroacetic acid, tribromoacetic acid, or triiodoacetic acid. In one embodiment, the organic linker is formic acid or trichloroacetic acid. In one embodiment, the organic linker is trichloroacetic acid.

[0129] To obtain a layered metal coordination polymer (each layer containing stronger intralayer covalent coordinate bonds between the organic linker and one or more metal atoms throughout the layer, and weaker electrostatic interactions between the layers), in some embodiments, the organic linker does not form coordinate bonds to metal atoms of adjacent metal coordination polymer layers, allowing each layer of the layered metal coordination polymer to be held together by weak van der Waals interactions between each layer.

[0130] Layered metal coordination polymers The layered metal coordination polymer may be an unstable layered metal coordination polymer. An unstable layered metal coordination polymer is one that contains metal centers or substructures that are inherently unstable but can exist indefinitely due to the presence of organic linkers (e.g., [Ce(OH)2] 2+), which effectively "caps" and stabilizes the unstable metal center or substructure of the coordination polymer. The unstable metal center or substructure may also be referred to as a "reactive metal-based species." Upon removal of the stabilizing or "capping" organic linker, the metal has a tendency to form a more stable metal-based species, such as a nanostructure. For example, the reactive metal-based species may be a metal atom (e.g., a metal ion) with an unsaturated coordination number that has a tendency to create covalent bonds to fill coordination sites when the organic linker is removed. The conversion from an unstable / metastable state to a stable state may be achieved through an intermediate. For example, in some embodiments, the reactive metal-based species may have a tendency to form an unstable / metastable intermediate that is rapidly converted to a more stable metal-based species upon removal of the organic linker. However, the unstable / metastable intermediate is not formed in all embodiments. The terms "unstable" and "metastable" may be used interchangeably throughout this disclosure.

[0131] Prior to this disclosure, these properties meant that they could not be used as nanostructure materials for any length of time, and therefore unstable metal coordination polymers were previously avoided as potential precursors for forming nanostructures. However, the benefit of this instability is that the unstable metal coordination polymers can be used as precursor materials to create other nanostructures with specific geometries.

[0132] The labile metal coordination polymers are also capable of retaining the structure or architecture of the metal coordination polymer during the formation of nanostructures, something that has not previously been contemplated with the use of labile metal coordination polymers. The use of labile metal coordination polymers as precursors can also result in the formation of polycrystalline nanostructures, something that has not previously been contemplated with labile metal coordination polymers.

[0133] A reactive metal-based species comprising a metal coordinated to an organic linker forms part of a metal coordination polymer. The reactive metal-based species is stabilized by the organic linker, allowing the reactive metal-based species to exist in a "reactive" (or metastable) state. Removal of the organic linker allows the unstable metal-based species to adapt to a more stable state (i.e., a more stable metal-based species). In some embodiments, the organic linker stabilizes the metal atom by forming a coordinate bond of the metal atom to the organic linker. In other words, the ligand serves to "cap" the reactive metal-based species, preventing the reactive metal-based species from forming a more stable metal-based species. Removal of such a capping linker results in the conversion of the unstable metal-based species to a more stable metallic nanostructure.

[0134] In some embodiments, the layered metal coordination polymer comprises a plurality of metal coordination polymers interspersed between the metal coordination polymer layers. Rayville Contains ions. Rayville The term ionic refers to ions that can be interspersed throughout the interlayer space between the layers of the metal coordination polymer. Rayville The ions can form electrostatic interactions between one or more moieties of the organic linkers of each metal coordination polymer layer to form a layered metal coordination polymer. Rayville The ions can have a positive or negative charge. Rayville The ions are the acidic protons (H + ). The protons can be introduced in situ during the synthesis of the metal coordination polymer. Rayville The ions can form electrostatic interactions with one or more moieties that are terminal organic linkers to form layered metal coordination polymers. For example, if the organic linker is acidic (e.g., trichloroacetic acid), Rayville The ions may be protons of an acid and may intercalate between the sheets. The intercalated protons may help hold the layered material together. For example, the protons may act as weak electrostatic crosslinkers.

[0135] RayvilleThe ions can be of opposite charge to one or more terminal moieties of the organic linker. For example, if the organic linker terminates with one or more negatively charged ions, including, for example, halogen moieties (e.g., F, Cl, Br, I), Rayville Ions are positive, e.g., protons (H + Alternatively, if the organic linker is terminated with hydrogen or one or more positive ions (e.g., Li, Na, K, Rb, and / or Cs), Rayville The ions may be negatively charged (e.g., OH - ). Rayville The ions may originate from the carboxylic acid metal binding moiety of the organic linker, and / or from the metal source used in preparing the metal coordination polymer, and / or from the solvent system (e.g., HO) used in preparing the metal coordination polymer.

[0136] In some embodiments, Rayville The electrostatic interactions between the ions and one or more terminal moieties of the organic linker can be substantially orthogonal (e.g., perpendicular) to the coordination bonds within the metal coordination polymer. Such orientation of the interlayer and intralayer bonds provides the ability to exfoliate the layered metal coordination polymer into one or more individual metal coordination polymer layers under relatively simple conditions.

[0137] Interlayer RayvilleDue to the presence of ions (e.g., protons), the metal coordination polymer has a surface charge. In some embodiments, the surface charge is positive. The surface charge can be positive or negative. The surface charge can be positive. The layered metal coordination polymer can have a zeta potential (representing a surface charge). The layered metal coordination polymer can have a zeta potential greater than zero (0) mV. In some embodiments, the layered metal coordination polymer has a zeta potential of at least 1, 2, 5, 10, 15, 20, 30, 40, 50, 60, 80, or 100 mV. In some embodiments, the layered metal coordination polymer has a zeta potential of less than 100, 80, 60, 50, 40, 30, 20, 15, 10, 5, 2, or 1 mV. Combinations of any two or more of these upper and / or lower zeta potential values ​​are also possible, e.g., about 5 mV to about 100 mV, 5 mV to about 80 mV, or about 10 mV to about 60 mV, e.g., about +30 mV. Figure 69 shows the zeta potential of a layered metal coordination polymer according to at least some embodiments or examples described herein.

[0138] In some embodiments, the metal coordination polymer can be a metal coordination polymer layer that is not electrostatically linked to another layer (i.e., not crosslinked to form a bulk layered polymer). For example, a layered metal coordination polymer can be exfoliated to give one or more individual metal coordination polymer layers.

[0139] In some embodiments, the metal coordination polymer is a non-bridged metal coordination polymer comprising a metal atom coordinated to an organic linker to form a metal coordination polymer layer, the organic linker being described herein. The metal coordination polymer layer can be a planar or linear layer. In some embodiments, two or more metal coordination polymer layers can be electrostatically interacted (i.e., bridged) to form a layered metal coordination polymer, the metal coordination polymer layers being held together by electrostatic interactions between the organic linkers on each metal coordination polymer layer, as described herein.

[0140] It is understood that in addition to organic linkers, e.g., negatively charged ions, negatively charged complexes, and / or dipole-bearing molecules (e.g., water and / or hydroxide ions), metal coordination polymers can incorporate other organic ligands that coordinate to one or more metal atoms and can, for example, come from the metal salt and / or solvent used in the preparation of the metal coordination polymer.

[0141] In some embodiments, each metal atom of the metal coordination polymer may be independently coordinated to at least 5, 6, 7, or 8 atoms from the metal binding moiety and / or one or more additional organic ligands, hi some embodiments, each metal atom of the metal coordination polymer may be independently coordinated to at least 7 or 8 atoms of the metal binding moiety of one or more organic linkers and / or one or more additional organic ligands.

[0142] In one embodiment, the metal coordination polymer is a cerium metal coordination polymer having the formula Ce(TCA)2(OH)2·2H2O. The cerium metal coordination polymer may be characterized by an X-ray powder diffraction (XRD) pattern that includes one or more major peaks located at about 7.2, 8.1, 10.9, 20.6, 22.0, 23.1, and / or 23.2 degrees (2θ). Any one or more of these peaks can be used to characterize the cerium metal coordination polymer. The cerium metal coordination polymer may be characterized by the XRD pattern provided in FIG. 8.

[0143] The layered metal coordination polymer comprises layers having a certain thickness along the layer (referred to as the axial thickness along the c-axis of the metal coordination polymer layer). In some embodiments, each metal coordination polymer layer can independently have an axial thickness along the c-axis of less than 100, 70, 50, 20, 15, 10, 8, 6, 4, 2, or 1 nm, e.g., less than 20, 15, 12, 10, 8, 5, 2, or 1 nm. Combining any two of these upper and / or lower thickness limits can provide a range selection, e.g., from about 1 nm to about 12 nm. In one embodiment, each metal coordination polymer layer can independently have an axial thickness of about 1.1, 2.2, 5.5, or 11 nm, the thickness being proportional to the thickness of one unit cell of the metal coordination polymer. In some embodiments, each metal coordination polymer layer can be about 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 unit cells thick. The thickness may be measured using scanning electron microscopy or atomic force microscopy (AFM).

[0144] Method for preparing metal coordination polymers One main goal of the methods for preparing metal coordination polymers described herein is to establish synthesis conditions that can produce layered metal coordination polymers that are held together by weak electrostatic interactions. Depending on the reaction conditions, unstable metal coordination polymers can be prepared, which can be used to prepare a variety of nanostructures.

[0145] The metal coordination polymers described herein can be prepared by combining (i.e., contacting) a metal atom source with an organic linker to form a layered metal coordination polymer comprising two or more metal coordination polymer layers held together by electrostatic interactions. The terms "combining" or "contacting" can include reacting, interacting, or physically contacting two species, which can be an organic linker and a metal atom as described herein, and in some cases, one or more other species, including a gas, e.g., oxygen.

[0146] The metal atom source can include any metal atom (e.g., metal ion) as described herein for metal coordination polymers, such as those described under the heading "Metals Used in Metal Coordination Polymers." The metal atom source can typically include one or more metals selected from alkali metals, alkaline earth metals, transition metals, post-transition metals, metalloids, or rare earth metals (including actinides and lanthanides). Non-limiting metal atoms are from the following groups: alkali metals (e.g., Li, Na, K, Rb, Cs, Fr), alkaline earth metals (e.g., Be, Mg, Ca, Sr, Ba, Ra), transition metals (e.g., Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg), transition metals (e.g. ... The metal atom source may include ions of any one or more of the metals described herein. The metal ions may be monovalent or monovalent (i.e., a metal ion having only one possible charge). The metal ions may be multivalent (i.e., a metal ion may have two or more possible charges, e.g., two or more oxidation states). The metal ions may have two or more oxidation states. The metal atom source may include multivalent ions.

[0147] In some embodiments, the metal ion source may include one or more of rare earth metals or transition metals. In some embodiments, the metal ion is selected from one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Ta, W, Re, Os, Ir, Pt, Au, Hg, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Sc, Zn, Y, Zr, Cd, Lu, Hf, La, B, Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, or Sb. In some embodiments, the metal ion is selected from one or more of Ce, Cu, Mn, Fe, Ni, Zn, Ti, Zr. By way of example, the metal ion source may be Ce, 3+ , Ce 4+ , Ti 4+ , Zr 4+ , or Zn + In one embodiment, the metal ion may include one or more of Ce. 3+ and / or Ce 4+ The metal atom source (including any ions thereof) may be provided as a salt of any one or more of the metals described herein, such as a hydroxide, nitrate, chloride, acetate, oxalate, formate, peroxide, or sulfate.

[0148] The organic linker can be any organic linker as described herein for the metal coordination polymer. The organic linker includes a metal binding moiety. The organic linker can also include one or more moieties capable of forming electrostatic interactions with adjacent metal coordination polymer layers to form a layered metal coordination polymer. In some embodiments, the organic linker can be selected from one or more compounds having the structure of Formula 1: XR 1 (1) During the ceremony: X is a metal binding moiety for coordinating to a metal atom; and R 1is H or an optionally interrupted alkyl, alkenyl, or alkynyl group substituted with one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers to form said layered metal coordination polymer. In some embodiments, R 1 is H or an optionally interrupted alkyl group substituted with one or more moieties for forming electrostatic interactions with adjacent metal coordination polymer layers to form layered metal coordination polymers. 1 is a linking moiety and R 1 The organic linker may be selected from, for example, those described under the heading "Organic Linkers Used in Metal Coordination Polymers." In some embodiments, the organic linker is a carboxylic acid. In some embodiments, the organic linker is formic acid, trifluoroacetic acid, trichloroacetic acid, tribromoacetic acid, or triiodoacetic acid. In one embodiment, the organic linker is formic acid or trichloroacetic acid. In one embodiment, the organic linker is trichloroacetic acid.

[0149] Combining the metal atom source and the organic linker may include mixing the metal atom source and the organic linker. The metal atom source and the organic linker may be mixed using solvent-free conditions, such as sol-gel techniques. Alternatively, the metal atom source and the organic linker may be mixed using an aqueous solution or solvent. The mixture may then be heated. Suitable techniques for forming layered metal coordination polymers include hydrothermal, solvothermal, and electrodeposition processes. A polar solvent (e.g., water or an organic solvent) may be used to form the mixture of the metal atom source and the organic linker. For example, if the organic linker is an organic acid, a metal salt (e.g., metal atom source) and an organic acid may be mixed.

[0150] In some embodiments, the process can include mixing an aqueous solution comprising a metal atom source and an organic linker to form a layered metal coordination polymer comprising two or more metal coordination polymer layers held together by electrostatic interactions, hi some embodiments, the step of forming the layered metal coordination polymer comprises heating the aqueous solution comprising the metal atom source and the organic linker.

[0151] The reaction conditions may depend on the type of metal coordination polymer to be formed. In some embodiments, a mixture of the metal atom source and the organic linker may be subjected to a hydrothermal or solvothermal treatment.

[0152] In one embodiment, the step of forming a layered metal coordination polymer includes, for example, electrodeposition to prepare a cerium-based metal coordination polymer.

[0153] The electrodeposition may be modified anodic chronoamperometric electrodeposition (MACE). The electrodeposition process may include three electrodes, including a fluorine-doped tin oxide on a glass working electrode, a platinum wire counter electrode, and an Ag / AgCl reference electrode. Other electrodes may also be used. An example of a suitable electrodeposition setup is provided in Figures 49 and 50, however, this should not be considered limiting.

[0154] MACE can be carried out in an oxygen generating region of an aqueous solution containing a metal atom source and an organic linker. The oxygen generating region varies depending on the metal atom and organic linker system, however, it can be easily determined by those skilled in the art using available Poole-Bay diagrams. An example of a Poole-Bay diagram for cerium and trichloroacetate is provided in FIG. 7, however, this should not be considered limiting. By carrying out electrodeposition in an oxygen generating region of an aqueous solution containing a metal atom and an organic linker, oxygen molecules are generated at the working electrode, resulting in the oxidation of metal species (e.g., Ce(III) to Ce(IV)) that can form unstable metal coordination polymers.

[0155] The concentrations of the metal atom source and the organic linker in the aqueous solution are each limited by the maximum solubility of the precursor water-soluble salt used as the metal atom source. In some embodiments, the concentrations of the metal atom source and the organic linker in the aqueous solution are each independently at least about 0.001, 0.01, 0.02, 0.05, 0.08, 0.1, 0.2, 0.4, 0.5, 0.8, or 1 M. In some embodiments, the concentrations of the metal atom source and the organic linker in the aqueous solution are each independently less than about 1, 0.8, 0.5, 0.4, 0.2, 0.1, 0.08, 0.05, 0.02, 0.01, or 0.001 M. Combinations of any two or more of these upper and / or lower concentration limits are also possible, for example, from about 0.001 M to about 1 M or from about 0.01 M to about 0.1 M.

[0156] The initial pH of the aqueous solution or mixture may be adjusted. In some embodiments, the initial pH of the aqueous solution during electrodeposition may be an acidic pH, for example, less than about pH 7. The pH may be adjusted by adding an appropriate amount of acid or base depending on the acidity of the aqueous solution containing the metal atom source and the organic linker. In some embodiments, the initial pH of the aqueous solution during electrodeposition may be less than about 7, 6, 5, 4, 3, or 2. Combinations of these pH values ​​are also possible, for example, the initial pH of the aqueous solution during electrodeposition may be about pH 2 to about pH 7, about pH 3 to about pH 7, about pH 5 to about pH 6, for example, about pH 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.6, 5.8, 6.0, 6.2, 6.4, 6.8, or 7.0.

[0157] The electrodeposition is carried out with a constant applied voltage effective to maintain the oxygen evolution region of the aqueous solution containing the metal atom source and the organic linker. The voltage used for electrodeposition may be determined by the surface area of ​​the working electrode. The voltage may be proportional to the dimensions of the working electrode. The voltage used for electrodeposition may be determined by the aqueous or solvent system used for electrodeposition. In one embodiment, the voltage (i.e., potential) used for electrodeposition may be within the oxygen evolution region of the aqueous solution containing the metal ion and the organic linker, for example, as determined by a Poole Bay diagram.

[0158] In some embodiments, electrodeposition is performed using a constant applied voltage vs. Ag / AgCl of at least about 0.001, 0.01, 0.05, 0.1, 0.2, 0.5, 0.8, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 V. In some embodiments, electrodeposition is performed using a constant applied voltage vs. Ag / AgCl of less than 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.8, 0.5, 0.2, 0.1, 0.05, 0.01, or 0.001 V. Combinations of any two or more of these upper and / or lower voltage limits are also possible, e.g., about 1.0 V to 10.0 V, about 1.0 V to 5.0 V, or about 1.0 V to 2.0 V. Other applied voltages are also possible, depending on the metal atom and organic linker, and can be selected based on the appropriate Poole Bay diagram for a given metal and organic linker system, as will be appreciated by one of skill in the art. By applying a voltage effective to maintain the oxygen generation region of the aqueous solution, oxygen can be generated at the working electrode and oxidize the metal atoms, e.g., Ce(III) to Ce(IV). At the same time, protons can also be rapidly generated, lowering the local pH. The local pH of the aqueous solution during electrodeposition can be lowered to a more acidic pH compared to the initial pH of the aqueous solution, e.g., the local pH can be lowered to about pH 1 to about pH 3, e.g., about pH 3, 2.8, 2.6, 2.4, 2.2, or less than 2.0. The local pH of the aqueous solution during electrodeposition can be lowered below the initial pH of the aqueous solution.

[0159] The generation of protons during electrodeposition is due to one or more Rayville A source of ions (e.g., protons) can be provided that is interspersed between the metal coordination polymer layers to provide a source of ions (e.g., protons) to each R of the organic linker of each metal coordination polymer layer. 1 Electrostatic interactions are formed between one or more moieties of the optionally interrupted alkyl groups to form a layered metal coordination polymer.

[0160] Electrodeposition can be carried out at any suitable temperature, for example, at least about 0, 5, 10, 15, 20, 25, 30, 40, 50, 70, 90, or 100° C. Electrodeposition can be carried out at a temperature less than about 100, 90, 70, 50, 40, 30, 25, 20, 15, 10, or 5° C. Combinations of any two or more of these upper and / or lower temperature limits are also possible, for example, from about 0° C. to about 100° C., from about 10° C. to 60° C., or from 25° C. to 50° C. In some embodiments, electrodeposition can be carried out at room temperature (e.g., 25° C.), however, elevated temperatures can accelerate the diffusion rate and reaction rate of the formation of the metal coordination polymer.

[0161] The electrodeposition may be carried out for a suitable time to form the metal coordination polymer, for example, for a period of at least about 1, 2, 5, 10, 15, 20, 30, 60, or 90 minutes. The electrodeposition may be carried out for a period of less than about 90, 60, 30, 20, 15, 10, 5, 2, or 1 minute. A combination of any two or more of these upper and / or lower reaction times is possible, for example, about 1 minute to 90 minutes, about 10 minutes to 90 minutes, or about 30 minutes to about 90 minutes.

[0162] In some embodiments, the metal may be at a low oxidation state and low field strength within a viable working pH range of an aqueous solution containing the metal atom and an organic linker to form a metal coordination polymer, as described herein. The working pH range may be determined by a Pooley diagram. The oxidation state of the metal may be increased upon oxidation in an acidic pH environment, as described herein. In some embodiments, the metal may be at a low oxidation state and low field strength within a viable working pH range of an aqueous solution containing the metal atom and an organic linker to form a metal coordination polymer, as described herein. x n+ ) can form an acidic pH at high oxidation states.

[0163] The architecture of the layered material can be changed by disassembling and reassembling the layered metal coordination polymer using different solvent systems. For example, in polar solvents such as water, the layered metal coordination polymer may preferentially exfoliate rather than changing the architecture. When using low polarity solvents such as ethanol or other organic solvents, the layered metal coordination polymer may be differentiated and then reassembled. Methods for reassembling the layered metal coordination polymer may depend on the concentration of the layered metal coordination polymer, the type of solvent, the use of a solvent system such as a gradient solvent system, the evaporation rate, heating, cooling, pH, and the introduction of groups that cause layering such as salts. The change in the architecture of the layered metal coordination polymer may allow the formation of different nanostructures from a single precursor layered material.

[0164] In some embodiments, the layered metal coordination polymer is decomposed in an organic solvent and reconstituted from the organic solvent by evaporation. In some embodiments, the organic solvent is an alcohol, such as methanol, ethanol, propanol, butanol, pentanol, etc., preferably ethanol. In some embodiments, the organic solvent is a polar aprotic solvent, such as dichloromethane, NMP, THF, acetate, acetone, DMF, acetonitrile, or DMSO, or an amine, such as triethylamine. In some embodiments, the organic solvent is an amine, such as triethylamine. In some embodiments, the organic solvent is acetone.

[0165] The concentration of the metal coordination polymer decomposed in the organic solvent is limited by the maximum solubility of the metal coordination polymer in the organic solvent. In some embodiments, the concentration of the metal coordination polymer decomposed in the organic solvent is at least about 1, 2, 4, 5, 10, 20, 50, 70, 90, 100, 110, or 120 M. In some embodiments, the concentration of the metal coordination polymer decomposed in the organic solvent is less than about 120, 110, 100, 90, 70, 50, 20, 10, 5, 4, 2, or 1 M. The combination of any two of these upper and / or lower concentration limits can provide a range selection, for example, from about 1 M to about 200 M, or from about 4 M to about 120 M.

[0166] The evaporation of the organic solvent is carried out at a temperature and vapor pressure limited by the maximum solubility of the organic solvent in air. In some embodiments, the evaporation of the organic solvent is carried out at a temperature of at least about -20, -15, -10, -5, 0, 5, 10, 15, 20, 30, 40, or 50°C. In some embodiments, the evaporation of the organic solvent is carried out at a temperature less than about 50, 40, 30, 20, 15, 10, 5, 0, -5, -10, -15, or -20°C, or greater than about -20, -15, -10, -5, 0, 5, 10, 15, 20, 30, 40, or 50°C. Combinations of any two or more of these upper and / or lower evaporation temperatures are possible, for example, from about -20°C to about 40°C, or from about -10°C to about 25°C. In some embodiments, the evaporation of the organic solvent is carried out at a vapor pressure of at least about 0.1, 0.2, 0.5, 0.7, 1, 2, 5, 7, 10, 15, or 20 kPa. In some embodiments, the evaporation of the organic solvent is carried out at a vapor pressure of less than about 20, 15, 10, 7, 5, 2, 1, 0.7, 0.5, 0.2, or 0.1 kPa. Combinations of any two or more of these upper and / or lower vapor pressure limits are possible, for example, from about 0.1 kPa to about 20 kPa, from about 0.1 kPa to about 10 kPa, from 0.5 kPa to about 10 kPa, or from about 0.7 kPa to about 10 kPa. It is understood that any single or range of vapor pressures and evaporation temperatures can be combined. In some embodiments, the evaporation time can be at least about 1 minute, 15 minutes, 30 minutes, 1, 2, 3, 4, 6, 8, 12, 18, 24, 48, or 72 hours. Combinations of these evaporation times are also possible, for example, from about 6 hours to 72 hours.

[0167] The layered metal coordination polymer may be exfoliated to provide one or more metal coordination polymer layers. In some embodiments, the step of exfoliating the layered material includes exfoliating the metal coordination polymer interspersed within each layer. Rayville This involves removing the ions. Rayville The removal of ions can destroy the electrostatic interactions between metal coordination polymer layers (e.g., dispersions of metal coordination polymer layers) to obtain one or more metal coordination polymer layers. For example, increasing the pH of a dispersion or solution of layered metal coordination polymers can destroy the dispersed ions. RayvilleIons (e.g., protons) may be removed. Generally, sparse Rayville The removal of ions occurs at the edge of the layered metal coordination polymer, weakening the van der Waals forces holding the layers together and allowing the intrusion of water or solvent molecules between adjacent sheets. The propagating front of ion removal and water or solvent intrusion then progresses from the edge toward the interior of the layered metal coordination polymer. Thus, in embodiments, water or solvent intrusion causes delamination. In some embodiments, the layered metal coordination polymer is exfoliated by agitation in water. However, exfoliation is not limited to water or solvent intrusion and may be facilitated by, for example, adjusting temperature, chemical environment, etc.

[0168] In some embodiments, the exfoliation of the layered metal coordination polymer comprises the formation of interspersed metal coordination polymer layers between each metal coordination polymer layer. Rayville By removing the ions, each R of the organic linker of each metal coordination polymer layer 1 disrupting the electrostatic interactions between one or more moieties of the optionally interrupted alkyl groups to obtain one or more metal coordination polymer layers.

[0169] The exfoliation can be carried out by dispersing the metal coordination polymer in a suitable solvent (e.g., water or an organic solvent) and further applying heating and / or stirring, e.g., stirring or (ultra)sonication. The exfoliation can be assisted via chemical means. The exfoliation can be assisted by heating and / or ultrasonication. The exfoliation can be carried out using any solvent, e.g., water, alcohol, e.g., methanol, ethanol, propanol, butanol, pentanol, etc.; preferably, ethanol, polar aprotic solvent, e.g., dichloromethane, NMP, THF, acetate, acetone, DMF, acetonitrile, or DMSO, or amine, e.g., triethylamine.

[0170] In some embodiments, exfoliating the layered metal coordination polymer includes dispersing the layered metal coordination polymer in water or an organic solvent, stirring, and exfoliating the layered metal coordination polymer to obtain one or more metal coordination polymer layers. The layered metal coordination polymer may be stirred at a temperature of about 5° C. to about 50° C., for example, at about room temperature. The layered metal coordination polymer may be stirred (e.g., by sonication) for a period of time effective to exfoliate the layered metal coordination polymer to obtain one or more metal coordination polymer layers. Suitable stirring times for exfoliating the layered metal coordination polymer to obtain one or more metal coordination polymer layers include, for example, about 1 minute to about 72 hours, about 1 minute to about 60 minutes, or about 1 minute to about 20 minutes.

[0171] In some embodiments, decomposition of the layered metal coordination polymer in an organic solvent also exfoliates the layered metal coordination polymer. In some embodiments, the combined exfoliation and decomposition can be facilitated by similar polarity indices of the metal coordination polymer and the solvent, e.g., organic or inorganic. In embodiments, the exfoliation can be facilitated by different polarity indices (in the range of 1-10) of the metal coordination polymer and the solvent. Similar polarity indices can be, for example, in the range of ±2; different polarity indices can be, for example, in the range of ±3-9.

[0172] In some embodiments, the step of forming the layered metal coordination polymer includes hydrothermal treatment of an aqueous solution comprising metal atoms and an organic linker as described herein. The initial pH of the aqueous solution during the hydrothermal treatment can be less than about 7. The hydrothermal treatment can be carried out at a temperature range of about 25° C. to about 200° C., or about 25° C. to about 100° C., for example, less than about 100° C. Suitable techniques for hydrothermal treatment are known to those of skill in the art.

[0173] Process for preparing nanostructures The metal coordination polymers disclosed herein are relatively unstable precursors, providing a platform for controllable disassembly to form a multitude of useful and / or previously unattainable nanoarchitectures, ranging from nanosheets that can be made ultrathin to a variety of two- and three-dimensional nanostructures that can feature varying degrees of defects. Unexpectedly and advantageously, these diverse nanostructures can be obtained from a single metal coordination polymer precursor in a controlled manner. For example, exfoliation of a metal coordination polymer can ultimately produce nanosheets containing metal oxides (MOs), which can be made as thin as one unit cell and can be suitably diversified with, for example, useful transition metals. On the other hand, disassembly / reassembly of a metal coordination polymer under certain conditions can provide a variety of two- and three-dimensional nanostructures based on the morphology of the reassembled metal coordination polymer. The assembly / reassembly process can be controlled by varying parameters such as solvent type, solute concentration, temperature, and time. Both initial steps of exfoliation and / or disassembly / reconstruction are followed by the removal of the metal coordination polymer-coordinating organic linkers, transforming the initial metal coordination polymer structures into corresponding nanostructures, e.g., porous metal oxide nanosheets.

[0174] Thus, the present disclosure provides, in one aspect, a method of forming a nanostructure comprising providing a layered metal coordination polymer comprising two or more layers, each layer comprising a metal atom each coordinated to one or more organic linkers to form a metal coordination polymer, and removing at least a portion of the coordinating organic linkers to form the nanostructure.

[0175] In some embodiments, the method includes providing a layered metal coordination polymer having a number of metal atoms stabilized by coordination to one or more organic linkers. In some embodiments, the layered metal coordination polymer includes a number of reactive metal-based centers (i.e., reactive metal-based species) stabilized by coordination to one or more organic linkers. In some embodiments, the method can include removing at least a portion of the coordinating organic linkers to reveal an unstable metal-based species, which is then converted to a more stable metal-based species to form the nanostructure. In some embodiments, the unstable metal-based species is converted to one or more more stable intermediates, which are then converted to the more stable metal-based species to form the resulting nanostructure.

[0176] According to the method, at least a portion of the coordinating organic linker is removed to form a nanostructure. In some embodiments, the step of removing at least a portion of the coordinating organic linker to form a nanostructure comprises aging the layered metal coordination polymer.

[0177] As used herein, the term "aging" refers to the physical and / or chemical changes of a material with respect to time, for example, aging a metal coordination polymer to form a nanostructure.

[0178] In some embodiments, aging the layered metal coordination polymer includes heating the metal coordination polymer. For example, the layered metal coordination polymer can be heated to a temperature sufficient to decompose the organic linker and form the nanostructure. The sufficient temperature can be, for example, 100°C to 1000°C, preferably 100°C to 850°C, more preferably 100°C to 700°C. In some embodiments, the temperature can be at least about 50, 75, 100, 150, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, 900, or 1000°C. Combinations of these temperature values ​​are also possible, for example, about 300°C to about 400°C, for example, about 350°C.

[0179] In some embodiments, at least a portion of the coordinating organic linker is removed by pyrolysis of the layered metal coordination polymer. In some embodiments, the pyrolysis is low temperature pyrolysis. In other embodiments, the pyrolysis is carried out at a temperature of at least 100, 150, 200, 250, or 300° C.

[0180] Other possible processes for forming nanostructures include X-ray irradiation, cold laser irradiation, gamma ray irradiation, neutron irradiation, and other suitable high energy beam irradiation capable of forming nanostructures from metal coordination polymers.

[0181] In some embodiments, removing at least a portion of the coordinating organic linker to form the nanostructure comprises aging a solution containing the layered metal coordination polymer. The solution containing the metal coordination polymer is sonicated or agitated during the aging step. Alternatively, the solution can be static for the aging step.

[0182] Aging of the solution can be at a basic pH (e.g., a low acidic pH, e.g., using a solution concentration of up to 6.0 M NaOH). In some embodiments, aging of the solution containing the layered metal coordination polymer is at a basic pH greater than pH 7, e.g., at least about pH 7, 8, 9, 10, 11, 12, 13, or 14, preferably pH 8. Combinations of these pH ranges are also possible, e.g., from about pH 7 to pH 14, or from about pH 7 to about pH 10, e.g., a pH of about 8.

[0183] The aging of the solution at a basic pH may further include a stirring step. The stirring step may be performed simultaneously with the aging of the solution at a basic pH. The aging of the solution at a basic pH may include increasing the pH of the solution containing the metal coordination polymer by adding a suitable base, such as sodium hydroxide. Alternatively, the solution may have its pH adjusted before adding the metal coordination polymer. In one embodiment, the step of removing one or more organic linkers includes increasing the pH of the solution. The solution may be stirred while increasing the pH.

[0184] In some embodiments, the solution containing the layered metal coordination polymer is aged for a period of time effective to form a nanostructure, such as at least about 1 minute, 15 minutes, 30 minutes, 1 hour, 2 hours, 6 hours, 12 hours, 1 day, or 2 days. In some embodiments, the solution is aged for a period of time of about 1 minute to about 2 days, preferably about 10 minutes to about 2 hours, such as about 30 minutes.

[0185] In some embodiments, the solution is aged at a temperature effective to form nanostructures, e.g., at least about 1, 5, 10, 15, 20, 30, 40, 50, 70, or 100°C, and combinations thereof, e.g., from about 10°C to about 50°C, preferably at room temperature, e.g., about 25°C.

[0186] Aging may include a heating or burning step. The heating or burning step may include heating or burning a solution containing the metal coordination polymer. The heating or burning of the solution may be at a temperature of at least about 10, 20, 25, 30, 40, 50, 80, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, or 600°C. The heating or burning of the solution may be at a temperature of less than about 600, 550, 500, 450, 400, 350, 300, 250, 200, 150, 100, 80, 50, 40, 30, 25, 20, or 10°C. Combinations of these heating or burning temperatures, for example, about 10°C to about 50°C, about 50°C to about 600°C, about 100°C to about 600°C, or about 200°C to about 600°C, are also possible.

[0187] The morphology of the nanostructures can change in response to a heating or burning rate of at least about 0.01, 0.05, 0.1, 0.2, 0.3, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, or 5.0 degrees Celsius per minute. -1 The heating or burning rate may be about 5.0, 4.0, 3.5, 3.0, 2.5, 2.0, 1.5, 1.0, 0.5, 0.3, 0.2, 0.1, 0.05, or 0.01 degrees Celsius per minute. -1Combinations of these heating or burning rates, for example, from about 0.1 to about 5°C min -1 Or about 0.2 to 3 degrees Celsius -1 The heating or burning can be carried out for a suitable period of time, for example, at least about 1 minute, 15 minutes, 30 minutes, 1, 2, 3, 4, 8, 12, 18, 24, 48, or 72 hours.

[0188] The aging solution may be heated to a temperature up to the boiling point of the solution, in one embodiment, the aging solution may be heated to a temperature of 100°C to 300°C, for example, about 200°C.

[0189] In some embodiments, removal of at least a portion of the coordinating organic linker destabilizes the metal atom, which in turn forms a stable nanostructure. In some embodiments, upon removal of at least a portion of the coordinating organic linker, the metal coordination polymer transforms (e.g., spontaneously or by application of heat, stirring, etc.) to form a stable nanostructure. In some embodiments, the morphology of the nanostructure is the same as the morphology of the metal coordination polymer.

[0190] As a result of removing at least a portion of the coordinating organic linker, the resulting nanostructure may be a porous nanostructure. Removing at least a portion of the coordinating organic linker to form reactive metal-based species (e.g., uncoordinated metal atom centers / substructures) into more stable metal-based species forms a porous nanostructure. Thus, in some embodiments, the nanostructure is a porous oxide nanostructure, and removing at least a portion of the coordinating organic ligand forms a porous nanostructure. In some embodiments, the nanostructure exhibits a fine and homogeneous pore network. The terms "nanostructure" and "porous nanostructure" may be used interchangeably throughout this disclosure, unless the context makes clear otherwise. For example, references to pore size are made with reference to porous nanostructures.

[0191] The reactive metal-based species forms part of a metal coordination polymer. The reactive metal-based species is stabilized by a coordinating organic linker, so that the reactive metal-based species can exist in a "reactive" state while coordinated to the organic linker. In some embodiments, upon removal of the organic linker, an unstable metal-based species can be formed after removal of the organic linker and can adopt a more stable state (i.e., a more stable metal-based species). For example, the reactive metal-based species can be a multivalent metal, and in the reactive or unstable state, the multivalent ion is in a first oxidation state, and in the stable state, the multivalent ion is in a second oxidation state. For example, the metal of the reactive metal-based species can have a first oxidation state when bound to a ligand, and a second oxidation state when the ligand is removed. In some embodiments, the metal of the reactive metal-based species is a multivalent metal. The reactive metal-based species can include metals having two or more oxidation states. In some embodiments, the metal atom is selected from any one or more metal atoms (including ions) as described herein, including, for example, Ce, Cu, Mn, Fe, Ni, Zn, Ti, or Zr. In some embodiments, the metal atom is Ce, Ti, Zr. In some embodiments, the metal ion is Ce(IV), Ti(IV), Zr(IV).

[0192] In some embodiments, the method includes providing a layered metal coordination polymer having multiple metal ions. In some embodiments, the metal ions are monovalent or multivalent, preferably multivalent.

[0193] In some embodiments, the metal may be at a low oxidation state and low field strength within a viable working pH range for forming metal coordination polymers. In some embodiments, the metal atom has an oxidation state that can increase when oxidized at an acidic pH. The working pH range can be determined by a Pooley diagram. The oxidation state of the metal of the reactive metal center can increase when oxidized at an acidic pH. In some embodiments, the unsaturated metal hydroxide (M(OH) x n+ ) can form an acidic pH at high oxidation states.

[0194] For example, in some embodiments, when the ligand is removed, the reactive metal-based species may form an unsaturated metal hydroxide as the unstable metal-based species, which then converts to a more stable metal oxide. Upon removal of at least a portion of the organic linker, the reactive metal-based species may form an unstable metal oxide-based species. In aqueous systems, the unstable metal oxide-based species may include hydroxide and peroxide salts. In non-aqueous systems, other metal oxide-based species may be formed. As an example, when Ce is coordinated to an organic linker but used as the metal of the reactive metal species, removal of the organic linker may result in the formation of Ce(OH) as the unstable metal-based species. x (4-x)+ As a more stable metal-based species, which can then form porous nanostructures, CeO 2-x Convert to.

[0195] In some embodiments, the conversion of the metal coordination polymer to a metal oxide is achieved by reacting the metal oxide with OH in aqueous solution. - This is due to the displacement of weakly bound organic linkers by / H2O. For example, in Ce-based coordination polymers in aqueous solution, Ce 4+ The relatively high field strength of enhances its ability to form Ce(OH)4, which then dissolves into CeO upon drying. 2-x The conversion of the reactive metal-based species to the more stable metal-based species can occur at room temperature (e.g., < about 35° C.). In some embodiments, a heating step is used to convert the reactive metal-based species to the more stable metal-based species.

[0196] In some embodiments, the layered metal coordination polymer is exfoliated to obtain a dispersion of metal coordination polymer layers prior to removing at least a portion of the coordinating organic linkers forming the nanostructures, hi some embodiments, the layers may be formed into sheets of metal coordination polymer, and the exfoliation results in the formation of a dispersion of discrete sheets.

[0197] In some embodiments, removing at least a portion of the organic linker from a dispersion of discrete sheets can result in the formation of a dispersion of porous nanosheets. Alternatively, removing at least a portion of the organic linker can form species capable of forming pores.

[0198] In embodiments, the steps of exfoliating the layered material and removing at least a portion of the coordinated organic linkers are performed simultaneously. If the layered material is not exfoliated before the removal of the ligands, and regardless of the mechanism used to form the porous nanostructure, it should be noted that the sheets may still be converted into porous nanosheets, but the pores of each nanosheet may not be aligned with each other, giving the appearance of a structure that is "porous" at the nano level, although the "porosity" is not visible. The layered material does not have to be planar. In some embodiments, the layered material may be formed into a tube or rod. For example, the layers may wrap around a central axis of the layered material.

[0199] Exfoliation can be performed, for example, using agitation, as described herein. In some embodiments, the metal coordination polymer is dispersed in a suitable solvent (e.g., water) and agitated for a period of time effective to exfoliate the metal coordination polymer to obtain a dispersion of the metal coordination polymer layer before removing at least a portion of the coordinating ligands to form the nanostructure. Suitable solvents can include water, polar protic solvents, or polar aprotic solvents. Polar aprotic solvents can include dichloromethane, NMP, THF, acetate, acetone, DMF, acetonitrile, or DMSO. Polar protic solvents can include water, alcohols (e.g., ethanol and methanol), and carboxylic acids.

[0200] In some embodiments, the metal coordination polymer is stirred for a period of time, preferably at least about 1 minute, 2 minutes, 5 minutes, 8 minutes, 10 minutes, 15 minutes, 30 minutes, 1 hour, 2 hours, 6 hours, 12 hours, 1 day, or 2 days, to exfoliate the metal coordination polymer and obtain a dispersion of the metal coordination polymer layer and / or nanostructures. Combinations of these stirring times are also possible. For example, the metal coordination polymer is stirred for a period of time, preferably about 1 minute to about 2 days, preferably about 10 minutes to about 2 hours, for example, about 30 minutes, to exfoliate the metal coordination polymer and obtain a dispersion of the metal coordination polymer layer. The exfoliation can be assisted via chemical means. The exfoliation can also include heating and / or ultrasonication. The exfoliation step can be at a basic pH, for example, a pH as described herein, with respect to removing one or more organic linkers. The exfoliation step and the aging step can be performed simultaneously.

[0201] In an embodiment, Rayville The ions are interspersed between the metal coordination polymer layers as described herein. For example, when the organic linker contains a terminal acidic group, Rayville The ions may be protons of an acid and may be intercalated between the sheets. The intercalated protons may help hold the layered material together. For example, the protons may act as a weak crosslinking agent. In some embodiments, the step of exfoliating the layered material includes removing the intercalated protons. For example, an alkaline pH may be used to remove the intercalated protons. Typically, the removal of the intercalated protons occurs at the edge of the layered material, which weakens the van der Waals forces that hold the layers together, allowing the intrusion of water molecules between adjacent sheets. The propagating front of proton removal and water intrusion then proceeds from the edge toward the interior of the layered structure. Thus, in embodiments, water intrusion causes exfoliation. However, exfoliation is not limited to water intrusion and may be facilitated by, for example, adjusting temperature, chemical environment, etc.

[0202] The layered structure may have many different architectures. In some embodiments, the structure (architecture) of the layered structure may change prior to removal of at least a portion of the ligand. During the change in the layered structure, the reactive metal-based species may remain unchanged. Upon removal of the ligand to convert the reactive metal-based species to a more stable metal-based species, the architecture of the layered material may be retained. In some embodiments, the structure of the sheet does not change during the conversion from the reactive metal-based species to a more stable metal-based species. It should be understood that while at the atomic level the structure may change, at the macro level the architecture of the nanostructure (e.g., nanosheet) does not change, e.g., remains a two-dimensional sheet. The change in the architecture of the layered material (i.e., precursor material) may enable the formation of different nanostructures from a single precursor layered material.

[0203] In some embodiments, the architecture of the layered material may be altered by dissolving the layered material in different solvent systems, as described herein. For example, in a strong polar solvent, such as water, the layered material may preferentially exfoliate rather than change architecture. When a low polar solvent, such as ethanol, is used, the layers may be differentiated and then reconstituted. Thus, in some embodiments, the metal coordination polymer is dissociated in an organic solvent prior to removing at least a portion of the coordination ligands to form the nanostructure, and reconstituted from the organic solvent by evaporation, changing the morphology of the metal coordination polymer before or during removal of one or more organic linkers to form the nanostructure. In this way, tailored and unique nanostructure morphologies can be formed.

[0204] Methods of restructuring layers can depend on the concentration of the layered materials, the type of solvent, the use of solvent systems such as gradient solvent systems, evaporation rate, heating, cooling, pH, and the introduction of groups that cause layering such as salts.

[0205] In some embodiments, the concentration of the metal coordination polymer that is decomposed in the organic solvent is limited by the maximum solubility of the metal coordination polymer in the organic solvent, and is preferably about 4M to about 120M.

[0206] In some embodiments, evaporation of the organic solvent is carried out at a temperature and vapor pressure limited by the maximum solubility of the organic solvent in air, preferably from about -20°C to about 40°C, more preferably from about -10°C to about 25°C, and at a vapor pressure of from about 0.1 kPa to about 10 kPa, preferably from about 0.5 kPa to about 8 kPa.

[0207] In some embodiments, the organic solvent is an alcohol, such as methanol, ethanol, propanol, butanol, pentanol, etc., preferably ethanol. In some embodiments, the organic solvent is a polar aprotic solvent, which may include dichloromethane, NMP, THF, acetate, acetone, DMF, acetonitrile, or DMSO. In some embodiments, the organic solvent is an amine, such as triethylamine. In some embodiments, the organic solvent is acetone.

[0208] The step of removing at least a portion of the coordinating organic linker may include (i) increasing the affinity of the metal to form a more stable metal-based species, e.g., converting to an oxidized form, and / or (ii) decreasing the affinity of the organic linker for the reactive metal site. These may be accomplished by changing the environment of the metal coordination polymer, e.g., adjusting the solvent, salt concentration, temperature, pH, and / or introduction of an agent that disrupts the bond of the linker to the reactive metal-based species. In embodiments, decreasing the affinity of the linker for the reactive metal-based species includes increasing the pH of the mixture containing the nanostructure. For example, if the linker contains an acidic group, such as a carboxyl group, increasing the pH of the solution in which the metal coordination polymer is present changes the affinity of the carboxyl group by deprotonating the carboxyl group and promoting the formation of a reactive metal intermediate.

[0209] In some embodiments, reducing the affinity of the linker for the reactive metal-based species comprises heating the metal coordination polymer. For example, a combination of processes such as changes in pH and temperature may be used to reduce the affinity of the bond between the reactive metal-based species and the coordinating organic linker.

[0210] In some embodiments, the weak electrostatic bond between the cation (e.g., metal ion) and the organic linker (e.g., an organic linker comprising an organic acid) in the labile coordination polymer results in Lability have demonstrated the discovery of previously unobserved nanostructures, e.g., CeO 2-x This provides a valuable platform to simply and controllably destroy / reconstruct coordination polymer crystallites to form nanostructures.

[0211] The nanostructures used in preparing the metal coordination polymers can be metal coordination polymers as described herein or can be metal coordination polymers prepared by the processes described herein.

[0212] Nanostructures There are a variety of nanostructures that can be produced by the present methods. In some embodiments, the present disclosure provides nanostructures. In some embodiments, the nanostructures exhibit fine and homogeneous pore networks. In some embodiments, the nanostructures are bulk nanostructures.

[0213] The morphology of the nanostructures can be sheet-like, hollow, porous, cubic, rod-like, polyhedral, spherical or hemispherical, round or semicircular, angular, and irregular morphologies, tubular, dumbbell-like, rhombohedral, honeycomb, needle-like, bundle-like, wafer-like, fiber, flower-like, and the like, including two- and / or three-dimensional scaffold structures. The morphology of the nanostructures can correspond to the morphology of the layered nanostructures used in the preparation of the metal coordination polymer.

[0214] In some embodiments, the nanostructures are polycrystalline. In some embodiments, the nanostructures are solid and / or hollow. The hollow nanostructures can be faceted. The nanostructures can be porous nanostructures. Removing at least a portion of the organic linkers can allow the reactive metal centers to form porous nanostructures.

[0215] In some embodiments, the nanostructures are metal oxides. The metal oxides can be oxides of any of the metals described herein with respect to the metal coordination polymers.

[0216] In some embodiments, the nanostructure is a nanosheet or nanolayer. For example, a metal coordination polymer is peeled off to form one or more metal coordination polymer layers, and then aged to remove one or more organic linkers therefrom to form a nanosheet. The nanosheet can be solid or hollow. In one embodiment, the nanosheet is a metal oxide.

[0217] In one embodiment, the nanosheets are porous nanosheets. In one embodiment, the nanosheets are porous metal oxide nanosheets, such as porous CeO 2-x nanosheet, where x can vary between 0-0.9, 0-0.8, 0-0.7, 0-0.6, and 0-0.5. The porous metal oxide nanosheet can be a porous FCO nanosheet, a porous NCO nanosheet, or a porous ZCO nanosheet.

[0218] In one embodiment, the nanostructure is a bulk metal oxide nanostructure. The bulk metal oxide nanostructure can be porous. The bulk metal oxide nanostructure can be one-dimensional, two-dimensional or three-dimensional. The bulk nanostructure can be solid or hollow.

[0219] In one embodiment, the nanostructure is a porous metal oxide nanosheet. The nanosheet may have an average pore size of at least about 1, 2, 3, 4, 5, 8, 10, 12, 14, 18, or 20 nm. The nanosheet may have an average pore size of less than about 20, 18, 14, 12, 8, 5, 4, 3, 2, or 1 nm. Combinations of any two or more of these upper and / or lower diameter limits are also possible, e.g., from about 2 nm to about 20 nm, e.g., from 2 nm to about 14 nm. The pore size can be measured using transmission electron microscopy.

[0220] In some embodiments, the nanostructures are metal oxide nanosheets having a concentration of point defects (e.g., cation vacancies and / or anion vacancies). The concentration of point defects may depend on the type of metal oxide nanostructure and / or the morphology of the metal coordination polymer used to prepare the metal oxide nanostructure. In some embodiments, the metal oxide nanosheets have a defect concentration of at least about 1, 2, 5, 10, 12, 14, 18, 20, 25, 30, 35, or 40 atomic %. In some embodiments, the metal oxide nanosheets have a defect concentration of less than about 40, 35, 30, 25, 20, 18, 14, 12, 10, 5, 2, or 1 atomic %. Combinations of any two or more of these upper and / or lower defect concentrations are also possible, such as from about 1 to about 30 atomic %, for example, from 18 to about 30 atomic %.

[0221] The nanostructures can have a BET specific surface area of ​​at least about 25, 50, 75, 85, 95, 100, 200, 500, or 1000 m 2 The specific surface area can be about 1000, 500, 200, 100, 95, 85, 75, 50 or 25 m 2 The specific surface area may be at least about 70, 75, 80, 85, 90, 95, 100 m / g. 2 / g. A combination of any two or more of these upper and / or lower limits of specific surface area, for example, about 75 to about 1000 m 2 / g is also possible.

[0222] The nanostructures can be polycrystalline. Polycrystalline nanostructures can include one or more crystallites. The average crystallite size can be less than 100, 80, 60, 50, 40, 30, 20, 15, 10, or 5 nm. The average crystallite size can be from about 1 nm to about 20 nm.

[0223] The nanostructure can be a nanolayer, e.g., a nanosheet. The nanosheet can be a porous nanosheet. The nanosheet can have a certain thickness (e.g., cross-sectional distance) along the layer or sheet (referred to as the axial thickness along the c-axis of the sheet or layer). In some embodiments, the nanosheet can have an axial thickness along the c-axis of less than 100, 70, 50, 20, 15, 10, 8, 6, 4, 2, or 1 nm, e.g., less than 20, 15, 12, 10, 8, 5, 2, or 1 nm. Combinations of any two or more of these upper and / or lower thickness limits are also possible, e.g., from about 1 nm to about 100 nm, from about 1 nm to about 50 nm, or from about 1 nm to about 20 nm.

[0224] The nanosheet may be a porous nanosheet, and the average diameter of the pores may be at least about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 50, 80, or 100 nm. The nanosheet may be a porous nanosheet, and the average diameter of the pores may be less than about 100, 80, 50, 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, 2, or 1 nm. A combination of any two or more of these upper and / or lower average pore diameters, for example, about 1 nm to about 50 nm, or about 2 nm to about 14 nm, is also possible.

[0225] In one embodiment, a porous ceria nanosheet is provided. The porous ceria nanosheet may have an axial thickness of less than 100, 70, 50, 20, 15, 10, 8, 6, 4, 2, or 1 nm, for example, less than 20, 15, 12, 10, 8, 5, 2, or 1 nm. A combination of any two or more of these upper and / or lower thickness limits is also possible, for example, about 1 nm to about 100 nm, about 1 nm to about 50 nm, or about 1 nm to about 20 nm.

[0226] In one embodiment, the nanosheets have an axial thickness of about 1.1, 2.2, 5.5, or 11 nm, the thickness being proportional to the thickness of one unit cell of the metal coordination polymer. In some embodiments, the nanosheets can be about 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 unit cells thick. The thickness can be measured using scanning electron microscopy or atomic force microscopy (AFM).

[0227] In some embodiments, the nanostructure may consist of multiple individual layers, where each layer is stacked to form an individual nanolayer. In some embodiments, the individual nanolayers are stacked to form a bulk nanostructure. In some embodiments, the nanostructure is a metal oxide nanosheet, where two or more metal oxide nanosheets are stacked to form a bulk metal oxide nanostructure. In some embodiments, the nanostructure is a porous metal oxide nanosheet, where multiple nanosheets are stacked to form a stacked nanostructure.

[0228] In some embodiments, the morphology of the nanostructure is the same as the morphology of the nanostructure used to prepare the metal coordination polymer, for example, if the metal coordination polymer is a hollow nanotube, after removal of one or more organic linkers described herein, the resulting nanostructure can also be a hollow nanotube.

[0229] Heterojunction Nanostructures The metal coordination polymers described herein can also be used to prepare heterojunction nanostructures, where one or more adsorbed species can be adsorbed onto the surface of the nanostructure. The adsorbed species can be a second metal species. Adsorption of the second metal species onto the surface can form a metal-functionalized nanostructure. The nanostructure can act as a template.

[0230] The adsorbed species is adsorbed onto the surface by dispersing it in a solution or dispersion containing the adsorbed species. The adsorbed species can be adsorbed in the pores and on the surface. If the nanostructure is a porous nanostructure, the surface charge of the porous nanostructure can provide an attractive force to adsorb the adsorbed species. For example, the porous nanostructure can have a negative zeta potential, and positive metal ions can be attracted to the surface of the porous nanostructure and adsorbed uniformly on the surface.

[0231] In some embodiments, one or more adsorbed species are adsorbed onto the surface of the nanostructure, forming one or more heterojunctions on the surface of the nanostructure.

[0232] In some embodiments, one or more species are adsorbed onto the surface of the nanostructure by removing at least a portion of the organic linker in the presence of the adsorbed species.

[0233] The adsorbed species can be aged in the presence of the metal coordination polymer. For example, the adsorbed species can be added to an aging solution containing the metal coordination polymer or aged in a solution containing the metal coordination polymer. In some embodiments, the adsorbed species is mixed with an aging solution containing the metal coordination polymer when the solution is at a pH of about pH 3 to about pH 7.

[0234] Preferably, the adsorbed species comprises one or more metal atoms that are different from the metal atoms of the metal coordination polymer. Alternatively, the adsorbed species can be the same metal but of a different valency as the metal atoms of the metal coordination polymer.

[0235] The adsorbed species may be in ionic form. More preferably, the adsorbed species is a metal, nonmetal, semimetal, or metalloid, or combination thereof, such as their elemental, ionic form, oxide, or non-oxide, preferably, for example, S, C, N, C, As, Te, O, Se, P, Mn, Fe, Ni, Cu, Zn, Mo, and Ru, such as mixtures thereof. The adsorbed species may also be, for example, a metal-based species, which is oxidized after adsorption onto the surface of the nanostructure. Alternatively, when adsorbed, the metal species may be an element M. 0The nanostructures can be doped with one or more of the adsorbed species described herein.

[0236] In embodiments, once the adsorbed species is adsorbed onto the surface of the nanostructure, the nanostructure is subjected to oxidizing conditions, including combustion, chemical oxidation with an oxidizing agent, etc. The adsorbed species may serve to change the catalytic, electrode potential, pore size (if the nanostructure is a porous nanostructure), and / or selectivity properties of the nanostructure, for example, to allow passage of selected species through the pores of the porous nanosheet.

[0237] In some embodiments, a solution containing a metal coordination polymer is aged in the presence of one or more adsorbed species to form one or more heterojunctions on the surface of the nanostructure. For example, one or more adsorbed species can be dissolved or suspended in the solution containing the metal coordination polymer (which is aged to form one or more heterojunctions on the surface of the nanostructure). Alternatively, the adsorbed species is part of the organic solvent used to prepare the solution containing the metal coordination polymer. For example, the metal coordination polymer can be decomposed in an organosulfosolvent (e.g., DMSO), which is then reconstituted and aged to form a mixed metal oxide / sulfide nanostructure.

[0238] In some embodiments, the nanostructures can be metal oxides, metal sulfides, metal arsenides, metal selenides, metal tellurides, metal phosphides, metal nitrides, or metal carbides, or mixtures thereof. In one embodiment, the metal coordination polymers can be used as precursors to form hybrid nanostructures containing sulfur and / or carbon. In one embodiment, the nanostructures are mixed ceria sulfide carbides.

[0239] Also disclosed are nanostructures including porous nanosheets having metal oxides. The nanosheets can have a unit cell thickness of less than 30. The pores can result from removing ligands bound to reactive metal-based species that form the metal oxide.

[0240] The thickness of the nanosheet can be less than 5 unit cells, e.g., 2 unit cells. The thickness can be 1 unit cell thick. The thickness of the nanosheet in nanometers (nm) can depend on the size of the unit cell and the number of unit cells. In an embodiment, the nanostructure has a defect concentration of approximately 18-30 atomic %.

[0241] The nanosheets can be formed from metal coordination polymers as described herein. The nanosheets can have the same morphology and / or structure as the metal coordination polymers. The nanostructures can include multiple porous nanosheets. For example, multiple porous nanosheets can be stacked to form a stacked structure. When the nanostructures have multiple porous nanosheets, the pores of adjacent sheets can be aligned with each other. However, in some embodiments, the pores of adjacent sheets do not have to be aligned with each other. When the pores of adjacent sheets are not aligned with each other, the nanostructures may not appear to have pores at a macro level.

[0242] The metal oxide can be an oxide of a polyvalent metal. The metal of the metal oxide can be a metal that is polyvalent. The metal of the metal oxide can have a high coordination number. The metal oxide can include oxides of Ce, Cu, Mn, Fe, Ni, Ti, Zr, and Zn. The surface of the nanosheet can be decorated with a second metal-based species (i.e., heterojunction, plasma resonance). The second metal-based species can include a mixture of metal-based species, for example, a mixture having two or more metal-based species. The second metal-based species can be in ionic, metallic, or / and oxide form. The electrode potential properties of the nanosheet can be tailored through the inclusion of a second metal.

[0243] The nanostructures may be mixed cerium oxides. The mixed cerium oxides may include one or more oxides of Cu, Mn, Fe, Ni, Ti, Zr, and Zn. The mixed cerium oxides may be FCO, NCO, or ZCO.

[0244] The porous nanosheets may have a surface charge of less than zero (0) mv. In some embodiments, the porous nanosheets may have a zeta potential of less than about 0, -5, -10, -15, -20, -25, -30, -40, -50, -80, or -100 mv. Combinations of these zeta potentials are also possible, for example, from about -10 mV to about -40 mv.

[0245] In some embodiments, once an adsorbed species (eg, a second metal-based species) is adsorbed onto the surface of the nanostructure, the adsorbed species undergoes a structural transformation with O, N, S, Se, or Te.

[0246] catalyst composition The nanostructures described herein have one or more catalytic properties. Thus, in one aspect, a catalyst composition comprising the nanostructures is provided according to any embodiment or example thereof as described herein. The nanostructures can be used as catalysts. In one embodiment, a method for catalyzing a reaction using the nanostructures or catalyst composition thereof is provided according to any embodiment or example thereof as described herein. The reaction can be an oxidation reaction. The nanostructures or catalyst composition thereof can catalyze the oxidation of one or more reactants. The reaction can include the oxidation of one or more polluting or contaminating materials present in an aqueous or gaseous environment.

[0247] In some embodiments, a method for purifying a gas stream or atmosphere (e.g., air) by contacting the gas stream or atmosphere with a nanostructure or catalytic composition thereof according to any embodiment or example described herein is provided, wherein one or more contaminant or contaminant materials present in the gas stream or atmosphere are catalyzed (e.g., oxidized) upon contact with the nanostructure or catalytic composition thereof. The gas stream or atmosphere may contain carbon monoxide. The nanostructure or catalytic composition thereof may oxidize the carbon monoxide to carbon dioxide. In one embodiment, a method for purifying a gas stream or atmosphere containing carbon monoxide is provided, comprising contacting the gas stream or atmosphere with a nanostructure or catalytic composition thereof according to any embodiment or example described herein to oxidize the carbon monoxide to carbon dioxide. The gas stream or atmosphere may be an exhaust stream (e.g., industrial flue gas or vehicle exhaust).

[0248] In some embodiments, the nanostructures or compositions comprising same may achieve complete CO oxidation (e.g., to CO2) (i.e., 100% CO oxidation) at temperatures less than about 200, 190, 180, 170, 160, 150, 140, 130, 120, 110, 100, 90, or 80° C., e.g., from about 80° C. to about 200° C. In some embodiments, the nanostructures or compositions comprising same may achieve 50% CO→CO2 oxidation at temperatures less than about 200, 190, 180, 170, 160, 150, 140, 130, 120, 110, 100, 90, or 80° C., e.g., from about 80° C. to about 200° C.

[0249] In some embodiments, the nanostructure or composition thereof has a molecular weight of at least about 1, 2, 5, 7, 10, 12, 15, or 20 mol g -1 s -1 and / or a CO→CO conversion rate at 400° C. of at least about 1, 2, 3, 4, or 5×10 -3 Mol Mol -1 s -1Combinations of these catalytic properties are also possible, for example, in some embodiments, the nanostructure or composition thereof has a CO→CO turnover frequency (TOF) of about 1-20 mol g -1 s -1 and / or a CO → CO2 conversion rate of about 1 to about 5 × 10 -3 Mol Mol -1 s -1 In some embodiments, the nanostructure or composition thereof has a CO→CO2 conversion rate according to the performance provided in FIG.

[0250] The nanostructures or compositions thereof can be used to purify a water stream (e.g., water) by contacting the water stream with the nanostructures or catalytic compositions thereof, according to any embodiment or example described herein, and one or more pollutant or contaminant materials present in the water stream are catalytically decomposed (e.g., oxidized) upon contact with the nanostructures or compositions thereof.

[0251] The catalyst composition may comprise or consist of the nanostructures and, optionally, one or more additives. Suitable additives may include one or more inert materials for enhancing catalytic activity, such as binders and fillers, and / or one or more catalyst promoters.

[0252] The catalyst composition may be provided as any suitable composition. In one embodiment, the catalyst composition may be a coating composition. The coating composition may be applied to a surface or substrate, such as quartz wool. Additional additives, such as binders, may facilitate coating of the catalyst composition onto the surface. The catalyst composition or coating may be provided as a partial coating or a complete layer on the surface. The catalyst composition may be deposited on the surface by brush coating, painting, slurry spraying, spray pyrolysis, dip coating, ink printing, sputtering, chemical or physical vapor deposition techniques, electroplating, screen printing, or tape casting.

[0253] In embodiments, the loading of nanostructures in the catalyst composition may be less than 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 18%, 16%, 14%, 12%, 10%, 8%, 6%, 4%, or 2% by weight. The catalyst loading may be at least 1%, 3%, 5%, 7%, 9%, 11%, 13%, 15%, 17%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90% by weight. In one embodiment, the catalyst is comprised of nanostructures.

[0254] The present disclosure may also be defined by reference to one or more of the following numbered paragraphs:

[0255] 1. A method for forming a nanostructure, comprising: providing a metal coordination polymer having multiple reactive metal-based species coordinated to one or more ligands; and removing at least a portion of the coordinated ligands to allow the reactive metal-based species to form more stable metal-based species, thereby forming the nanostructure. The method comprising:

[0256] 2. The method of paragraph 1, wherein removing at least a portion of the ligand comprises increasing the pH of a mixture comprising the nanostructures.

[0257] 3. The method of paragraphs 1 or 2, wherein removing at least a portion of the ligand comprises heating the metal coordination polymer.

[0258] 4. The method of any one of paragraphs 1 to 3, wherein the ligand has only one binding site.

[0259] 5. The method of any one of paragraphs 1 to 4, wherein the ligand comprises a carboxyl group.

[0260] 6. The method of any one of paragraphs 1 to 5, wherein the metal coordination polymer forms a sheet, and a plurality of sheets can be assembled to form a layered material.

[0261] 7. The method of paragraph 6, wherein the layered material is exfoliated to form a dispersion of discrete sheets prior to removing at least a portion of the coordinated ligands.

[0262] 8. The method of paragraph 7, wherein the steps of exfoliating the layered material and removing at least a portion of the coordinated ligands are performed simultaneously.

[0263] 9. Rayville Ions are intercalated between the laminated sheets, and the step of exfoliating the layered material comprises: Rayville 9. The method of paragraph 7 or 8, comprising removing ions.

[0264] 10. The method of any one of paragraphs 6 to 9, further comprising altering the structure of the layered material prior to removing at least a portion of the coordinated ligands, wherein the reactive metal-based species remains unchanged during the alteration of the structure of the layered material.

[0265] 11. The method of any one of paragraphs 1-10, wherein the step of providing the metal coordination polymer comprises forming the metal coordination polymer, and forming the metal coordination polymer comprises combining a first metal atom with a ligand, and the metal of the first metal atom is the same as the metal in the reactive metal-based species.

[0266] 12. The method of paragraph 11, wherein the step of forming a metal coordination polymer comprises electrodeposition.

[0267] 13. The method of paragraph 11, wherein the step of forming the layered material comprises heating a solution of the metal atoms and ligands.

[0268] 14. The method of any one of paragraphs 1 to 13, wherein the metal of the reactive metal-based species is multivalent.

[0269] 15. The method of any one of paragraphs 1 to 14, wherein the reactive metal-based species forms an unstable metal oxide-based species upon removal of the ligand.

[0270] 16. The method of paragraph 15, further comprising converting the unstable metal oxide-based species to a more stable metal oxide.

[0271] 17. The method of any one of paragraphs 1-16, further comprising adsorbing a second metal-based species onto the surface of the nanostructure.

[0272] 18. The method of paragraph 17, wherein the second metal-based species is adsorbed onto the surface of the nanostructure by removing at least a portion of the coordinated ligands in the presence of the second metal.

[0273] 19. The method of paragraph 17 or 18, wherein the second metal base is different from the more stable metal base species.

[0274] 20. The method of any one of paragraphs 17-19, wherein the second metal-based species is in ionic forms of metals, nonmetals, metalloids, and / or metalloids, as well as forms including oxides and nonoxides.

[0275] 21. The method of any one of paragraphs 17 to 20, wherein the second metal-based species comprises Cu, Ni, Fe, and Zn.

[0276] 22. The method of any one of paragraphs 17 to 21, wherein the second metal-based species is oxidized once the second metal-based species is adsorbed onto the surface of the nanostructure.

[0277] 23. The method of any one of paragraphs 1 to 22, wherein the reactive metal-based species forms the more stable metal-based species at room temperature.

[0278] 24. The method of any one of paragraphs 1 to 23, wherein the structure of the metal coordination polymer does not change during the formation of the more stable metal-based species.

[0279] 25. The method of any one of paragraphs 1 to 24, wherein the nanostructure is a porous nanostructure, and the step of removing at least a portion of the coordinated ligands and forming the reactive metal-based species into the more stable metal-based species forms the porous nanostructure.

[0280] 26. The method of any one of paragraphs 1 to 25, wherein the nanostructure is polycrystalline.

[0281] 27. The method of any one of paragraphs 1 to 26, wherein the nanostructure is solid and / or hollow.

[0282] 28. A nanostructure prepared using the method of any one of paragraphs 1 to 27.

[0283] 29. A nanostructure comprising nanosheets having a metal oxide, said nanosheets resulting from the removal of ligands that bind to reactive metal-based species which proceed to form a metal oxide.

[0284] 30. The nanostructure of paragraph 29, wherein the nanosheet has a thickness of less than 5 unit cells.

[0285] 31. The nanostructure of paragraph 30, wherein the thickness is two unit cells or less.

[0286] 32. The nanostructure of any one of paragraphs 29 to 31, wherein the metal oxide comprises an oxide of Ce.

[0287] 33. The nanostructure of any one of paragraphs 29 to 32, wherein the nanosheet is a porous nanosheet.

[0288] 34. The nanostructure according to paragraph 33, wherein the pores have a diameter in the range of about 2 nm to 14 nm.

[0289] 35. The nanostructure of any one of paragraphs 29 to 34, wherein the nanosheet has a defect concentration of approximately 18 to 30 atomic %.

[0290] 36. The nanostructure of any one of paragraphs 29 to 35, comprising a plurality of said nanosheets, said plurality of nanosheets being stacked to form a stacked structure.

[0291] 37. The nanostructure described in any one of paragraphs 29 to 36, wherein the nanostructure is formed from a metal coordination polymer precursor and the structure of the nanostructure is the same as the metal coordination polymer precursor.

[0292] 38. The nanostructure of any one of paragraphs 29 to 37, wherein the nanostructure is polycrystalline.

[0293] 39. The nanostructure of any one of paragraphs 29 to 38, wherein the nanostructure is solid and / or hollow.

[0294] 40. A catalyst comprising the nanostructure described in any one of paragraphs 28 to 39.

[0295] 41. The catalyst according to paragraph 40, wherein the catalyst is a photocatalyst or an oxidation catalyst.

[0296] 42. Use of a porous nanostructure according to any one of paragraphs 28 to 39 as a catalyst. EXAMPLES

[0297] The present disclosure is further illustrated by the following examples. It should be understood that the following descriptions are merely for the purpose of illustrating specific embodiments, and are not intended to be limiting with respect to the above description.

[0298] Materials and Methods Transmission Electron Microscopy (TEM) Dry powders of the specimens were suspended in water and dropwise coated on Cu-loaded carbon grids, then air-dried at room temperature. The prepared samples were used for TEM, scanning transmission electron microscopy (STEM), high-angle annular dark field (HAADF), energy dispersive spectroscopy (EDS) and electron energy loss spectroscopy (EELS) analyses. High-resolution transmission TEM (HRTEM) images and EDS analyses of the nanostructures were performed by a Philips CM 200 microscope (Eindhoven, the Netherlands), while HAADF images and EELS analyses were performed by a JEOL JEM-ARM200F microscope (Tokyo, Japan). Both instruments were operated at an accelerating voltage of 200 kV. In addition, the beam flux was reduced to a very low value of about 15 pA to minimize the beam damage effects. Finally, spectroscopy was performed using the spectral imaging mode with subpixel scanning enabled. This procedure ensured that the beam was constantly moving during acquisition to minimize local unevenness. In addition, to avoid beam damage to the sample during the EELS measurement, the sample was cooled to liquid nitrogen temperature.

[0299] Scanning Electron Microscopy (SEM) Scanning electron microscopy images were obtained by SEM (FEI Nova NanoSEM, secondary electron emission, accelerating voltage 5 kV, Hillsboro, OR, USA).

[0300] X-ray photoelectron spectroscopy (XPS) Surface analysis of the samples was performed using a Thermo Fisher Scientific ESCALAB 250Xi spectrometer (Loughborough, Leicestershire, UK) equipped with a monochromated Al Kα radiation source (1486.6 eV) hemispherical analyzer. XPS samples were prepared by dropwise coating of an aqueous suspension of the nanostructures onto a substrate and subsequent air drying at room temperature. The pressure in the analysis chamber was maintained below 8-10 mbar during XPS data acquisition. All binding energies were referenced to the C1s signal corrected to 285 eV, and the spectra were fitted using a convolution of Lorentzian and Gaussian profiles.

[0301] X-ray diffraction method (XRD) Mineralogical data for the nanostructures were obtained using a Philips X'Pert multipurpose X-ray diffractometer (Almelo, Netherlands) with CuKα radiation at [0.15405 nm], 2θ ranging from 20 to 80°, a step size of 0.02°, and a scan rate of 5.5° 2θ / min. Peaks were analyzed using X'Pert High Score Plus software (Malvern, UK).

[0302] Neutron Diffraction (ND) Neutron diffraction patterns for the structure analysis were collected on a Wombat high intensity powder diffractometer at the Open Pool Australian Light-water (OPAL) reactor at the Australian Nuclear Science and Technology Organisation (ANSTO). Two data sets were collected at 1.63 Å and 2.41 Å relative to a CaAlNaF3 standard sample.

[0303] Raman spectroscopy (Raman) Raman data were collected using a Renishaw inVia confocal Raman microscope (Gloucestershire, UK) equipped with a helium-neon green laser (514 nm) and a diffraction grating of 1800 g / mm. All Raman data were recorded with a laser power of 35 mW and a spot size of approximately 1.5 μm. Data analysis was performed using Renishaw WiRE 4.4 software and spectra were calibrated to the silicon peak located at approximately 520 cm-1.

[0304] Thermogravimetric analysis (TGA) The decomposition of Ce-CP was evaluated by using thermogravimetric analysis (TGA, TA Instruments, Q5000, 20–1000 °C, heating rate 10 °C / min) in various atmospheres of nitrogen and air.

[0305] Fourier Transform Infrared Spectroscopy (FTIR) ATR-FTIR; Spotlight 400 FTIR, PerkinElmer (Waltham, MA, USA) was used in the wavelength range of 400–4000 cm−1 to determine the chemical species present in the Ce-CPs.

[0306] Ab-initio molecular dynamics (MD) simulation Density functional calculations were carried out based on augmented plane wave pseudopotentials using the Perdew-Burke-Ernzerhof functional [Comput. Mater. Sci. 1996, 6, 15] implemented in the VASP code. For the electronic settings, a fine Monkhorst-Pack k-point lattice with spacing of 0.05 Å-1 and an energy cutoff of 520 eV was used. To find the ground state configuration, we performed quenched ab initio molecular dynamics simulations based on the microcanonical ensemble with a target temperature of 20 K and a step of 0.1 fs over 10 ps. Afterwards, a global optimization of the geometry to the equilibrated structure was performed with energy and force convergence criteria of 10-6 eV and 10-2 eV / Å, respectively. The final geometry optimization was performed using van der Waals correction (vdw-DFT) based on the application of the method of Michaelides [Phys.Rev.Lett.2004,92; Phys.Rev.B 2011,83,195131].

[0307] Atomic Force Microscope (AFM) The thickness of the nanosheets was measured by atomic force microscopy (AFM, Bruker Dimension Icon SPM, PeakForce Tapping mode). A ScanAsyst-Air probe (Bruker AFM probes) was attached to an AFM holder and used for all measurements. Samples were transferred onto glass or silicon substrates by applying a slight vacuum. The pixel resolution was 512 samples / line. A slow scan speed of 0.195 Hz was used to ensure accuracy. Peak forces were minimized to avoid sample deformation, and feedback gain settings were optimized appropriately. Height profiles from line scans were used to determine the film thickness.

[0308] Kelvin Probe Force Microscopy (KPFM) Amplitude-modulated KPFM (AM-KPFM) measurements were performed using a Bruker Dimension ICON SPM equipped with a Nanoscope V controller. A platinum-iridium coated AFM tip (SCM-PIT-V2, Bruker AFM probes) was used to scan the surface. The probe was first mounted on a cantilever holder and the laser was aligned to the back of the cantilever. The probe was then tuned to its resonance frequency with a slight offset to the right hand side of the resonance curve (typically for regular tapping mode images the left side of the resonance curve is tuned, which makes the interaction forces with the surface slightly repulsive; in contrast, for KPFM measurements a right hand offset was found to give better results in selected specimens). The oscillation amplitude was kept around 30-40 nm depending on the specimen. The amplitude set point and gain were adjusted appropriately for each specimen. The scan speed was around 0.3-0.4 Hz, the scan size was 10 μm, and the resolution was 512 samples per line. The scan settings included amplitude set point = 172mV, gain = 1.1, scan rate = 0.326Hz. Additionally, the operating parameters were as follows: the lift height was fixed at 50nm to avoid any effect from the surface topography of the specimen (a lower lift height of 30nm is sometimes used when scanning smaller areas). The drive2 amplitude of the AC bias applied to the tip during the lift pass was set to 500mV with a phase angle of 170°. The same AFM tip was also measured against freshly cut HOPG samples and / or pre-calibrated TiO2 on silicon reference samples for calibration tests performed before and after the specimen measurements. This calibration was important in determining the work function of the platinum tip, which can vary significantly from tip to tip.

[0309] Photoluminescence (PL) spectroscopy PL was measured using a spectrofluorometer (RF-5301PC, Shimadzu, Kyoto, Japan). The samples were used as free-standing laminated nanosheets.

[0310] Zeta potential measurement Zeta potential determinations were also performed using a Zetasizer Nano ZS (Malvern Instruments, 4 mW He-Ne laser, 633 nm). For this work, CeO2-x and heterojunction nanostructures were suspended in 3 mL of deionized water at a concentration of 20 μg / mL using separate glass tubes of 10 mL volume. The suspensions were sonicated for 2 min before measurements were performed.

[0311] Details of first-principles calculations First-principles calculations based on density functional theory (DFT) [Rev.Mod.Phys.2017,89,035003] were carried out to simulate and analyze the band structure differences between ceria nanosheets and the corresponding bulk and 0D / 2D heterostructures. The PBEsol functional implemented in the VASP software was used. To better handle the localized Ce 4f, Fe 3d, Ni 3d, and Zn 3d electronic orbitals, the "Hubbard-U" scheme with U=3 eV is adopted. The "projection operator augmented wave" method was used to represent the ionic core by considering the following electrons as valences: Ce 4f, 5d, 6s, and 4d; Fe 3d and 4s; Ni 3d and 4s; Zn 3d and 4s; and O 2s and 2p. The wave functions are expressed in plane wave basis truncated at 650 eV. For integration within the Brillouin zone we employ a Monkhorst-Pack k-point lattice with a density equivalent to that of a 16 × 16 × 16 case for a fluorite CeO2 unit cell. Geometry relaxation is performed by a conjugate gradient algorithm that allows simulation of cell shape and volume variations. Relaxation is stopped when the intraatomic forces are all less than 0.01 eV·Å-1. Using these technical parameters we obtain zero-temperature energies converged to within 0.5 meV per elemental composition. To estimate the accurate electron density of states and band gaps, we employ a hybrid HSE06 exchange calibration functional to perform single-point calculations on the equilibrium geometries determined at the PBEsol+U level.

[0312] Photocatalytic activity test The photocatalytic activity of the nanostructures was evaluated by analyzing the photodegradation of methylene blue (MB, M9140, dye content ≥ 82 wt%, Sigma-Aldrich) in aqueous solution under solar irradiation. By using a UV-visible spectrometer (UV-Vis, PerkinElmer Lambda 35, aperture size 20 mm × 10 mm), the gradual decrease in intensity of the MB absorbance peak at 664 nm in the presence of the nanosheets was recorded. The concentration of the nanosheet samples was 1 × 10 -5 The concentration was determined to be 0.5 mg / mL in 50 mL of MB solution with 100 μM. To eliminate the role of adsorption / desorption equilibrium between the dye and the surface of the nanosheets during light irradiation, the suspension was stirred with the nanosheets for 15–20 min under dark conditions before irradiation. The suspension was exposed to 100 mW / cm 2 light under 1 sun of AM1.5 simulated light. 2 The samples were irradiated with an illuminance output of 10000 g for 0–120 min at 20 min intervals. The CeO2-x and heterojunction nanostructures were isolated by centrifugation (10000 g, 10 min) and then the optical absorption was measured in the range of 400–800 nm. The degradation of MB solution was quantitatively evaluated based on the absorbance determined by the peak intensity at 664 nm by UV-Vis absorbance spectrophotometry (UV-Vis, PerkinElmer Lambda 35 UV-Visible spectrophotometer, aperture size 20 mm × 10 mm). The same samples for repeating the photodegradation test were used to test the high photocatalytic stability of the heterojunction nanostructures.

[0313] Carbon monoxide (CO) conversion test The CO oxidation catalytic activity was evaluated using a fixed-bed quartz microreactor (inner diameter = 6.0 mm). 50 mg of catalyst sample was placed on the quartz wool bed in the reactor, and the system was purged with N2 gas for 20 min. Then, the reaction gas containing CO (10 sccm) and O2 (25 sccm) in N2 (100 sccm) was introduced at an initial temperature of 30 °C without catalyst pretreatment (space velocity 162000 mL / (gcat.h)). The temperature was increased incrementally to 150 °C with a step size determined by the point on the ignition curve. The composition of the exiting gas was evaluated by a Young Lin-6100 gas chromatograph equipped with a thermal conductivity detector (TCD) and a Carboxen-1010 PLOT column.

[0314] Example 1: Synthesis of metal coordination polymers 1.1 Synthesis of Ce-CP The synthesis of Ce-CP tubes was carried out by chronopotentiometric electrodeposition in an unsplit three-electrode configuration system using an electrochemical station (Ezstat Pro, Indiana, USA) with a resolution of 300 μV and 3 nA (within the range of ±100 μA). Fluorine-doped tin oxide on glass (FTO, Wuhan Geo Scientific Education Instrument, China, 3.0 cm × 1.5 cm, film resistance approximately 16 Ω / sq2), platinum wire (Basi Inc., Indiana, USA, L = 23 cm, D = 0.5 mm), and Ag / AgCl (Basi Inc., Indiana, USA) were used as the working electrode, counter electrode, and reference electrode, respectively. The electrolyte was prepared from a mixture of 0.05 M glacial trichloroacetic acid (TCA) and 0.05 M Ce(NO3)3.6H2O. The pH of the as-prepared aqueous solution was measured to be about 3, but was raised to 6 using 1 M NaOH solution with magnetic stirring at 500 rpm. Prior to electrodeposition, each substrate was stepwise cleaned by ultrasonication in ethanol and acetone, followed by immersion (1 cm) in 45% nitric acid for 2 min and drying with compressed nitrogen. Anodic electrodeposition was performed by applying a high voltage of 1.2 V vs. Ag / AgCl for 50 min at room temperature, which, crucially, is within the oxidation region of water. As a result, electrodeposition was accompanied by oxygen bubbling at the FTO working electrode and hydrogen bubbling at the Pt counter electrode. The deposit was washed by gentle spraying with DI water and dried at room temperature in air. Ce-CP tubes were deposited using chronopotentiometric electrodeposition at an applied voltage of 1.4 V. FIG. 49(a) shows a representative schematic of the three-electrode electrochemical cell used for the synthesis of Ce-CP tubes during vigorous oxygen evolution and deposition of free-standing hexagonal tubes of Ce-CP on fluorine-doped tin oxide (FTO) substrates.

[0315] 1.2 Synthesis of Ti-CP Ti-CP was prepared by injecting an ice-cold solution of TiCl4 (27.41 μL, 0.25 mmol) into a mixture of DMF (4 mL) and formic acid (7.5 mL), followed by heating at 100 °C for 16 h. The as-synthesized powder was then washed with DMF and acetone by three cycles of centrifugation (5000 g, 20 min), and the obtained Ti-CP powder was dried at 60 °C under vacuum for 24 h.

[0316] 1.3 Synthesis of Zr-CP In a typical procedure, ZrCl4 (58 mg, 0.25 mmol) was added to a mixture of dimethylformamide (DMF, 4 mL) and formic acid (7.5 mL) followed by sonication at room temperature for 10 min. The resulting clear liquid was then transferred into a Teflon-lined stainless steel vessel and heated at 100 °C for 16 h. After cooling to room temperature, the resulting white powder was washed three times with DMF (5000 g, 20 min) followed by solvent exchange with acetone. The final product was dried at 60 °C for 24 h to remove the solvent.

[0317] 1.4 Synthesis of MOF-5 For the preparation of MOF-5, Zn(NO3)2.4H2O (3.14 g, 15.8 mmol) was added to a mixture of dimethylformamide (DMF, 100 mL) and terephthalic acid (0.665 g, 4 mmol) and then stirred at room temperature for 15 min. The resulting clear solution was then transferred into a Teflon-lined stainless steel vessel and heated at 105 °C for 24 h. After cooling to room temperature, the white precipitate was dispersed in chloroform (100 mL) and stirred for 24 h for solvent exchange. It was then dried under vacuum at 105 °C for 24 h.

[0318] Example 2: Synthesis of nanostructures 2.1 Chief Operating Officer 2-x Synthesis of nanosheets Ce-CP powder (50 mg) was added to 50 mL of DI water (pH 7), then stirred (100 rpm) for 5 min, followed by ultrasonic treatment at room temperature for 10 min. Then, 10 ml of NaOH solution (3 M) was added dropwise to convert the Ce-CP to CeO.2-x The resulting nanosheets were collected and washed with DI water. The final product was then air-dried at 100 °C for 24 h. Figure 49(b) shows the exfoliation of the Ce-CP tubes into Ce-CP nanosheets and the subsequent transformation of the Ce-CP nanosheets into porous CeO 2-x CeO nanosheets by a three-step process including oxidation 2-x A schematic diagram of the formation is shown.

[0319] 2.2 Large-scale CeO 2-x Nanosheet synthesis 700 mg of Ce-CPs were added to 200 mL of DI water at room temperature and then stirred for 72 h using a magnetic stirrer (100 rpm). Large sheets with thicknesses of up to 0.5 cm were produced by this method. These large-scale sheets were essentially formed by stacking atomic-scale thin nanosheets formed in DI water. Longer times usually resulted in the synthesis of wider and thicker sheets. The addition of NaOH (3M) transformed the Ce-CPs into CeO 2-x The dispersed phase was then filtered using filter paper to obtain CeO 2-x The sheet was separated from the liquid. The sheet was dried in an oven at 100 °C for 12 hours. This method produced CeO 2-x Nanosheets have been produced on a large scale.

[0320] 2.3 Synthesis of TiO2 nanosheets TiO2 nanosheets were prepared by adding 10 mg of Ti-CP powder into 5 mL of DI water and then stirring (500 rpm) at room temperature for 3 h. Then, 5 mL of NaOH (0.1 M) solution was added to the mixture and stirring was continued at room temperature for 2 h. The resulting muddy mixture was washed three times with DI water (10,000 g, 20 min), and the resulting nanosheets were dried at 60 °C for 24 h.

[0321] 2.4 Synthesis of ZrO2 nanosheets ZrO2 nanosheets were prepared by adding 10 mg of Zr-CP powder into 5 mL of DI water and then stirring (500 rpm) at room temperature for 3 h. Then, 5 mL of NaOH (0.1 M) solution was added to the mixture and stirring was continued at room temperature for 2 h. The resulting muddy mixture was washed three times with DI water (10,000 g, 20 min) and the resulting nanosheets were dried at 60 °C for 24 h.

[0322] 2.5 Fe2O3 / Fe3O4-CeO 2-x Synthesis of (FCO) CeO was prepared by adding 24 mg of Ce-CP powder into 15 mL of DI water, followed by stirring (100 rpm) for 30 min at room temperature with the pH increased to 8. 2-x The nanosheets were first prepared. Then, 5 mL of iron(II) chloride (FeCl2) solution (0.3 mM) was added to the acidic Ce-CP nanosheets solution (pH=6), followed by 2 mL of NaOH (1 M) under gentle stirring, which was continued for 30 min. The resulting muddy mixture was washed with DI water (10000 g, 40 min) and heated at 200 °C for 24 h.

[0323] 2.6 NiO-CeO 2-x Synthesis of (NCO) CeO was prepared by adding 24 mg of Ce-CP powder into 15 mL of DI water, followed by increasing the pH to 8 and stirring (100 rpm) at room temperature for 15 min. 2-x The nanosheets were first prepared. Then, 5 mL of nickel(III) nitrate (Ni(NO3)2·6H2O) aqueous solution (0.3 mM) was added to the acidic Ce-CP nanosheet solution (pH=6), followed by 2 mL of NaOH (1 M) under gentle stirring, which was continued for 30 min. The resulting muddy mixture was washed with DI water (10000 g, 40 min) and heated at 200 °C for 24 h.

[0324] 2.7 ZnO-CeO 2-x Synthesis of (ZCO) CeO was prepared by adding 24 mg of Ce-CP powder into 15 mL of DI water, followed by increasing the pH to 8 and stirring (100 rpm) at room temperature for 15 min. 2-x The nanosheets were first prepared. Then, 5 mL of zinc(II) nitrate (Zn(NO3)2·6H2O) aqueous solution (0.3 mM) was added to the acidic Ce-CP nanosheets solution (pH=6), followed by 2 mL of NaOH (1 M) under gentle stirring, which was continued for 30 min. The resulting muddy mixture was washed with DI water (10,000 g, 40 min) and heated at 200 °C for 24 h.

[0325] 2.8 Various CeO from Ce-CP 2-x Synthesis of nanostructures Tubular nanostructures. Ce-CP powder (400 mg) was left in aqueous NaOH solution (200 mL, 3 M) for 30 min at room temperature. The tube was then washed with water (DI) by centrifugation at 5000 g (10 min) three times. The collected tube was then air-dried at 80 °C for 24 h.

[0326] Cuboid nanostructures. Ce-CP powder (100 mg) was added to 100 mL of NaOH solution (10 M) and mixed at room temperature using a magnetic stirrer (300 rpm, 5 min). The resulting solution was then hydrothermally treated at 140 °C for 24 h. The resulting cubes were washed three times by centrifugation at 7000 g (10 min). The final precipitate was then air-dried at 80 °C for 24 h.

[0327] Dumbbell-shaped nanostructures. Ce-CP powder (100 mg) was added to 100 ml of DI water at acidic pH 5 under gentle stirring (100 rpm) at room temperature. The solution was then fired at 350 °C (low speed of 1 °C / min) for 2 h. The resulting powder was washed by three cycles of centrifugation (5000 g, 10 min). The final product was then air-dried at 80 °C for 24 h.

[0328] Rhombohedral nanostructures. Ce-CP (10 mg) was dissolved in acetone (4 mL) by stirring (300 rpm) at room temperature for 10 min. The resulting solution was then recrystallized as rhombohedral Ce-CP at room temperature. The resulting nanoparticles were then collected and left to stand in NaOH solution (3 M) for 30 min to form CeO 2-x The final product was then washed three times with DI water (3000 g, 10 min) and air-dried at 80 °C for 24 h.

[0329] Flower-shaped nanostructures. Ce-CP (40 mg) was dissolved in acetone (2 mL) by stirring (300 rpm) at room temperature for 10 min. The resulting solution was then spread on a glass substrate and recrystallized at room temperature to form flower-shaped Ce-CP. The resulting Ce-CP nanostructures were then gently aged in NaOH solution (3 M) for 30 min to form CeO 2-x Finally, the obtained nanoflowers were washed three times with DI water (5000 g, 15 min) and air-dried at 80 °C for 24 h.

[0330] Hollow spherical nanostructures. Ce-CP (40 mg) was dissolved in 4 mL of ethanol under stirring (100 rpm) at room temperature for 10 min. The resulting solution was then recrystallized at a low temperature of 0 °C for 24 h to form hollow spheres of Ce-CP. The resulting nanostructures were then gently placed in concentrated NaOH solution (3 M) for 30 min to obtain the CeO 2-x The hollow spheres were washed with water recovered by three cycles of centrifugation (5000 g, 10 min), and then air-dried at 80° C. for 24 h.

[0331] Hollow octahedral nanostructures. Ce-CP (40 mg) was dissolved in ethanol (4 mL) by magnetic stirring (100 rpm) at room temperature for 10 min. The solution was then recrystallized at room temperature to form the hollow octahedral morphology of Ce-CP. The resulting Ce-CP nanostructures were then aged in an aqueous solution of NaOH (3 M) for 30 min to form CeO 2-x Final CeO 2-xThe powder was washed by three cycles of centrifugation (5000 g, 15 min) and then air-dried at 80° C. for 24 h.

[0332] Solid spherical nanostructures. Ce-CP (40 mg) was dissolved in 40 mL of ethanol under continuous stirring (100 rpm) at room temperature for 10 min. The solution was then transferred into a Teflon-coated steel autoclave reactor for hydrothermal processing (140 °C, 24 h). The resulting spheres were centrifuged and redispersed in water three times (7000 g, 10 min), and the final precipitate was air-dried at 80 °C for 24 h.

[0333] 2D-3D scaffold nanostructures. Ce-CP (300 mg) was added to 4 mL of triethanolamine (TEA) and mixed at room temperature using a magnetic stirrer (100 rpm, 10 min). The mixture was then heated to 450°C with a heating rate of 6°C / min and a residence time of 3 h. The resulting powder was then cooled and collected for further characterization.

[0334] Solid octahedral nanostructures. Ce-CP (400 mg) was added to 10 mL of dimethyl sulfoxide (DMSO) at room temperature under gentle stirring for 10 min. The solution was then gently recrystallized at room temperature to obtain the octahedral morphology of Ce-CP. The resulting Ce-CP nanostructures were then placed in an aqueous solution of NaOH (3 M) for 30 min to obtain CeO 2-x The final dispersion was then washed with DI water by three cycles of centrifugation (5000 g, 10 min) and then air-dried at 80° C. for 24 h.

[0335] Honeycomb scaffold nanostructures. Ce-CP (40 mg) was added to 100 mL of dimethyl sulfoxide (DMSO) under gentle stirring at room temperature for 10 min. The solution was kept at a low temperature of 0 °C for 2 h to form a honeycomb scaffold at the air-liquid interface. The resulting scaffold was then collected by contact printing on a clean glass substrate. The resulting honeycomb scaffold was then heated to 350 °C and maintained for 2 h to obtain CeO 2-x converted into nanostructures.

[0336] CeO derived from Ce-CP by decomposition / reassembly in polar solvents 2-x General procedure for the synthesis of nanostructures 3D CEO 2-x To synthesize the forms, Ce-CP precursors at various concentrations ranging from 4 to 120 M (full details of concentrations, temperatures and obtained forms are given in Table A below) were added to pure ethyl alcohol (96.0-97.2%) as a solvent and then stirred at room temperature for 5 min. 4+ The resulting solutions, yellow in colour indicative of the ions, were evaporated at different rates by adjusting the temperature in the range 0°C to +25°C, resulting in the recrystallisation of Ce-CP in different forms. Temperatures below 25°C (room temperature) were achieved by the use of a freezer with a temperature probe inserted.

[0337] Ce-CP to CeO 2-x Conversion to is effected by oxidizing the Ce-CP form by immersion in 6 M aqueous NaOH for 30 minutes, followed by rinsing with a DI water spray and completing the drying by heating in an oven at 200°C.

[0338] 2D CEO 2-x The synthesis of the forms was carried out in an identical manner with the following exceptions. The evaporation temperature ranged from -10 to 0 °C, and the corresponding vapor pressures are shown in Table A. For thickness measurements as a function of drying time, Ce-CP nanosheets were deposited on glass substrates using contact printing technique. Nanosheets of various thicknesses were obtained by controlling the evaporation time ranging from 6 to 72 h, and the data obtained are shown in Figure 54. Furthermore, nanosheets were obtained at a constant temperature of -10 °C but with varying Ce-CP concentrations, and the AFM results are shown in Figure 55. [Table 1]

[0339] 2.9 Synthesis of various ZnO nanostructures from MOF-5 Spherical nanostructures. As-synthesized MOF-5 (100 mg) was dispersed in a vial containing tetrapropylammonium hydroxide (TPAOH, 2 mL, 40 wt%) and stirred at room temperature for 5 min. The dispersion was then cooled to 0 °C and kept undisturbed for 72 h. After nanocrystal growth, the precipitate was washed three times with EtOH (40 mL) and air-dried at room temperature.

[0340] Needle-like nanostructures. MOF-5 (100 mg) was dispersed in tetrapropylammonium hydroxide (TPAOH, 2 mL, 40 wt%) and transferred into a Teflon-lined autoclave for hydrothermal processing (140 °C, 24 h). The resulting precipitate was washed three times with EtOH (40 mL) and air-dried at room temperature.

[0341] Rod-like structure. MOF-5 (100 mg) was added to a vial containing HO (40 mL) and stirred (500 rpm) at 40 °C for 12 h. The dispersion was then washed three times with EtOH (40 mL) and air-dried at room temperature.

[0342] Bundle nanostructures. MOF-5 (100 mg) was added to a vial containing acetone (39 mL) and KOH solution (1 mL, 10 M) and gently stirred at 40 °C for 12 h. The resulting precipitate was washed with EtOH (40 mL) by three cycles of centrifugation (4000 g, 20 min), and the final product was air-dried at room temperature.

[0343] Wafer-like nanostructures. MOF-5 (0.1 g) was dispersed in a vial containing tetrabutylammonium hydroxide (TBAOH, 2 mL, 40 wt%), stirred at room temperature for 5 min, and kept under static conditions for 12 h. The resulting precipitate was then washed with EtOH (40 mL) by three cycles of centrifugation (4500 g, 15 min), and then air-dried at room temperature.

[0344] Fiber nanostructure. MOF-5 (0.1 g) was added to a vial containing ethanol (39 mL) and HO (1 mL) and stirred at 40 °C for 12 h. The resulting dispersion was then centrifuged and redispersed in EtOH (40 mL) three times, then air-dried at room temperature.

[0345] Example 3: Synthesis and characterization of Ce-CPs The electrodeposition of Ce-CP was carried out using a modified anodic electrochemical deposition (called chronoamperometric technique; MACE), in which a constant potential is applied while the current varies as a function of deposition time. Figure 1a shows a scanning electron microscope (SEM) image of a free-standing Ce-CP hexagonal tube with a bulk layered structure. In addition, a transmission electron microscope (TEM) image and the corresponding schematic diagram are shown in Figure 1b and c, respectively.

[0346] The layered Ce-CP tubes can be easily exfoliated by sonication in deionized water (DI) at room temperature. Figure 1d and e show ex situ SEM and TEM images of partially exfoliated Ce-CP after 4 min of sonication. The corresponding schematic is shown in Figure 1f. Longer sonication (8 min) led to complete Ce-CP exfoliation, as shown in the SEM and TEM images in Figure 1g and h, respectively. The overall exfoliation progress as a function of sonication time is shown diagrammatically in Figure 1c-i. The final step involves increasing the pH of the solution to pH = 8 during sonication, resulting in incomplete exfoliation of CeO from the Ce-CP nanosheets. 2-x It is important to note that during this transformation, a high density of nanopores is formed throughout the ultrathin sheets, as shown in Figure 1j and k. This is due to the high electric field strength of Ce(IV) over a wide pH range and therefore the corresponding increase in the electric field strength of CeO 2-x This is believed to be due to the strong affinity of the organic bidentate trichloroacetate (TCA) linker for the formation of CeO. 2-x A schematic of the porous structure of the nanosheets is also shown, and a schematic of the modified anodic electrochemical deposition technique and subsequent exfoliation and organic linker removal is shown in Figure 49.

[0347] In the absence of reference data consistent with the X-ray diffraction (XRD) pattern obtained for Ce-CP, the corresponding crystal structure was investigated by comparative ab-initio molecular dynamics simulations, as well as XRD and neutron diffraction patterns, as shown in Figures 8-19 and Tables 1-2. The data representing the crystallography of Ce-CP, which was determined to be Ce(TCA)2(OH)2·2H2O, is in the triclinic space group.

number

[0348] The crystal structure of layered Ce-CP is shown in Figure 1m, where the intercalated protons and the chloride ions of the terminal TCA ligands hold the interlayer space together. Application of ultrasound to the Ce-CP tubes enhances the exfoliation by vibrational scission of the nanosheets and the resulting facilitated water molecule penetration (Figure 1n). Furthermore, the c-axis lattice parameter of the Ce-CP crystal structure was measured to be 1.1n, which represents the thinnest possible Ce-CP monolayer of Ce-CP nanosheets. Increasing the pH of the solution leads to the dissolution of TCA from the two surfaces of the M-OH substructure (Figure 1n). This is followed by the formation of the highly reactive internal M-OH (Ce(OH)2 2+ ) substructure to the more stable Ce(OH)4, followed by the stable CeO 2-x (Fig. 1o) is rapidly formed without any morphological change. 2-x The structural evolution during the transformation to Ce-CP and CeO was studied using XRD and SAED analyses (Fig. 20). To confirm the removal of TCA, 2-x Energy dispersive spectroscopy (EDS) elemental mapping was performed on both nanosheets, as shown in Figures 21 and 22, respectively. 2-x The rapid evolution to is studied by in situ laser Raman microspectroscopy of nanosheets subjected to alternative removal methods (Figure 23).

[0349] Figure 6 shows a current-deposition time graph, where the current density increases rapidly in the initial stage of deposition. The high current density is attributed to the oxygen evolution reaction at the working electrode (FTO substrate). However, the current density drops after about 100 s of potential application, followed by a gradual taper after about 160 s. The variation of the current density was studied as a function of deposition time by the nucleation / growth mechanism using SEM images (inset of Figure 6). The image obtained at the peak current density (Figure 6b) revealed small nuclei of Ce-CP. The lower conductivity of the Ce-CP polymer compared to the FTO substrate could result in a decrease in the current density. The continued growth of the Ce-CP polymer led to a decrease in the exposed FTO surface and thus to a decrease in the current density. Interestingly, Figure 10c shows that after 150 s of deposition, the nuclei grow perpendicular to the substrate forming hexagonal rods. By increasing the deposition time (Figure 6d), holes were formed in the centers of the hexagonal rods, and eventually the hexagonal rods transformed into hexagonal tubes (Figure 6f). This transition can be attributed to the effect of applying high current density, which caused the generated oxygen bubbles to move perpendicular to the substrate. Thus, the morphology evolution proceeds to minimize the contact surface between Ce-CPs and the FTO substrate, since the accessibility of water in the FTO substrate is enhanced, leading to the oxygen evolution reaction.

[0350] Applying a high current density in the oxygen evolution region resulted in a high rate of oxygen bubble generation in the region adjacent to the FTO substrate. The high O2 concentration environment leads to the oxidation of Ce(III) species to Ce(IV), which is shown as step (1) in Figure 7. From another perspective, the water splitting reaction involves the evolution of one mole of oxygen followed by the formation of four moles of protons, which leads to a rapid decrease in the local pH and the formation of a strongly acidic environment. All these reactions occur above the water stability region, marked in blue in Figure 7.

[0351] A region of stability for Ce(IV) species in aqueous solution exists due to the high electric field strength (affinity for hybridization) of Ce(IV) species. Thus, oxidation of Ce(III) species to Ce(IV) leads to the formation of Ce(IV) hydroxide, albeit with unsaturated coordination bonds, even at acidic pH. This is also shown in the Pourbaix diagram (Figure 7), where the formation of Ce(IV) hydroxide with low coordination number occurs followed by rapid proton evolution (step (2)). In the final step, the presence of TCA molecules together with the unstable Ce(IV) species leads to coordination bonds between the Ce(IV) hydroxide and the TCA ligands, resulting in the formation of a monolayer. The presence of a high concentration of protons due to the acidic pH allows protons to intercalate into the interlayer space of the Ce(IV)-TCA coordination monolayer and establish van der Waals interactions between the layers, resulting in the formation of (Ce(OH)2(TCA)2.2H2O).

[0352] The possible chemical reactions leading to the formation of Ce-CP are as follows: (1) Deprotonation of TCA in water and subsequent reduction of the pH value from 6.5 to less than 2.3: CCl3COOH+H2O→H3O + +CCl3COO - (Formula 1) (2) Free Ce resulting from the dissociation of cerium nitrate in solution 3+ and release of nitrate ions: Ce(NO3)3.6H2O → Ce 3+ +3NO3 - +6H2O (formula 2) (3) At pH = 6, the oxidation potential of cerium was found to be 0.55 V vs. Ag / AgCl, while the onset of water oxidation is at 0.8 V. Application of a constant potential of 1.2 V vs. Ag / AgCl resulted in rapid oxygen evolution at the anode (FTO) surface (Eqs. 3-5): 2H2O→4H + +O2+4e - (Formula 3) 4OH - →4H + +2O2+4e - (Formula 4) HO2 - +OH - →H2O+O2+2e - (Formula 5) The high molecular oxygen generation rate on the FTO substrate leads to the oxidation of Ce(III) species to Ce(IV). However, during water oxidation, the evolution of one mole of oxygen is followed by the formation of four moles of protons, which in turn leads to a rapid decrease in the local pH and an increase in the proton concentration. Under this condition, the Ce(IV) hydroxide species is in a soluble form. In addition, due to the low pKa value of TCA, the deprotonated TCA acts as a second building block (SBU) to bridge the Ce(IV) hydroxide species together, leading to the formation of novel polycrystalline Ce-CPs. The corresponding formula is shown below: Ce 4+ +2OH - +2TCA+2H2O=Ce(OH)2(TCA)2.2H2O (Formula 6)

[0353] The layered Ce-CP tubes can be easily exfoliated by sonication in deionized water (DI) at room temperature. Figure 1d and Figure 1e show ex situ SEM and TEM images of partially exfoliated Ce-CP after 4 min of sonication. The corresponding schematic is shown in Figure 1f. Longer sonication (8 min) led to complete Ce-CP exfoliation, as shown in the SEM and TEM images in Figure 1g and h, respectively. The overall exfoliation progress as a function of sonication time is shown diagrammatically in Figure 1c-i. The final step involves increasing the pH of the solution to pH = 8 during sonication, resulting in incomplete exfoliation of CeO from the Ce-CP nanosheets. 2-x It is important to note that during this transformation, a high density of nanopores is formed throughout the ultrathin sheets, as shown in Figure 1j and k. This is due to the high electric field strength of Ce(IV) over a wide pH range and therefore the corresponding increase in the electric field strength of CeO 2-x This is believed to be due to the strong affinity of the organic bidentate trichloroacetate (TCA) linker for the formation of CeO. 2-x A schematic diagram of the porous structure of the nanosheet is also shown.

[0354] The Raman spectrum of Ce-CP (Figures 11 and 11A) was comprehensively analyzed and assigned by the vibrational modes of pure TCA and CeO2. The data show that some of the peaks observed in the Ce-CP spectrum are also present in the TCA spectrum, suggesting the presence of TCA molecules in Ce-CP. -1 The peaks at 688 cm are thought to be due to the asymmetric and symmetric bending vibrations of the C-Cl bond, respectively. -1 The peaks at 845 and 744 cm belong to the symmetric stretching vibration mode of the C-Cl bond. -1 The peak at 952 cm is due to the asymmetric stretching vibration mode of the same bond. -1 The peaks located at 952–962 cm correspond to the symmetric vibrational modes of the carbon-carbon bond (CC). Further comparison of the two spectra reveals that some of the peaks (952–962 cm) -1 , 700~740cm -1 , and 683-688cm -1 ) which is believed to be due to the change in vibrational mode of the bonds in the TCA structure upon interaction with the cerium ion. In addition, TCA has a Raman shift at 1746 cm, which corresponds to the vibrational mode of the free carboxylate group (COO). -1 The peaks at 1367 (symmetric stretching vibration) and 1662 cm -1 (asymmetric stretching vibration) splits into two peaks at 455 cm -1 This may be due to the interaction between the COO groups and Ce, which leads to the formation of Ce-O bonds, which exhibit a peak at 214 cm -1 and 360cm -1 The peaks at 455 and 470 cm are correlated with the in-phase and anti-phase vibrational modes of the Ce-CP structure. -1 There are two main peaks located at 1000 nm. The former is assigned to the symmetric stretching vibration of cerium and its coordinated oxygen, while the latter is due to the vibrational modes of cerium bonded to chlorine and oxygen.

[0355] The FTIR spectrum of the Ce-CP tube (Figure 12) shows peaks at 3620 and 3410 cm -1 The band centered at 1660 cm indicates the stretching vibration of the hydroxyl group, revealing the presence of water and OH groups in Ce-CP. -1 and 1360cm -1 The peak at 1040 cm is believed to be due to the asymmetric and symmetric stretching modes of the carboxyl group bound to the cerium cation. -1 and 966 cm -1 The peaks at 688 cm and 690 cm are due to the bending vibration of the carboxyl group and the symmetric vibration mode of the carbon-carbon bond (CC), respectively. -1 , 744cm -1 and 845 cm -1 The peak is believed to be due to the C-Cl vibration mode.

[0356] The XPS data of Ce-CP tubes (Figure 13) showed that peaks corresponding to the 3d, 1s, 1s and 2p orbitals of cerium, oxygen, carbon and chlorine elements could be detected at binding energies ranging from 880 to 920, 529 to 535, 284 to 292 and 198 to 202 eV, respectively. For cerium, the spin-orbit coupling of the d orbitals (3d 5 / 2 and 3d 3 / 2 ) represents Ce 3+ and Ce 4+ There are two oxidation states: 3d 5 / 2 Ce in Placement 4+ and Ce 3+ The corresponding binding energies of are located at 883, 889, and 899, and 881 and 886 eV, respectively (Table 1). The peak at 530 eV is located at Ce. 4+ This corresponds to the hydroxyl bonded to the carboxylate HO. A peak for the organic oxygen in TCA can be seen at 532 eV. At a binding energy of 534 eV, there is a small broad peak representing the structure HO. All peak positions are shown in Table 1. [Table 2]

[0357] Quantitative analysis of the elements in the Ce-CP structure was performed by peak deconvolution using a Gaussian fit, and the results are shown in Table 2. From the analysis, the stoichiometry of Ce-CP was determined to be Ce(OH) based on atomic percentage. 1.8 (TCA) 2.0 (H2O) 1.0 Furthermore, the XPS results were used for TGA analysis to confirm the molar ratio of Ce-CP structures from wt%, which will be described in detail in the following section.

[0358] Quantitative analysis of the elements in the Ce-CP structure was performed by peak deconvolution using a Gaussian fit, and the results are shown in Table 2. From the analysis, the stoichiometry of Ce-CP was determined to be Ce(OH) based on atomic percentage. 1.8 (TCA) 2.0 (H2O) 1.0 Furthermore, the XPS results were used for TGA analysis to confirm the molar ratio of Ce-CP structures from wt%, which will be described in detail in the following section. [Table 3]

[0359] The TGA analysis of Ce-CP (Figure 14) showed a similar pattern under both nitrogen and air atmospheres. There were four stages during which adsorbed water, structural water, chlorocarbons, and CO2 were removed from Ce-CP, respectively. The results indicate that 35.8 wt% of the total Ce-CP was converted to CeO2 under both conditions. The weight percentages of each organic component and the resulting products are shown in Table 3, along with the associated XPS analysis data for comparison. XRD and Raman spectroscopy of the Ce-CP samples after the TGA test (data not shown here) revealed that the cubic fluorite structure of CeO2 was formed by heat treatment in either gas. [Table 4]

[0360] Characterization data of Ce-CP crystal structure In order to identify the structure of Ce-CP, which does not match any existing structure in the crystallographic database (Cambridge Crystallographic Data Centre (CCDC)), attempts were made to produce single crystals of Ce-CP by the vapour layer diffusion method. However, all attempts resulted in the formation of polycrystalline Ce-CP. For this reason, based on the obtained chemical composition (Ce(OH)2(TCA)2·2H2O) and the obtained X-ray (1) and neutron (2) diffraction patterns, a Rietveld refinement (using the program package FullProf) was performed combining all three data sets to increase the level of information. The lattice parameters, atomic positions and zero-shift parameters were refined. Good approximations were obtained for both the X-ray and neutron diffraction patterns of Ce-CP (Figures 15 and 16). However, while the positions of the Ce atoms and the lattice parameters were found to be very similar to those of the experimental data, the interpretation of the obtained structure from a physical point of view was a challenge due to the uncertainty of the positions of the lighter elements, especially H (Figure 17).

[0361] To obtain a physically meaningful structure, the Rietveld refined lattice was used as a guide for density functional theory and subsequent ab initio molecular dynamics calculations (especially the lattice parameters and Ce positions). To roughly depict the coordination environment around the cerium atoms in the Ce-CP structure, a small stoichiometric supercell consisting of Ce(OH)2(TCA)2.2H2O with one-sixth the volume of the refined experimental structure was first used (Figure 17). Many coordination possibilities, e.g., Ce coordinated with Cl and O atoms of TCA, were exhaustively compared. The relaxed structure of the most stable coordination is shown in Figures 18A and 18B. Ce was found to be coordinated with seven O atoms, of which two are from the OH groups, two from each water molecule, and three from the two TCA molecules. The experimentally refined

number

[0362] The final optimized structure shown in Figure 18B(a) reproduces with reasonable accuracy the major diffraction peaks at low angles centered at 7.34982° and 813390°. It should be noted that the low resolution of XRD measurements limits the use of experimental diffraction patterns for evaluation of DFT optimized structures. As a result, comparison with measured patterns can only estimate the positions of larger atoms, while finer details, such as H-bond networks and hydrogen positions, can hardly be evaluated based on this comparison.

[0363] In addition, Ce-O (TCA) The bond is approximately 2.60 Å Ce-O (H2O) Bond and 1.96 Å Ce-O (OH) The bond was found to be about 2.56 Å, which is longer than either of the Ce-O bonds. (TCA) The weak bond strengthens the notion of the fragility of this bond. The empty Ce 4f, 5d, and 6s states in Figure 18B(b) point to the 4+ oxidation state of the Ce ion. Furthermore, the lack of overlap between the Ce states and the coordinated O states (Figure 18B(b)-(e)) suggests the absence of strong covalent bonds to Ce.

[0364] In summary, based on the results presented herein, the XRD pattern of the Ce-CP powder is triclinic Ce(OH)2(C2O2Cl3)2·2H2O, space group

number

[0365] Photoluminescence spectrum of Ce-CP CeO at room temperature 2-x The photoluminescence (PL) emission of the CeO heterojunction structure is shown in FIG. 2-x The PL spectrum of the nanosheets shows two small broad emissions with wavelengths of 426 nm (blue emission) and 510 nm (green emission). The former is F ++→It is thought to be due to 4f1 transition, because F ++ The 4f1 state is just below the 4f0 band acting as an electron trap, while the 4f1 state acts as a hole trap. 3+ The radiative recombination of these two traps results in excitation at a wavelength of 510 nm. 2-x The weaker PL intensities of these two emissions in nanosheets compared to reported CeO2 nanostructures once again confirms the short diffusion paths for charge carriers and hence the reduced radiative recombination.

[0366] Example 4: Synthesis and characterization of Ti-CP and Zr-CP The flexibility of the disclosed fabrication method is demonstrated by the synthesis of layered titanium-based CPs (Ti-CPs) and zirconium-based CPs (Zr-CPs). Details of the morphological and structural characterization of these bulk layered MCPs are shown in Figures 24-29. Ti-CPs and Zr-CPs, as well as Ce-CPs, were rapidly exfoliated as nanosheets in basic aqueous solutions, as shown by TEM and EDS analysis (Figures 30-39). CeO 2-x , TiO 2-x and ZrO 2-x The morphological analysis of the nanosheets is shown in Figure 3a-c, respectively, where the TEM images reveal the porous nanostructure of the MCP-derived metal oxides. Also, Figure 3d-f show the SAED patterns of the randomly oriented polycrystalline nanosheets, which are assigned to CeO2, TiO2, and ZrO2, respectively. Given the ultrathin nature of the porous nanosheets, the surface chemical analysis provides a de facto bulk analysis, since the penetration depth of XPS is about 3 nm. As an example, the deconvolution of the Ce 3d orbitals of the XPS spectrum reveals the presence of CeO 2-x Quantitative analysis of high Ce (Figure 40) was performed. 3+ The concentration was revealed, which is generally the corresponding oxygen vacancy concentration due to charge compensation ([V O ** These results are consistent with the EELS data shown in Figure 2d and e.

[0367] To measure the thickness of the porous metal oxide nanosheets, atomic force microscope (AFM) images were obtained by deposition of the nanosheets on a silicon substrate as shown in Figure 3g-i. The corresponding height profiles are shown in Figure 3j-l by two height steps from the substrate. 2-x In the case of TiO, these are about 1.1 nm and about 1.2 nm, indicating that the nanosheets are two unit cells thick (CeO unit cell = 0.54 nm). 2-x and ZrO 2-x The thicknesses of the nanosheets were measured to be approximately 10.0 nm and approximately 1.8 nm, respectively, indicating thicknesses of 20–40 and 3–4 unit cells, respectively. 2-x The relatively thicker thickness of the nanosheets may be due to the loose packing caused by the anisotropy of the tetragonal anatase, while the thin ZrO 2-x The nanosheets are likely derived from a de facto equiaxed lattice. These data suggest that self-assembled metal oxides with equiaxed or perhaps highly anisotropic and therefore self-aligned nanostructures are somewhat more likely to give rise to ultrathin nanosheets.

[0368] The Raman spectrum collected from the TiO2 nanosheets is shown in Figure 32. According to group theory, Eg (approximately 144 cm -1 ), B1g (about 397cm -1 ), B1g / A1g (approx. 516cm -1 ) and Eg (approx. 639 cm -1 There are four main peaks that can be attributed to TiO2 with Raman active modes of 153 cm− ... -1 Similarly, the B1g and Eg bands are blue-shifted to 397 and 639 cm, respectively. -1The asymmetric broadening of the peak and the observed shifts can be explained by the phonon confinement phenomenon that occurs by reducing the crystallite size to the nanoscale. The nanosheets in this study have a porous structure consisting of nanosized crystallites with diameters of 2-4 nm (as shown by high-resolution TEM images), which can explain these slight shifts as they occur. Furthermore, the 690 cm -1 The small broad peak at 2-x This may be thought to be due to.

[0369] XPS peaks for carbon 1s orbitals for both Ti-CP and TiO2 are shown in Figure 33. The peak at 248.8 eV is believed to be due to C-C bonds, either from the sample composition or from contaminants adsorbed on the surface of the sample. The peak at 286 eV is assigned to C-O-C bonds of formic acetic anhydride, whose concentration is determined to be 9.70 at% by calculation of the corresponding peak areas. However, this amount drops to only 2.20 at% upon conversion to TiO2 nanosheets. Furthermore, the peak at 288.5 eV corresponds to the O-C=O bond of formic acid, but its atomic percentage drops by a factor of about 13 from 10.36 at% for Ti-CP to 0.80 at% for TiO2. The removal of the formic acid organic linker by TiO2 production is also confirmed by examining the XPS peaks for oxygen (Figure 34). The peak at 532.1 eV is due to the 1s orbitals of organic oxygen, but this peak disappeared in the oxygen spectrum of TiO2. The two main peaks due to oxygen 1s orbitals are located at 530.0 eV and 531.85 eV, respectively. 4+ and O-Ti 3+ It is.

[0370] The Raman spectrum of zirconia nanosheets and the associated fit (reproduced by a set of eight Lorentzian bands corresponding to the most prominent vibrational modes) are shown in Figure 37. The bands appearing at about 195 and about 450 correspond to the A bands of monoclinic zirconium oxide, Zr-Zr and Zr-O. gThis is thought to be due to vibrational modes, while the 180 and 240 cm -1 A broad line consisting of two peaks at 550 cm -1 The most dominant peak located at is assigned to the presence of cubic phase. Thus, the Raman data indicates the coexistence of monoclinic and cubic phases in the zirconia nanosheets.

[0371] The conversion of Zr-Cp to ZrO2 was also investigated by XPS analysis, as shown in Figures 38 and 39. The XPS peaks for carbon 1s orbitals for Zr-CP (bottom) and ZrO2 (top) are shown in Figure 38. The unavoidable peak at 248.8 eV is attributed to C-C bonds, which mainly originate from contaminants adsorbed on the surface of the sample. The peaks at 286.0 and 288.5 eV are related to the C-O-C and O-C-O bonds of formic acetic anhydride bonded to Zr. The total atomic percentage of these two peaks was measured to be 23.14 at% for Zr-CP and reduced to 3.87 at% for ZrO2. It should be noted that the peak at 286.0 eV can be attributed to the presence of CO3 due to surface bonding between the atmospheric CO2 and the surface oxygen of the sample upon exposure to air, and therefore to the atmospheric CO2. This bond is confirmed by the XPS results obtained from the oxygen 1s orbital shown in Figure 39. The organic peak at 532.0 eV in Zr-CP is eliminated in the XPS spectrum for ZrO2. Furthermore, the Zr 4+ The small peak of O-ZrO2 was dramatically increased in ZrO2. 3+ The peak at 531.6 eV, which is attributed to oxygen from adsorbed water, accounts for 27.0 at% of the total oxygen concentration in ZrO2, which clearly indicates that incomplete ZrO2 is formed. It should be noted that the peak located at 533.2 eV is related to oxygen from adsorbed water, as previously reported.

[0372] Example 5: Synthesis of heterostructures Porous CeO 2-xThe applicability of the nanosheets can be expanded by using them as templates in the fabrication of mixed 0D / 2D heterostructures with Fe-, Ni-, and Zn-based transition metal oxides (TMOs) (0D). 2-x The nanosheets were dispersed in an aqueous solution (pH = 6), which gave a relatively stable suspension with a zeta potential of -25 mV (Figure 41), slightly below the threshold of -30 mV for a fully stable colloidal system. In addition, considering the speciation diagram of transition metal (TM) ions (Figure 42), CeO 2-x The predominant species in the acidic pH range of the suspension is TM n+ It is predicted that the lattice constant of the nanosheets is 0.01 to 0.05. This situation therefore establishes electrostatic attraction between the positively charged metal species and the negatively charged porous nanosheets, thereby providing a mechanism for the assembly of metal species at the nanosheet surface. This is supported by the reduced zeta potential of Fe, Ni, and Zn nanostructure suspensions, respectively. This approach may significantly improve the functionality of the nanosheets by preventing layer stacking while minimizing the interfacial vdW interactions and maximizing the accessibility of active sites.

[0373] Moreover, the mixed 0D / 2D heterostructures can provide sufficient hybridization between atomic orbitals, resulting in enhanced carrier delocalization at the junction interface.The elemental, mineralogy, and crystallography studies of the nanostructures were carried out by EDS, laser Raman microspectroscopy, and XRD, as shown in Figure 4.

[0374] EDS mapping of the nanosheets in Figure 4a-c indicates the formation of nanostructures and reveals the uniform distribution of 0D TMO. Furthermore, the TMO and CeO 2-x The coexistence of CeO2 in the pure state was confirmed by laser Raman microspectroscopy (Fig. 4d-f). -1 Therefore, Fe2O3 / Fe3O4-CeO 2-x (FCO), NiO-CeO 2-x (NCO) and ZnO-CeO 2-x (ZCO) approx. 460cm -1The large peak at 2g (attributed to vibration mode) is V O ** These results suggest a red shift to lower wavenumbers consistent with dilatational distortion caused by the -1 The peak located at V O ** This is thought to be due to the defect-induced mode originating from the 230 cm -1 The peaks at 294, 395 and 620 cm are assigned to the A1g vibration mode of α-Fe2O3. -1 The peak at 310(T 2g ), 538(T 2g ) and 680 (A1g). Figure 4e shows the coexistence of NiO (magenta peak) and CeO2 (gray peak). The peaks due to Eg, one-phonon shear optical branch (1T), one-phonon longitudinal optical branch (1L), and two-phonon shear optical branch (2T) vibrational modes of NiO are present at 287, 380, 560, and 690 cm -1 The deconvolution of the ZCO peak in Figure 4f is at 380 cm -1 and 412 cm -1 Two peaks at A of ZnO were revealed. 1T and E 1T It is assigned to the vibration mode of 580cm -1 The peak at is attributed to the E1L vibration mode of ZnO. Similarly, the peaks at 2-x The coexistence of nanosheets was confirmed by XRD analysis, as shown in Figure 4g-i. Further data analysis of the nanostructures is shown in Figure 43.

[0375] CEO 2-xThe photoluminescence (PL) emission of the FCO-based heterojunction structure at room temperature is shown in Figure 46. The intensity of the peak drops to near zero for FCO, indicating minimal electron / hole recombination due to rapid charge carrier separation via very short diffusion paths. The broad emission band located at about 450 nm is caused by surface oxygen vacancies and is the largest in the atomically thin CeO 2-x This confirms the high concentration of oxygen vacancies in the porous nanosheets. The addition of NiO and ZnO significantly reduced the near-band-edge UV emission peak and simultaneously shifted it towards deep level (DL) emission in the green wavenumber range. 2+ and Zn 2+ Localized d-electrons in the band electrons and CeO 2-x This may be due to the sp-d exchange interaction between the nanosheets. Furthermore, the high intensity of PL emission in both NCO and ZCO indicates the increase in defect concentration. The increase in defect concentration is also confirmed by determining the trap sites from the XPS valence band results (Figure 44). For NiO, the green emission band at 560 nm is due to defects in the NiO lattice, such as Schottky pair defects, interstitial oxygen traps, and Ni 2+ Ion and Ni 3+ The small and broad emission peak at 390 nm in ZCO is attributed to the recombination of free excitons via exciton-exciton collision process, which is not significant in any of the heterojunction nanostructures. The weak and broad blue emission band at about 460 nm is deep level emission (DLE) caused by oxygen vacancies or interstitial zinc ions in the ZnO nanomaterials. A broad green emission band at 550 nm was observed in all ZnO nanomaterials, which may be due to the presence of defects such as singly ionized oxygen vacancies.

[0376] Example 6: Controllable disassembly / reassembly of metal coordination polymers to form nanostructures with unique morphologies Ce-CPs exhibit environmental stability during long-term exposure. In contrast, the instability of Ce-CPs in polar solvents leads to their rapid dissociation. Upon controlled removal of the solvent, the ultrafine crystallites of CPs reassemble to form unique nanostructures. This is due to the weak electrostatic bonds between the cations and the organic linkers in the unstable CPs. High latitude is an unconventional CEO. 2-x It provides a basis for the easy and controllable destruction / reconstruction of CP crystallites to form nanostructures. These nanostructures are prepared by varying the processing parameters, including solvent type, solute concentration, temperature (T) and time (t). Subsequent post-oxidation in air or aging in a basic NaOH solution transforms the Ce-CP nanostructures into similar CeO 2-X The feasibility, high yield, and suitability of the disclosed approach, in which CP acts exclusively as a precursor, allows the production of functional CeO nanostructures, despite the fact that CeO is a naturally non-layer-forming material. 2-x It enables large-scale synthesis of nanostructures such as ultrathin nanosheets (see Figures 48u-x) and 2D-3D scaffolds (see Figure 79).

[0377] By tuning the very weak bonds between the metal ion center and the coordination linkers, a variety of metal oxide (MO) structures can be obtained from a single metal coordination polymer precursor. The success of this method is confirmed by the synthesis of new labile cerium-based coordination polymers (Ce-CPs) that can be subjected to controllable decomposition / reassembly in polar solvents (ethanol). This allows the formation of distinct Ce-CP nanostructures by controlling the kinetics of the reassembly process. Post-treatment of the Ce-CP nanostructures by low-temperature pyrolysis and / or time course in alkaline solutions affords the formation of defect-rich 2D and 3D nanostructured forms of CeO. 2-x This method provides a rapid, template-free, precisely controlled, and economical route to synthesize MCPs with specific structures.

[0378] Electrochemical preparation of Ce-CPs CEO 2-xTo synthesize the nanostructures, the Ce-CP precursor was prepared as described herein. A schematic of the synthesis process (Figure 50(a)) shows the growth of free-standing Ce-CP hexagonal rods on a fluorine-doped tin oxide (FTO) substrate. This is illustrated by the SEM image shown in Figure 51. The Ce-CP rods were synthesized in the oxygen evolution region in aqueous solution under anodic electrochemical current. One key factor in the deposition of the Ce-CP precursor was the application of high current density in the oxidizing range of water, such that vigorous oxygen bubbling led to the formation of an oxidizing atmosphere as well as an acidic pH both on and around the working electrode.

[0379] The Ce-CP structure was analyzed for its stability and was found to be fairly stable even when exposed to air for 90 days after deposition as judged from the XRD pattern of the corresponding sample (Figure 52). However, Ce-CP exhibited high instability when exposed to the polar solvent ethanol, which is shown in step 1 of Figure 50(b).

[0380] The simplified molecular structure of the hexagonal Ce-CP rod consists of eight-coordinated cerium ions (Figure 50(c)), with the coordinating oxygen ions linked to trichloroacetic acid acetate (TCA) ligands (four), hydroxyl ions (two), and water molecules (two). In addition, the cerium ions are cross-linked by covalent bonds with the carboxyl groups of the TCA ions, thus forming a two-dimensional (2D) substructure. However, there are weak electrostatic interactions in the interlayer spaces of the 2D Ce-TCA substructures, which lead to the formation of a layered structure (Figure 1A).

[0381] The Ce-CP structure readily decomposes upon exposure to ethanol to form a pale yellow, transparent solution (Figure 50(d), (e)). The high instability of Ce-CP and the resulting rapid decomposition are largely attributed to the retention of Ce ions in the 4+ valence state. From a thermodynamic point of view, Ce 4+ The ion is Ce 3+ The electric field strength is higher compared to that of the Ce ion, as shown in the Pourbaix diagram (Figure 7).4+ Even at acidic pH, the surrounding OH - While there is a strong tendency to attract 3+ tends to remain in the cationic state.

[0382] As discussed herein, the aqueous solution conditions used to prepare Ce-CPs resulted in strongly acidic conditions with a pH of <2.3, which resulted in the formation of Ce(OH)2 2+ was formed as the predominant species. From the associated speciation diagram, it appears that this species is a stable solute at these pH values ​​but becomes unstable at higher values. Furthermore, the Pourbaix diagram (Figure 7) shows that Ce(OH)2 2+ We have shown that Ce(OH)2 exists only in the region of aqueous instability, requiring the application of an external bias and an appropriately low pH for its existence. Application of an external bias causes it to move out of the aqueous stability range, resulting in rapid proton formation and a drop in the local pH. Therefore, under typical aqueous processing conditions used in the present study, Ce(OH)2 2+ No positively charged Ce(OH)2 is formed. 2+ The coexistence of unsaturated coordination bonds in and a negatively charged bidentate TCA as an organic linker leads to the formation of Ce-CPs with a unique layered structure. 4+ The aqueous chemistry of Ce is one in which coordination polymers that cannot be disassembled / reassembled exist. 3+ It is distinct from the aqueous chemistry of

[0383] In the recrystallization of Ce-CP from ethanol, this local bonding arrangement, and therefore Ce 4+ The presence of the Ce-CP is preserved, thereby allowing the reformation of Ce-CP (Fig. 50(f), (g)). The design of the final structure can be tuned by controlling the kinetics of solvent evaporation and the concentration of the Ce-CP solute. This novel technique results in the precise and controllable assembly of nanostructures at room temperature, or even lower, without the use of templates. Therefore, this method can be used to form unique structures that are very difficult to form by existing techniques.

[0384] Formation of a Ce-CP monolayer at the ethanol / air interface to form 2D Ce-CP nanosheets and the resulting porous CeO 2-x There is very limited research on fabricating cerium-based porous nanosheets, and more importantly, such structures with controllable thickness.

[0385] Herein, by imposing conditions of slow kinetics of ethanol evaporation at a low temperature of −10 °C and a vapor pressure (VP) of 0.744 kPa, porous ultrathin CeO films with various thicknesses were fabricated. 2-x Nanosheets were successfully fabricated. Under these conditions, individual Ce-CP layers were formed by virtual Langmuir-Blodgett deposition, as shown in the schematic of a Ce-CP monolayer in Figure 53(a).

[0386] In contrast to the work of Wang et al., which used separate solvents and surfactants, the mechanism shown in Figure 53(b) involves the surface assembly of Ce-CPs at the ethanol / air interface, where ethanol exhibits a dual functionality as both a solvent and surfactant in this bottom-up 2D process. A negatively charged layer consisting of hydrophilic -OH groups of ethanol is established at the surface by the protruding side-by-side positively charged hydrophobic -CH3 groups of ethanol in air. The formation of this layer is due to the fact that the Ce-CPs in solution 4+ thus forming the basis for the development of a cerium-rich electrostatic double layer. 4+ -COO bonded to - Each of the groups contains a negative hydrophobic tail of -CCl3 group, at which the Ce-CP monolayer is terminated. This terminal layer provides the structural and charge neutral requirements for electrostatic binding to the positive -CH3 group of ethanol on the opposing terminal layer of the Ce-CP monolayer. Continued evaporation of the ethanol results in the release of more Ce, regardless of whether the monolayer is permeable or not. 4+ It provides the driving force for the ions to move towards the surface.

[0387] Thus, multiple monolayers can be stacked together to form sheets with a wide range of thicknesses. This is shown in Figure 54, where Ce-CP sheets with various thicknesses ranging from very thin (10 nm) to thick (100 nm) were synthesized during reassembly over a period of 6 to 72 hours. A graph of the thickness variation as a function of evaporation time is shown in Figure 54, which shows a partially linear trend in the controllable production of nanosheets with precisely tuned thicknesses. Furthermore, varying the concentration of Ce-CP as precursor at a constant reassembly time of 48 hours leads to the formation of Ce-CP nanosheets with different thicknesses (Figure 55).

[0388] Figure 53(c) shows an optical image of fragmented Ce-CP nanosheets with lateral sizes of hundreds of microns. Figure 53(d) shows an AFM image of a representative nanosheet taken from the ethanol / air interface after 48 h of ethanol evaporation at -10 °C. The associated height profile shown in the inset of Figure 53(d) reveals a consistent thickness of about 48 nm. TEM and corresponding selected area diffraction (SAED) patterns confirm the presence of Ce-CP nanosheets with polycrystalline structure, as shown in Figure 53(e) and the corresponding inset, respectively. Elemental mapping performed by energy dispersive spectroscopy (EDS) (Figures 53(f)-(k)) indicates that the predominant elements are Ce and Cl. These nanosheets can be easily transferred to glass substrates using van der Waals exfoliation techniques.

[0389] Ce-CP to CeO 2-x The conversion to porous CeO was achieved by aging the Ce-CP nanosheets in a strong basic solution (6 M NaOH) at room temperature followed by heating at 200 °C. As a result, the 2D morphology was retained along with extensive nanopore formation. Figure 56(a) and (b) show the porous CeO 2-x High angle annular dark field (HAADF) image of nanosheets. CeO 2-xThe polycrystalline nature of the nanosheets is confirmed by the SAED pattern in the inset (Fig. 56(b)). A high-resolution TEM (HRTEM) image of the nanosheets (Fig. 56(c)) shows crystallites with sizes ranging from 4 to 8 nm, and intercrystallite pores of 10 nm or less. In addition, strong chemical bonds exist between the single crystallites due to the transverse stripe lattice. Fig. 56(d) shows that the CeO 2-x Ce in 3+ and Ce 4+ Porous CeO suggesting the coexistence of both oxidation states 2-x The XPS spectrum of the nanosheets is shown. As discussed above, 3+ The presence of oxygen vacancies (V) is considered to be the active sites of the catalyst. O ** ) reflects the oxygen vacancies ([V O ** ]) is Ce 3+ The amount of CeO2 in the nanosheets was indirectly quantified from the amount of CeO2, which will be discussed later. Figure 56(e) and (f) show the highly porous CeO2 nanosheets obtained from the Ce-CP nanosheets recovered after 10 h of evaporation. 2-x An AFM image of the nanosheet (e) and the corresponding height profile (f) are shown.

[0390] 3D Ce-CP hollow pseudooctahedron and its derived CeO 2-x The role of evaporation kinetics was investigated by rapidly recrystallizing Ce-CP at room temperature while keeping the concentration unchanged ([Ce-CP] = approx. 8M). Ce-CP can form free-standing Ce-CP pseudo-octahedra. Figure 57(a) shows an SEM image of a free-standing Ce-CP pseudo-octahedra. The pseudo-octahedra with variable c-axis length and terminating in up- and down-pointing pyramids shown in Figure 57(b) are common crystal morphologies for minerals that crystallize in the monoclinic system. The XRD pattern of the Ce-CP octahedra is identical to that of the Ce-CP rods (Figure 58(a)), confirming that the crystal structure remained unchanged and that it was not affected by the decomposition / reassembly process. However, the peaks of the hollow pseudo-octahedra were broadened compared to those of the rods. The difference in full width at half maximum (FWHM) of the XRD patterns may be justified because the crystallite size of the hollow pseudooctahedra is smaller compared to the Ce-CP rods / tubes (Figure 58(b)). As further support, laser Raman microspectroscopy and Fourier transform infrared spectroscopy (FTIR) showed that the chemical structures of the Ce-CP tubes and pseudooctahedra are identical (Figure 58(c), (d)).

[0391] The pseudooctahedrons were transformed into CeO without any morphological changes by time lapse in concentrated NaOH solution at room temperature. 2-x This is shown in Figure 57(d) and (e) by the SEM images and corresponding schematic diagrams, respectively.

[0392] CeO obtained from Ce-CP 2-x The XRD pattern of (Figure 57(f)) was assigned to the cubic fluorite structure of CeO2, space group Fm3m. In general, the conversion of CP to metal oxides occurs when weakly bonded organic linkers are converted to OH in aqueous solution. - and / or H2O. Regarding Ce-CP in aqueous solution, Ce 4+ The relatively high electric field strength of enhances its ability to form Ce(OH)4, which can be easily converted to CeO by drying. 2-x The conversion may be followed by pyrolysis at temperatures above 200° C. As a result, the crystal faces are deformed by the remaining OH -The removal of the CeO and HO molecules results in a concave distortion (Fig. 57(g) and (h)), which leads to improved crystallinity (Fig. 57(i)). 2-x SEM images of the pseudo-octahedrons reveal the presence of holes (indicated by magenta circles in Fig. 57(g)) formed on the structure. This is supported by dark-field HRTEM images (Fig. 57(j), (k)), where a cluster of holes with a size of about 10 nm is identified. The splayed rings in the selected area diffraction (SAED) pattern (inset in Fig. 57(j)) indicate polycrystalline CeO 2-x The BET surface area of ​​the hollow pseudooctahedron is 47.18 m 2 g -1 The pore diameter was measured to be 6.86 nm and the pore volume was measured to be 0.42 cm 3 / g -1 It was.

[0393] The second crucial factor controlling structural reassembly is the Ce-CP concentration. In principle, the concentration of the major ion in solution determines the supersaturation factor (S) according to the following equation:

number

[20] , increasing the Ce-CP concentration is expected to lead to the formation of 3D structures, such as those observed in the case of pseudo-octahedra.

[0394] 3D Ce-CP hollow spheres and their derived CeO 2-x Another determining factor is the ionization (α) of Ce-CP, which represents the amount of dissociation of Ce-CP, and is considered to be approximately 1 due to the complete decomposition of Ce-CP in ethanol.

number

[0395] The proposed mechanism for the formation of the spheroids is based on the swelling of the nanosheets during the evaporation of interlayer ethanol, which is shown diagrammatically in Figure 59(d). To support the proposed mechanism, experimental conditions were designed to accelerate the evaporation, which contributes to the formation of hemispheres prior to spheroid formation and exfoliation. 3D AFM images and corresponding height profiles are shown in Figures 59(e) and (f), respectively. The hemispheres are about 600-700 nm in diameter (about 10-25 nm in height), which is larger than the about 200-400 nm diameter of the spheroids as shown in Figure 60, which may be due to the gradual shrinkage of the former during the formation of the latter.

[0396] Similarly, the Ce-CPs were converted to CeO using NaOH time course and thermal decomposition at 200 °C. 2-x It was converted into a spherical body. CeO 2-xThe hollow spheres had diameters of 200-400 nm and wall thicknesses in the range of approximately 28-0 nm. 2-x SEM images of CeO are shown in Fig. 5a-c, which reveal that the hollow spheres have diameters of 200-400 nm. TEM images in Fig. 60(d) and (e) show that the CeO 2-x The hollow structure of the nanosheets is shown in Fig. 60(c), with the wall thickness of the spheres ranging from about 28 to 40 nm. These thicknesses are estimated to be roughly half the thickness of the original nanosheets. An HRTEM image of an individual hollow sphere (Fig. 60(d)) is shown in Fig. 60(e), where crystallites with exposed crystallographic planes of (111) and (100) were identified. The SAED pattern of the hollow spheres, as shown in Fig. 60(g), was assigned to CeO2, with the rings confirming the polycrystalline structure. Furthermore, Figs. 60(h) and (i) show that the CeO 2-x 1 shows EDS mapping of Ce and O in hollow spheres.

[0397] Figure 60(j) shows the Raman spectrum of Ce-CP and the time course and heating process of CeO 2-x The effect of NaOH on the Ce-CP is shown. After the NaOH time, -1 The peaks were assigned to the F2g vibrational modes of Ce and O. However, the asymmetric nature and red shift of the peaks indicate that the V O ** This is thought to be due to the presence of charge compensation (V O ** After heating at 200 °C, a single narrow peak indicates relatively well-crystallized CeO. 2-x This suggests that residual compression and V O ** The annihilation of -1 4. The graph shows a blue shift (higher value) of the F2g peak located at .

[0398] Overall Ce-CP formation mechanism Tuning of the structure of the nanostructures of the present disclosure and the resulting performance can be accidental due to the use of unstable CPs. The disclosed approach generally provides fast yet tunable disassembly / reassembly kinetics by generating new nanostructures using various solvents at room temperature. For example, immersion of Ce-CP in deionized water results in gradual exfoliation of the Ce-CP as shown by ex situ TEM imaging and the schematic diagram in Figure 1-h. The exfoliation occurs due to the intercalation of water molecules between the terminal Cl ions on the Ce-CP nanosheets. Furthermore, deionized water does not act as a solvent due to the different polarity index. The same results are obtained by applying the same method to Zr-CP and Ti-CP, thus highlighting the universality of the disclosed approach.

[0399] In contrast, weakly polar solvents such as ethanol result in very rapid decomposition / reassembly of Ce-CP. This solubility indicates that Ce-CP has a comparable intermediate polarity as the solvent. The tendency of very fast structural transformation of Ce-CP at room temperature is indicated by the decomposition of tubular Ce-CP nanostructures within 1.5 min and their rapid reassembly in octahedral form during ethanol evaporation. In addition, in situ Raman spectra revealed changes in vibrational modes of structural bonds during the decomposition / reassembly of Ce-CP. The Raman spectrum after 360 s did not show any trace of ethanol, confirming that ethanol only formed a medium for the decomposition and reassembly of Ce-CP nanostructures. Such behavior was also observed in MOF-5 nanostructures, where different experimental conditions led to various ZnO nanostructures.

[0400] The decomposition kinetics of unstable CPs may be influenced by (i) high cationic valency and the associated high electric field strength that favors hydroxide formation at high pH, ​​(ii) the tendency of the linker to be protonated in aqueous media at low pH, thereby replacing the linker with a hydroxyl group, (iii) linkers with low molecular symmetry (monodentate, bidentate, etc.), and (iv) the polarity match between the solute and the solvent. In the case of Ce-CPs, Ce 4+has a relatively strong electric field strength that favors the formation of bonds with hydroxyl groups over bonds with monodentate trichloroacetate (TCA) linkers, effectively destabilizing any Ce-TCA bonds. The solvents that exhibit the fastest kinetics are those with polarity indices in the range of 4.3-5.9, indicating that the polarity index of Ce-CP falls in this intermediate range. Furthermore, the reassembly kinetics of the new nanostructures is primarily determined by the partial pressure of the solvent, which can be manipulated by temperature and chemical potential. For example, hollow octahedra are formed when ethanol is rapidly evaporated at room temperature, whereas hollow spheres are formed when the evaporation is carried out at 0°C.

[0401] Figure 61 shows the various nanostructures obtained as a function of [Ce-CP], with Fig. 4(ad) showing the Ce-CP nanostructures and Fig. 59(e-h) showing the CeO nanostructures obtained by NaOH aging and heating at 200 °C. 2-x The Ce-CP and therefore CeO as a function of increasing [Ce-CP]. 2-x The structural evolution of follows the order of nanosheets, hollow spheres, hollow pseudooctahedrons, hollow elongated octahedrons, and dense foils.

[0402] The model of stacking of multiple flat nanosheets presented in Fig. 53 is supported by the presence of ridges, which are evident in Fig. 61(f), (g) and faintly visible in Fig. 61(h) and Fig. 55. Ultimately, the collision of the elongated octahedral morphology shown in Fig. 61(g) results in the formation of the dense foil morphology shown in Fig. 61(h). This dense state arises due to the larger [Ce] and the resulting reduced diffusion distance. All the nanostructures in Fig. 61 were produced at low temperature (25 °C) and therefore the driving force for diffusion was low. This favored the formation of polycrystalline structures over single crystals. Consequently, the flexibility to generate various nanostructures suggests structural changes due to phase transformations with low-energy displacements rather than high-energy reconstructions.

[0403] CEO 2-xFurther morphological analysis of is shown in Figure 62. In Figure 62(h), a large amount of single crystal CeO 2-x The identification of pyramids, combined with the presence of ridges on the pseudooctahedra, suggests that these morphologies were generated from interlocking hemispheres still attached to nanosheets along their diameter (Figure 61(a)). It can be proposed that the process occurs through the formation of ridges from the fractured surfaces of the flexible Ce-CP monolayer, with the early formation of crystal faces by flattening of the rounded hemispheres. As suggested in Figure 61(a), pyramids form before detachment from the nanosheets due to the presence of the largest diametral stress at the circle of greatest sheet misalignment. Although complete delamination would have formed the individual pyramids, nanosheets and elongated octahedra form by different mechanisms. These structures may have been generated by chemical gradient fluctuations induced by periodic evaporation and replenishment of ethanol while the two hemispheres remained in close proximity. This view is supported by closer visual inspection of Figure 61(g), in that the central ridge of the elongated octahedron is the most discordant, suggesting closure of two interlocking pyramids during the final stages of evaporation-condensation.

[0404] The general mechanism of formation of the microstructure is shown in Figure 63. Recrystallization of the aggregates from an electrolyte containing both constituent cations and anions is governed by the above equation. 2It is known that the rate of recrystallization depends on the ionization (α) and supersaturation factor (S), which are expressed as: α = 0.5; α = 1.5; ... When the α-factor increases upon evaporation at room temperature, the increase in S leads to a change in the 3D structure, in the progressive order: hollow spheres, hollow pseudooctahedrons, hollow elongated pseudooctahedrons, and finally solid foils.

[0405] Overall, the metal-based CP (MCP) processing approach represents a simple, cost-effective, template-free, low-temperature (below 25 °C) method for the fabrication of metal oxides with unprecedented structures. The approach involves the oxidation of cerium-based MCPs, which allows for their rapid disassembly / reassembly in the polar solvent ethanol, thus affording well-defined porous 2D and hollow 3D CeO with high functionality. 2-x Nanostructures are obtained: Porous 2D metal oxides with precisely controlled thicknesses were achieved by manipulating the nucleation / growth kinetics of MCPs.

[0406] Example 7: Photocatalytic activity of nanostructures Photocatalytic parameters CEO 2-xTo investigate the photocatalytic parameters of the CeO and mixed nanostructures, the corresponding electronic band structures were constructed. Therefore, the gap between the valence band (VB, orange line) and the Fermi level (Ef, black dashed line), the optical indirect transition band gap (Eg) and the work function (Φ) were determined using XPS, UV-visible spectrophotometry, and amplitude modulation Kelvin probe force microscopy (AM-KPFM). The AFM image in Figure 5a shows the CeO 2-x The reference for the KPFM results is shown in Fig. 1. Silicon substrate (higher potential) and 1.2 nm thick CeO 2-x There is a large potential difference of 90 mV (0.09 eV) between the nanosheet (lower potential) and the Pt / In coated silicon tip. Φ was measured to be 4.74 eV (similar to that reported previously), so by subtracting 0.09 eV, we can determine the potential difference between the CeO 2-x The Φ of 4.65 eV is obtained. The existence of trap states in the band gap is also shown for CeO. 2-x The XPS plot of the valence band of Fe2O3 / Fe3O4-CeO is shown in Figure 5c. Additionally, the Tauc plot of Eg is shown in Figure 5d. These data, as well as the Fe2O3 / Fe3O4-CeO 2-x The data for the nanostructure (FCO), NCO and ZCO (Figures 44 and 45) were used to construct the electronic energy level diagram shown in Figure 5e.

[0407] The above shows that these porous 2D nanostructures offer the dual advantages of rapid charge-carrier diffusion and a significant reduction in E from 3.36 eV to 2.89 eV. O ** and V Ce ”” There exists a potential where the influence of mid-gap trap states (Figure 5c) associated with the presence of CeO comes into play, although the location of the corresponding energy levels does not appear to be fixed. Figure 5e shows that the photocatalytic performance for a particular chemical reaction can be engineered by modifying the electronic band structure through nanostructuring. For example, Figure 5e shows that FCO lowers Eg to 2.50 eV, while CeO 2-x The CB (green line) is higher than that of Fe2O3 / Fe3O4 and O2 / ·O2 -The reduction in the band gap significantly increases the optical absorption, and the O2 / O2 - Significantly enhance the new CB position of FCO near the CeO 2-x The alignment of the VB and CB bands also suggests that charge transfer of both electrons and holes occurs toward Fe2O3 / Fe3O4, thus enhancing charge recombination. However, the electron / hole recombination in the mixed 0D / 2D heterostructures is enhanced toward CeO 2-x The reduction in the charge transport rate compared to the nanosheets was confirmed by PL spectroscopy (Figure 46). These data suggest that charge transfer dominates over electron / hole recombination due to the short diffusion paths in the nanosheets.

[0408] XPS analysis of the NCO and ZCO nanostructures (Figure 44) also indicated the formation of trap states. The band gaps of NCO and ZCO increased (Figure 5e), but the CB of NCO and the VB of both NCO and ZCO were O2 / ·O2, respectively. - and OH / HO reactions, thereby enhancing the formation of ROS, respectively. Furthermore, both VB and CB are suitably positioned to catalyze the CeO 2-x The charge separation was reduced compared to that of TMO and CeO. 2-x This suggests that the problem may be improved by hole diffusion to the

[0409] To further evaluate the difference in electronic band structure between CeO2 nanosheets, bulk CeO2, and 0D / 2D heterostructures, first-principles calculations based on DFT were performed. Figure 5f shows that the band gap of CeO2 nanosheets is reduced by about 10% compared to that of bulk CeO2, which is in excellent agreement with the experimental results (Figure 5d). Upon adsorption of transition metal ions, a significant shift in the band structure of CeO2 nanosheets is observed (Figures 5g-i) in the form of new electronic states that appear within the band gap and in one case at the bottom of the conduction band (Figure 5g); the band gap is in good agreement with the experimental data (Figure 5e). The origin of such band structure difference is supported by the difference in the calculated transition metal adsorption energies, which are -10.8 eV (Fe), -3.8 eV (Ni), and -0.1 eV (Zn). Larger charge transfer typically correlates with more favorable adsorption energies, and therefore the different attractive electrostatic interactions lead to large differences in the amount of charge that transition metal ions transfer to the nanosheets (approximately 2e per Fe ion). - , about 1e per Ni - , and approximately 0 e per Zn - ) These variations suggest the possibility of extensive band tuning by forming 0D / 2D heterostructures with different ions.

[0410] CeO based heterojunction structure 2-x The room temperature photoluminescence (PL) emission of FCO is shown in Figure 46. The intensity of the peak drops to near zero, indicating minimal electron / hole recombination due to rapid charge carrier separation via very short diffusion paths. The broad emission band located at about 450 nm is caused by surface oxygen vacancies and is seen in the atomically thin CeO 2-x This confirms the high concentration of oxygen vacancies in the porous nanosheets. The addition of NiO and ZnO significantly reduced the near-band-edge UV emission peak and simultaneously shifted it towards deep level (DL) emission in the green wavenumber range. 2+ and Zn 2+ Localized d-electrons in the band electrons and CeO 2-xThis may be due to the sp-d exchange interaction between the nanosheets. Furthermore, the high intensity of PL emission in both NCO and ZCO indicates the increase in defect concentration. The increase in defect concentration is also confirmed by determining the trap sites from the XPS valence band results (Figure 44). For NiO, the green emission band at 560 nm is due to defects in the NiO lattice, such as Schottky pair defects, interstitial oxygen traps, and Ni 2+ Ion and Ni 3+ The small and broad emission peak at 390 nm in ZCO is attributed to the recombination of free excitons via exciton-exciton collision process, which is not significant in any of the heterojunction nanostructures. The weak and broad blue emission band at about 460 nm is deep level emission (DLE) caused by oxygen vacancies or interstitial zinc ions in the ZnO nanomaterials. A broad green emission band at 550 nm was observed in all ZnO nanomaterials, which may be due to the presence of defects such as singly ionized oxygen vacancies.

[0411] CEO 2-x The functionality of nanostructures depends on their defect content.

number

number

number

number

number

number

number

[0412] Catalyst performance The photocatalytic performance of the samples was evaluated under sunlight irradiation by the decomposition analysis of methylene blue (MB) compound, which is widely used for photocatalytic analysis. -1 The gradual decrease in the intensity of the MB absorbance peak centered at was measured. 2-x The nanosheets exhibit a high degree of dye degradation of 85% after 2 h (Figure 47), while the reaction kinetics is 0.024 min−1, which corresponds to the fastest reported dye degradation by pure CeO2. -1 The results reveal high kinetic constants (k) (Table 4). The 0D / 2D heterostructure performed even better, with FCO, NCO and ZCO reaching 100%, 94% and 90% extents after 2 h, respectively, with correspondingly higher kinetic constants. High stability of the samples was observed after photocatalysis testing.

[0413] Figure 47(a) shows the absorption spectra corresponding to the mixed nanosheets and MB solution as a function of irradiation time. The substantial decrease in the absorption peak in the first 40 min is an indication of the rapid chemical decomposition of MB, followed by the near loss of the peak after 2 h. Using a pseudo-first-order reaction model, A t Let A be the dye absorption at time (t) and A be the dye absorbance before irradiation. tThe photodegradation kinetics was explored by plotting the photochemical degradation (A / A0) versus irradiation time. In addition, Figure 47(c) shows a graph comparing the dye degradation performance of the porous nanosheets synthesized in this study with the selected best performances reported previously. The experimental conditions of the study are summarized in Table 4. Furthermore, FCO with a band gap in the visible light region exhibits a remarkable enhancement in dye degradation performance with nearly 100% degradation after 2 hours (Figure 47(d)).

[0414] The performance of nanosheets can be attributed to two mechanisms: 1) a high density of structural defects that modify the electronic properties of nanosheets by narrowing the band gap. The atomic layers of nanosheets provide a high surface-to-volume ratio, which considerably enhances the exposed crystalline planes at the dye-nanosheet interface region. 2) This performance has been shown to be significantly improved by the fabrication of mixed heterojunction nanostructures that minimize the density of electron / hole recombination, introducing a large number of defects that act as active sites, thereby resulting in a large number of ROS in solution to catalyze dye degradation. [Table 5]

[0415] Furthermore, the CEO 2-x The complete CO oxidation at about 150 °C by the 2D-3D scaffold and its reduction to about 90 °C by modification as a CeO2-based hybrid leads to the lowest temperature yet reported for CO oxidation (see Table 5). [Table 6]

[0416] Various CeO 2-x Catalytic performance of morphology Various CeO 2-xThe catalytic performance of the nanostructures was compared by testing their activity in CO oxidation. The results in Figure 64 show that the CO conversion rate decreases in the order ultrathin sheets > pseudooctahedra > spheres > foils. For example, at 400 °C, these values ​​are 21.1, 12.8, 1.93, and 0.0 mol g, respectively. -1 s -1 At this temperature, the turnover frequency (TOF) values ​​calculated for each catalyst based on the CO molar ratio were 2 ·g -1 , pore volume = 0.32 cm 3 g -1 ) is 4.4 × 10 -3 Mol Mol -1 s -1 This shows that the highest TOF value was obtained for a pseudo-octahedron (surface area = 47 m 2 ·g -1 , pore volume = 0.42 cm 3 g -1 ), which is 1.5 times higher than the value for a sphere (surface area = 53 m). 2 ·g -1 , pore volume = 0.15 cm 3 g -1 ) and the surface area of ​​foil (surface area = 6 m 2 ·g -1 , pore volume ≒ 0 cm 3 g -1 ) is almost 50 times the value of the surface area. These results confirm that the combination of surface and pore volume reflects the density of active sites consisting of unsaturated coordinate bonds that enhance CO adsorption. Furthermore, it is important that the nanostructures are polycrystalline, since V O ** is shown to be present in high concentrations.

[0417] The activation energies (E aThe catalytic kinetics were also evaluated by Arrhenius plots to determine the [V] of the CeO2 samples. As expected, these follow the same relative order as the CO conversion rates, with the TOF increasing from 47 < 58 < 115 < 134 kJ / mol for ultrathin sheets, pseudooctahedra, spheres, and foils, respectively. The high [V O ** It is important to note that ] plays an important role in the catalytic activity by facilitating CO adsorption and accelerating the mobility of lattice oxygen to enhance CO2 desorption.

[0418] The CeO prepared herein 2-x The photocatalytic performance of the form was measured at an illumination intensity of 100 mW / cm 2 The photolysis of MB during solar irradiation of AM1.5G at 664 cm -1 The maximum intensity of the absorbance peak of was used as the basis for comparison and the data are shown in Figure 67(a). Figure 67(b) reveals that there are three performance levels for dye degradation: high (84% porous nanosheets), medium (55% pseudooctahedrons and 40% spheres), and low (16% foils). These data are consistent with CO oxidation and suggest a major role for surface area and pore volume in catalysis.

[0419] The absorbance at time t (A t The degradation kinetics by the porous nanosheets, converted into the ratio of 0.003 min−1 to 0.005 min−1 and plotted against irradiation time, is shown in Figure 67(c). The only other published value obtained under similar test conditions, i.e., 0.003 min−1 -1 and 0.012 min -1 The decomposition rate constant (k), which can be compared to 0.014 min -1 It was determined that pure CeO 2-x The high efficiency observed for Ru3Al is believed to be due to two main factors. First, the porous thin nanostructures provided high accessibility of charge carriers to the active sites due to the short diffusion distance from the bulk to the surface. This desirable property was due to the

[42] and Ni(OH)

[43] This resulted in a decrease in the charge carrier recombination time, as previously reported for catalysts such as porous nanosheets of ZnO, which exhibited enhanced hydrogen and oxygen evolution reactions (HER and OER, respectively). Second, the XPS data identified [V O ** ] (Figure 65) reveals a high area density of active sites.

[0420] FIG. 67(d) shows various pure and hybrid CeO with variable sizes. 2-x The results show that the porous nanosheet morphology is superior in terms of the degree of degradation. Furthermore, the analysis shows that the various CeO2 morphologies with crystallite sizes below 20 nm exhibit a range of degradation rates from 2 to 65 nm. 2 ·g -1 The results show that the BET specific surface area of ​​the zeolites ranges from 4 to 8 nm, and the degree of photolysis ranges from about 4 to 70%. 2 ·g -1 This can be contrasted with the values ​​for the porous nanosheet morphology, which exhibited a specific surface area of ​​100 nm and an outstanding photodegradation performance of 77%. 2-x This is the best performance yet reported for a catalyst. Comparing the data in this study, it stands out that the effect of accessible active sites dominates, as is most clearly manifested by the combination of specific surface area and pore volume, which are predictors of performance.

[0421] Structure, defect equilibrium and nanostructures of CeO 2-x The effect of SiO on the catalytic and photocatalytic performance is summarized in Figure 68, which shows the effect of the oxygen vacancy concentration ([V O ** ]), specific surface area, and pore volume. These data indicate the CO conversion rate, turnover frequency, and required activation energy (E a) and photolysis are compared. These data showed that the main factor controlling the performance was the specific surface area, which reflects the density of active sites. Table 6 shows the comparative data between this study and other comparable studies, again confirming the dominant effect of surface area. However, the inconsistent trend between pseudooctahedra and spheres indicates that this parameter is moderated by the influence of oxygen vacancy concentration and pore volume. Finally, there is no direct correlation between morphology and oxygen vacancy concentration, which is concentrated in the crystallites and grain boundaries. Such a correlation is not possible for single crystal CeO 2-x Although this has been previously observed in , the discrepancy with the present study highlights the effect of the polycrystalline nature of these structures.

[0422] Overall, the porous 2D CeO 2-x The nanostructures exhibited outstanding photocatalytic performance, which can be attributed to the short charge carrier diffusion paths and low recombination density resulting from the thin, porous, polycrystalline nanosheets containing a high concentration of active sites.

[0423] Example 8: Metal sulfide-based nanostructures Ce-CP is a hybrid CeO 2-x It can be used as a precursor for forming a system macrolayer (Ce / S / C).

[0424] The transformation of Ce-CP to Ce / S / C was structurally studied using XRD and Raman analysis, and the results are shown in Figure 70. The XRD data confirm that the decomposition / reassembly of Ce-CP using DMSO preserves the triclinic structure of the pure Ce-CP. Annealing of the reassembled Ce-CP in air and N2 atmospheres resulted in oxidation to the CeO2 fluorite structure. The Raman spectra obtained for Ce-CP and DMSO-derived Ce-CP (Figure 70b) reveal that the A of SO4 in the Ce sulfate structure is g 1040cm, which is thought to be due to a vibration mode -1 In contrast, the major peak at 450 cm -1 and 470cm -1As suggested by the decrease in intensity of the neighboring peaks at - The number density of bonds with the groups was significantly reduced after reassembly.

[0425] Annealing the DMSO-derived Ce-CP in air and N2 atmospheres gave CeO2 with carbon incorporated into the structure. -1 and 1600cm -1 The two peaks at 457 cm−1 are the D and G modes, which confirm the presence of graphitic carbon. It is important to note that the F2g mode, which is due to the stretching vibration between Ce and O in CeO2, appears in both the air and N2 spectra. However, in the CeO2 obtained in air, this peak appears at a lower value (457 cm−1). -1 ) which may be due to the presence of the E1g vibration mode of the SO4 group in the Ce sulfate structure. The Raman spectrum of the sample calcined in air also showed a shift to 1057 cm, which is believed to be due to SO4. -1 These results indicate that the formation of hybrid CeO2-based carbon and sulfur heterostructures involves a two-step process of reassembly and post-oxidation.

[0426] Further analysis by XPS surface characterization is shown in Figure 71. Variation of Cl concentration is shown in Figure 71a, where the intensity of Cl 2p orbitals remains unchanged in Ce-CP and DMSO-derived Ce-CP, while calcination in both air and N2 resulted in almost complete removal. In Figure 71b, XPS analysis of C 1s orbitals revealed similar differences in that Ce-CP and DMSO-derived Ce-CP exhibited C-O-C bonds (286 eV) and O-C=O bonds (289 eV), the former of which was increased by the introduction of DMSO into the structure. Calcination of DMSO-derived Ce-CP almost eliminated the less stable O=C bonds, but a small amount of such bonds remained, albeit shifted to higher bond energies due to the increased covalent nature of C-C bonds once the more electronegative Cl groups were removed. The presence of a dominant 286 eV peak may suggest the formation of a graphitic structure. Calcination in N2 revealed higher peak intensities, suggesting the formation of higher graphitic carbon concentrations compared to those obtained in air.

[0427] This is confirmed by the XPS analysis of the S 2p orbitals shown in Figure 71c. 3 / 2 The use of DMSO solvent led to the formation of Ce sulfate, as confirmed by the peak. This peak is not inconsistent with that reported for cerium sulfate (Ce(SO4)2), where the oxidation state of sulfur is +6. The structure of Ce(SO4)2 remained unchanged during calcination in air. On the other hand, calcination in N2 led to the appearance of a peak centered at a lower energy of 164 eV, which can be attributed to sulfur with an oxidation state of +4, suggesting the formation of CeO2 / SO2.

[0428] Simultaneous occurrence of S under N2 6+ From S 4+ Reduction to Ce 3+ From Ce 4+ The oxidation to is an electron exchange reaction: S 6+ +2Ce 3+ →S 4+ +2Ce 4+ This suggests the possibility of IVCT via N2. The feasibility of IVCT is supported by the XPS data, as shown in Fig. 72a, b. However, the corresponding XPS data does not show that this reaction occurs after calcination in air. Therefore, under N2, S 6+ From S 4+ It is possible to reduce it to Ce 3+ From Ce 4+ The simple oxidation of S to S facilitates IVCT as a means of charge transfer between CeO2 and the sulfate structure. 7+ The absence of a valence state of S 8+ The oxidation to Ce is effectively prevented, and therefore 3+ Ce via IVCT 4+ The latter is supported in Fig. 72a, b. The above results indicate that calcination with N2 results in the formation of a CeO2 / graphitic oxygen / Ce sulfate heterojunction structure.

[0429] The concentration of structural defects associated with the new heterojunction Ce / S / C and pure CeO2 was evaluated using EPR and the data are shown in Figure 73. The hyperfine pattern in Figure 73a shows that seven types of defects are present in the heterostructure compared to pure CeO2, and the area in Figure 73b shows that there is a much higher concentration of total defects.

[0430] It will be appreciated by those skilled in the art that many changes and / or modifications may be made to the invention as illustrated in the specific embodiments without departing from the spirit and scope of the invention as broadly described, and the present embodiments are therefore to be considered in all respects as illustrative and not restrictive.

[0431] All publications discussed and / or referenced herein are hereby incorporated by reference in their entirety.

[0432] Any discussion of documents, acts, materials, devices, articles or the like which has been included in the specification is solely for the purpose of providing a context for the present invention, and its existence prior to the priority date of each claim of this application should not be construed as an admission that any or all of such matter formed part of the prior art or was common general knowledge in the relevant field of the invention. (Additional Note) (Appendix 1) A layered metal coordination polymer comprising two or more layers, Each layer comprises a metal atom coordinated to an organic linker to form a metal coordination polymer layer; wherein the organic linker is represented by Formula 1: XR 1 (1) and wherein the compound is selected from one or more compounds having the structure During the ceremony: X is a metal binding moiety for coordinating to a metal atom; and R 1 is H or an optionally interrupted alkyl, alkenyl or alkynyl group substituted with one or more moieties that form electrostatic interactions with adjacent metal coordination polymer layers to form said layered metal coordination polymer. (Appendix 2) 1. A layered metal coordination polymer that is the reaction product of an organic linker and a source of metal atoms, the layered metal coordination polymer comprises two or more layers, each layer comprising a metal atom each coordinated to one or more organic linkers to form a metal coordination polymer layer; wherein the organic linker is represented by Formula 1: XR 1 (1) The compound is selected from compounds having the structure During the ceremony: X is a metal binding moiety for coordinating to a metal ion; and R 1is H or an optionally interrupted alkyl, alkenyl or alkynyl group substituted with one or more moieties that form electrostatic interactions with adjacent metal coordination polymer layers to form said layered metal coordination polymer. (Appendix 3) The layered metal coordination polymer is formed by forming the layered metal coordination polymer, and each R of the organic linker of each metal coordination polymer layer is 1 a plurality of metal coordination polymer layers interspersed therebetween that form said electrostatic interactions between said one or more moieties of said optionally interrupted alkyl, alkenyl or alkynyl groups of Rayville 3. The layered metal coordination polymer of claim 1 or 2, comprising an ion. (Appendix 4) R 1 is dispersed between the metal coordination polymer layers. Rayville 4. The layered metal coordination polymer of claim 3, wherein the alkyl, alkenyl or alkynyl group is optionally interrupted and terminated with one or more moieties for forming electrostatic interactions with ions to form said layered metal coordination polymer. (Appendix 5) The above Rayville The ions are each R of the organic linker of each metal coordination polymer layer. 1 5. The layered metal coordination polymer of claim 3 or 4, wherein the charge of said one or more terminal portions of said optionally interrupted alkyl, alkenyl, or alkynyl groups is opposite to that of said one or more terminal portions of said optionally interrupted alkyl, alkenyl, or alkynyl groups. (Appendix 6) The above Rayville ions and each R of the organic linker of each metal coordination polymer layer. 1 wherein the electrostatic interaction between the one or more terminal portions of the optionally interrupted alkyl, alkenyl, or alkynyl groups is substantially orthogonal to the coordination bonds within the metal coordination polymer layer. (Appendix 7) 7. The layered metal coordination polymer according to any one of claims 1 to 6, wherein the layered metal coordination polymer has a zeta potential greater than zero (0) mV. (Appendix 8) 8. The layered metal coordination polymer according to any one of claims 1 to 7, wherein the layered metal coordination polymer has a zeta potential of about 10 mV to about 60 mV. (Appendix 9) Each R of the organic linker 1 C, optionally interrupted by one or more O, N, S, Se, Te, Si, aryl, heteroaryl, and / or cycloalkyl. 1-10 9. The layered metal coordination polymer according to any one of claims 1 to 8, wherein the group is an alkyl group. (Appendix 10) Each R of the organic linker 1 wherein the alkyl group is optionally interrupted by one or more O, N, S, Se, Te, Si, aryl, heteroaryl, and / or cycloalkyl. 1-6 10. The layered metal coordination polymer according to any one of claims 1 to 9, wherein the group is an alkyl group. (Appendix 11) Each R of the organic linker 1 wherein the one or more moieties of the optionally interrupted alkyl, alkenyl, or alkynyl groups comprise one or more halogens selected from the group consisting of F, Cl, Br, and / or I, or one or more halides selected from the group consisting of Li, Na, K, Rb, and / or Cs. (Appendix 12) 12. The layered metal coordination polymer according to any one of claims 1 to 11, wherein the metal binding moiety (X) is a monodentate, bidentate or polydentate ligand. (Appendix 13) 13. The layered metal coordination polymer according to any one of claims 1 to 12, wherein the metal binding moiety (X) is a monodentate or bidentate ligand. (Appendix 14) 14. The layered metal coordination polymer according to any one of claims 1 to 13, wherein the metal binding moiety (X) is a monodentate or bidentate ligand that forms a bridging coordination bond with two or more metal atoms to form the metal coordination polymer layer. (Appendix 15) 15. The layered metal coordination polymer according to any one of claims 1 to 14, wherein the metal binding moiety (X) includes a carboxylate, an amine, a hydroxyl, a thiol, and a nitrile. (Appendix 16) 16. The layered metal coordination polymer according to any one of claims 1 to 15, wherein the metal binding moiety (X) comprises a carboxylate. (Appendix 17) The layered metal coordination polymer according to any one of claims 1 to 16, wherein the organic linker is formic acid, trifluoroacetic acid, trichloroacetic acid, tribromoacetic acid, or triiodoacetic acid. (Appendix 18) 18. The layered metal coordination polymer according to any one of claims 1 to 17, wherein the metal atom is selected from one or more of rare earth metals, transition metals, and metals of Group 13, Group 14, or Group 15 of the periodic table. (Appendix 19) 19. The layered metal coordination polymer according to any one of claims 1 to 18, wherein the metal atom is a metal ion. (Appendix 20) 20. The layered metal coordination polymer of claim 19, wherein the metal ion is monovalent or polyvalent. (Appendix 21) 21. The layered metal coordination polymer of claim 20, wherein the metal ion is monovalent or polyvalent and is one or more metals selected from rare earth metals, transition metals, Group 13, Group 14, or Group 15 metals of the periodic table. (Appendix 22) The metal ion is Ce 3+ , Ce 4+ , Ti 4+ , Zr + or Zn + 22. The layered metal coordination polymer according to claim 20 or 21, (Appendix 23) 23. The layered metal coordination polymer of any one of claims 1 to 22, wherein the metal coordination polymer is a cerium metal coordination polymer having the formula Ce(TCA)2(OH)2·2H2O. (Appendix 24) 24. The layered metal coordination polymer of claim 23, wherein the cerium metal coordination polymer is characterized by an X-ray powder diffraction (XRD) pattern comprising one or more major peaks located at about 7.2, 8.1, 10.9, 20.6, 22.0, 23.1, and 23.2 degrees (2θ). (Appendix 25) 25. The layered metal coordination polymer of any one of claims 1 to 24, wherein each metal coordination polymer layer can independently have an axial thickness along the c-axis of about 11.0 nm, 5.5 nm, 2.2 nm, or 1.1 nm. (Appendix 26) 26. The layered metal coordination polymer according to any one of claims 1 to 25, wherein the layered metal coordination polymer is polycrystalline. (Appendix 27) A process for preparing a layered metal coordination polymer comprising two or more metal coordination polymer layers, as defined in any one of claims 1 to 26, comprising: Combining a metal atom source and an organic linker to form a layered metal coordination polymer comprising two or more metal coordination polymer layers held together by electrostatic interactions. The process comprising: (Appendix 28) 28. The process of claim 27, wherein the step of combining the metal atom source and the organic linker comprises mixing an aqueous solution comprising the metal atom source and the organic linker to form a layered metal coordination polymer comprising two or more metal coordination polymer layers held together by electrostatic interactions. (Appendix 29) 29. The process of claim 27 or 28, wherein the step of forming the layered metal coordination polymer comprises hydrothermal treatment or electrodeposition. (Appendix 30) 30. The process of claim 29, wherein the electrodeposition is modified anodic chronoamperometric electrodeposition (MACE). (Appendix 31) 31. The process of claim 29 or 30, wherein the initial pH of the aqueous solution during electrodeposition is less than about 7. (Appendix 32) 32. The process of claim 29 or 31, wherein the initial pH of the aqueous solution during electrodeposition is from about pH 2 to about pH 7. (Appendix 33) 33. The process according to any one of claims 28 to 32, wherein the concentrations of the metal atom source and the organic linker in the aqueous solution are each independently from about 0.001 M to about 1 M. (Appendix 33) 33. The process of any one of claims 29 to 32, wherein the electrodeposition is carried out in an oxygen generating region of the aqueous solution comprising the metal atom source and the organic linker. (Appendix 34) 34. The process of any one of claims 29 to 33, wherein the electrodeposition is carried out with a constant applied voltage effective to maintain the oxygen evolving region of the aqueous solution comprising the metal atom source and the organic linker. (Appendix 35) 35. The process of claim 34, wherein the electrodeposition is carried out with a constant applied voltage of 1 mV to 10 V vs. Ag / AgCl. (Appendix 36) 36. The process according to any one of appendixes 29 to 35, wherein the electrodeposition is carried out at a temperature of about 0° C. to about 100° C. for a period of about 1 minute to about 90 minutes. (Appendix 37) The electrodeposition may include one or more metal coordination polymer layers interspersed between the metal coordination polymer layers. Rayville Ions are generated to each R of the organic linker of each metal coordination polymer layer. 1 forming said electrostatic interactions between said one or more moieties of optionally interrupted alkyl groups to form said layered metal coordination polymer. (Appendix 38) 38. The process of any one of claims 27 to 37, wherein the layered metal coordination polymer is decomposed in an organic solvent and reconstituted from the organic solvent by evaporation. (Appendix 39) The process according to claim 38, wherein the concentration of the metal coordination polymer decomposed in the organic solvent is preferably about 4 M to about 120 M. (Appendix 40) 40. The process of claim 38 or 39, wherein the evaporation of the organic solvent is carried out at a temperature of about -20°C to about 40°C and a vapor pressure of about 0.1 kPa to about 10 kPa. (Appendix 41) 40. The process of any one of claims 27 to 39, wherein the layered metal coordination polymer is exfoliated to provide one or more metal coordination polymer layers. (Appendix 42) The layered metal coordination polymer is peeled off, and the metal coordination polymer particles interspersed between the metal coordination polymer layers are peeled off. Rayville By removing ions, each R of the organic linker of each metal coordination polymer layer is 1 42. The process of claim 41, comprising disrupting the electrostatic interactions between the one or more moieties of the optionally interrupted alkyl group to obtain one or more metal coordination polymer layers. (Appendix 43) 43. The process of claim 41 or 42, wherein exfoliating the layered metal coordination polymer comprises dispersing and agitating the layered metal coordination polymer in water or an organic solvent to exfoliate the layered metal coordination polymer to obtain one or more metal coordination polymer layers. (Appendix 44) 44. The process of claim 43, wherein the layered metal coordination polymer is stirred at room temperature. (Appendix 45) 45. The process of claim 43 or 44, wherein the layered metal coordination polymer is agitated by sonication for a period of time effective to exfoliate the layered metal coordination polymer to yield one or more metal coordination polymer layers. (Appendix 46) 46. ​​The process of claim 45, wherein the layered metal coordination polymer is agitated by sonication for a period of about 1 minute to 72 hours, or 1 minute to 20 minutes, to exfoliate the layered metal coordination polymer to obtain one or more metal coordination polymer layers. (Appendix 47) 1. A method for forming a nanostructure, comprising: providing a layered metal coordination polymer comprising two or more layers, each layer comprising a metal atom each coordinated to one or more organic linkers to form the metal coordination polymer; and removing at least a portion of said coordinating organic linkers to form said nanostructures; The method comprising: (Appendix 48) 48. The method of claim 47, wherein removing at least a portion of the coordinating organic linkers to form the nanostructure comprises aging the layered metal coordination polymer. (Appendix 49) 49. The method of claim 48, wherein aging the layered metal coordination polymer comprises heating the metal coordination polymer. (Appendix 50) 49. The method of claim 47 or 48, wherein removing at least a portion of the coordinating organic linker to form the nanostructure comprises aging a solution comprising the layered metal coordination polymer at a basic pH. (Appendix 51) 51. The method of claim 50, wherein aging the solution comprising the layered metal coordination polymer is at a pH between about pH 7 and about pH 10. (Appendix 52) 52. The method of claim 50 or 51, wherein aging the solution containing the layered metal coordination polymer is for a period of time ranging from about 1 minute to about 2 days. (Appendix 53) 53. The method of any one of appendix 50 to 52, wherein aging the solution is at a temperature of about 10°C to about 50°C. (Appendix 54) 54. The method of any one of claims 50 to 53, wherein at least a portion of the coordinating organic linker is removed to exfoliate the layered metal coordination polymer prior to forming the nanostructure to obtain a dispersion of a metal coordination polymer layer. (Appendix 55) 55. The method of claim 54, wherein the steps of exfoliating the layered metal coordination polymer and removing at least a portion of the coordinating organic linker to form an oxide nanostructure are performed simultaneously. (Appendix 56) 56. The method of claim 54 or 55, wherein the metal coordination polymer is dispersed in a solvent and agitated for a period of time effective to exfoliate the metal coordination polymer to obtain a dispersion of a metal coordination polymer layer prior to removing at least a portion of the coordinating ligand to form the nanostructure. (Appendix 57) 57. The method of claim 56, wherein the metal coordination polymer is agitated by heating and / or ultrasonic treatment. (Appendix 58) 58. The method of any one of claims 50 to 57, wherein prior to removing at least a portion of the coordinating ligands to form the nanostructure, the metal coordination polymer is decomposed in an organic solvent and reconstituted from the organic solvent by evaporation to change the morphology of the metal coordination polymer. (Appendix 59) 59. The method according to claim 58, wherein the concentration of the metal coordination polymer dissolved in the organic solvent is about 4 M to about 120 M. (Appendix 60) 60. The method of claim 58 or 59, wherein the evaporation of the organic solvent is carried out at a temperature of about -20°C to about 40°C and a vapor pressure of about 0.1 kPa to about 10 kPa. (Appendix 61) 61. The method according to any one of claims 58 to 60, wherein the organic solvent is selected from an alcohol, an amine, or a polar aprotic solvent. (Appendix 62) 62. The method according to any one of claims 50 to 61, wherein the metal atom is a metal ion. (Appendix 63) 63. The method of claim 62, wherein the metal ion is monovalent or multivalent. (Appendix 64) 64. The method of any one of appendixes 50 to 63, wherein the metal atom has an oxidation state that can be increased upon oxidation at an acidic pH. (Appendix 65) 65. The method of any one of claims 50 to 64, wherein removing at least a portion of the coordinating organic linker destabilizes the metal atom, which in turn forms a stable nanostructure. (Appendix 66) 66. The method according to any one of claims 50 to 65, wherein the morphology of the nanostructure is the same as the morphology of the metal coordination polymer. (Appendix 67) 67. The method of any one of claims 50 to 66, wherein the nanostructure is a porous oxide nanostructure, and the step of removing at least a portion of the coordinating organic ligands forms the porous nanostructure. (Appendix 68) 68. The method of any one of appendix 50 to 67, wherein the nanostructure is polycrystalline. (Appendix 69) 69. The method of any one of claims 50 to 68, wherein one or more adsorbed species are adsorbed onto a surface of the nanostructure to form one or more heterojunctions on the surface of the nanostructure. (Appendix 70) 71. The method of claim 69, wherein the one or more species are adsorbed onto the surface of the nanostructure by removing at least a portion of the organic linker in the presence of the adsorbed species. 71. The method of claim 69 or claim 70, wherein the adsorbed species comprises one or more metal atoms different from the metal atom of the metal coordination polymer. (Appendix 72) 72. The method of any one of claims 69 to 71, wherein the adsorbed species is a metal, nonmetal, metalloid, or metalloid, or an oxide or nonoxide salt thereof, or a combination thereof. (Appendix 73) 73. The method of any one of claims 69 to 72, wherein the adsorbed species comprises one or more species selected from the group consisting of carbon, sulfur, nitrogen, arsenide, telluride, manganese, iron, nickel, copper, phosphide, or zinc. (Appendix 74) 74. The method of any one of claims 69 to 73, wherein the adsorbed species is a metal-based species that is oxidized after adsorption onto the surface of the nanostructure. (Appendix 75) 75. The method of any one of claims 50 to 74, wherein the metal coordination polymer is as defined in any one of claims 1 to 26 or is prepared from the process described in any one of claims 27 to 46. (Appendix 76) A nanostructure prepared using the method according to any one of claims 50 to 75. (Appendix 77) 77. The nanostructure of claim 76, wherein the nanostructure is a metal oxide. (Appendix 78) 78. The nanostructure of claim 77, wherein the metal oxide is a porous metal oxide. (Appendix 79) 79. The nanostructure of any one of appendix 76 to 78, wherein the nanostructure is a nanosheet. (Appendix 80) 80. The nanostructure of claim 79, wherein the nanosheet has a thickness of about 1 nm to about 100 nm. (Appendix 81) 81. The nanostructure of any one of claims 76 to 80, comprising a plurality of nanosheets, the plurality of nanosheets being stacked to form a stacked nanostructure. (Appendix 82) A porous metal oxide nanosheet having a thickness of about 1 nm to about 100 nm. (Appendix 83) 83. The nanosheet of claim 82, wherein the nanosheet has a thickness of about 1 nm to about 20 nm. (Appendix 84) 84. The nanosheet of claim 82 or 83, wherein the nanosheet comprises one or more oxides selected from cerium, copper, manganese, iron, nickel, titanium, zirconium, and zinc. (Appendix 85) 85. The nanosheet of any one of claims 82 to 84, wherein one or more adsorbed species are adsorbed onto a surface of the nanosheet to form one or more heterojunctions on a surface of the nanostructure. (Appendix 86) 86. The nanosheet of claim 85, wherein the adsorbed species is a metal, nonmetal, metalloid, or metalloid, or an oxide or nonoxide salt thereof, or a combination thereof. (Appendix 87) 87. The nanosheet of claim 86, wherein the adsorbed species comprises one or more species selected from the group consisting of carbon, sulfur, nitrogen, arsenide, telluride, manganese, iron, nickel, copper, phosphide, or zinc. (Appendix 88) A catalyst composition comprising the nanostructure according to any one of claims 76 to 87. (Appendix 89) 89. The catalyst composition of claim 88, wherein the catalyst composition is a photocatalyst or a CO oxidation catalyst composition. (Appendix 90) 88. Use of the nanostructure according to any one of claims 76 to 87 as a catalyst.

Claims

1. 1. A layered metal coordination polymer comprising two or more layers, Each layer comprises a metal atom coordinated to an organic linker to form a metal coordination polymer layer; wherein the organic linker has the formula (1): X-R 1 (1) and wherein the compound is selected from one or more compounds having the structure: During the ceremony: X is a metal binding moiety for coordinating to a metal atom; and R 1 is an alkyl, alkenyl or alkynyl group substituted with one or more halogens for forming an electrostatic interaction with an adjacent metal coordination polymer layer to form said layered metal coordination polymer.

2. 2. The layered metal coordination polymer of claim 1, wherein said layered metal coordination polymer comprises a plurality of labile ions interspersed between said metal coordination polymer layers that form said electrostatic interactions between said one or more halogens of said organic linkers of each metal coordination polymer layer to form said layered metal coordination polymer.

3. 3. The layered metal coordination polymer of claim 2, wherein the electrostatic interactions between the labile ions interspersed between the metal coordination polymer layers and the one or more halogens of the organic linker of each metal coordination polymer layer are substantially orthogonal to the coordination bond between the metal binding moiety (X) and the metal atom in the metal coordination polymer layer.

4. The layered metal coordination polymer according to any one of claims 1 to 3, wherein the one or more halogens are selected from the group consisting of F, Cl, Br, and / or I, or one or more halides thereof selected from the group consisting of Li, Na, K, Rb, and / or Cs.

5. 5. The layered metal coordination polymer of claim 1, wherein the metal binding moiety (X) is a monodentate or bidentate ligand that forms bridging coordination bonds with two or more metal atoms to form the metal coordination polymer layer, and the metal binding moiety (X) comprises a carboxylate, amine, hydroxyl, thiol, or nitrile.

6. 6. The layered metal coordination polymer according to claim 1, wherein the organic linker is trifluoroacetic acid, trichloroacetic acid, tribromoacetic acid, or triiodoacetic acid.

7. The metal atom is Ce. 3+ , Ce 4+ , Ti 4+ 7. The layered metal coordination polymer according to claim 1, wherein the metal ion is selected from the group consisting of Zr4+, Zr2+, and Zn2+.

8. The metal coordination polymer has the formula Ce(TCA) 2 (OH) 2 ・2H 2 The layered metal coordination polymer according to any one of claims 1 to 7, which is a cerium metal coordination polymer having O.

9. 9. The layered metal coordination polymer of claim 8, wherein the cerium metal coordination polymer is characterized by an X-ray powder diffraction (XRD) pattern comprising one or more major peaks located at about 7.2, 8.1, 10.9, 20.6, 22.0, 23.1, and 23.2 degrees (2θ).

10. A process for preparing the layered metal coordination polymer of any one of claims 1 to 9, comprising the steps of: combining a metal atom source with said organic linker to form said layered metal coordination polymer; Including, The process, wherein the step of combining the metal atom source and the organic linker comprises mixing aqueous solutions containing the metal atom source and the organic linker to form the layered metal coordination polymer.

11. The process of claim 10 , wherein the step of forming the layered metal coordination polymer comprises electrodeposition.

12. 12. The process of claim 11, wherein the initial pH of the aqueous solution during electrodeposition is less than about 7.

13. 13. The process of claim 11 or claim 12, wherein the electrodeposition is carried out in an oxygen generating region of the aqueous solution comprising the metal atom source and the organic linker.

14. 14. The process of any one of claims 10 to 13, wherein the layered metal coordination polymer is decomposed in an organic solvent and reconstituted by evaporation of the organic solvent, the reconstitution from the organic solvent changing the morphology of the metal coordination polymer.

15. The process of any one of claims 10 to 14, wherein the layered metal coordination polymer is exfoliated to provide one or more metal coordination polymer layers.

16. 1. A method for forming a nanostructure, comprising: Providing a layered metal coordination polymer according to any one of claims 1 to 9; and removing at least a portion of the organic linker to form the nanostructure; The method comprising:

17. 17. The method of claim 16, wherein the layered metal coordination polymer is exfoliated prior to removing at least a portion of the organic linker to form the nanostructure to obtain a dispersion of a metal coordination polymer layer.

18. 18. The method of claim 16 or 17, wherein prior to removing at least a portion of the organic linker to form the nanostructure, the metal coordination polymer is decomposed in an organic solvent and reconstituted from the organic solvent by evaporation.

19. A catalytic composition comprising nanostructures prepared using the method of any one of claims 16 to 18.

20. Use of a nanostructure prepared by the method according to any one of claims 16 to 19 as a catalyst.